Detection and differentiation of Salmonella Typhimurium and Salmonella Enteritidis in poultry meat using a machine learning-enabled paper chromogenic array sensor approach - Zhen Jia; Stephen N. White; Boce Zhang; Wei-Shinn Ku; Xian Gao; Lucas Harper; Ranju Kafle; Laura Garner; Kathryn Owen (Food Control, 2027)

Consumer preferences and consumption patterns in Nigeria: Influence of contributing factors and future perspectives - Stephen A. Fagbemi; Oluwapelumi E. Foluso; Praise J. Agbi; Opeyemi I. Alabi; Omolara R. Adegbanke; Victor N. Enujiugha (Food and Humanity, 2026)

Characterization of CANDU coolant void reactivity using nuclear data sensitivities and assessment of ZED-2 experimental configurations for code validation - Stephen N. Marshall; Julian E. Atfield; David R. Novog (Annals of Nuclear Energy, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Sex and base excision repair as key susceptibility factors for alkylation-induced mutations, toxicity and hepatic cancer - Jennifer E. Kay; Joshua J. Corrigan; Lindsay B. Volk; Amanda L. Armijo; Norah A. Owiti; Lee J. Pribyl; Ilana S. Nazari; Dorothea K. Torous; Svetlana L. Avlasevich; Robert G. Croy; Dushan N. Wadduwage; Sebastian E. Carrasco; et al. (DNA Repair, 2026)

Understanding the deactivation mechanisms of ethanol conversion over Cu-Y/Beta catalyst - Meijun Li; Stephen C. Purdy; Shivangi N. Borate; Junyan Zhang; Kinga A. Unocic; Michael Cordon; Hunter Jacobs; Zili Wu; Jacklyn Hall; A. Jeremy Kropf; Brian H. Davison; James W. Harris; et al. (Chemical Engineering Journal, 2026)

Human and Porcine Marginal Chordal Forces in a Vacuum Based Physiological In Vitro Mitral Valve Model - Mads V. Ancker; Sam E. Stephens; Justin T. Jack; Neil B. Ingels; Jonathan F. Wenk; Søren N. Skov; Surendra K. Chawla; Ajit. P. Yoganathan; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Introduction This study aimed to quantitatively investigate the role of marginal chordae of the mitral valve during static closure by analyzing the force within these chordae and its potential correlation with the transvalvular pressure. Materials and Methods Porcine (n = 10) and human (n = 4) mitral valves were mounted in a saddle-shaped annulus clamp, while an in vitro system was utilized to replicate a physiological systolic blood pressure by vacuum pressure applied to the atrial side of the valve. A Millar pressure catheter and force transducers (“C-gauges”) were used to acquire the data. Strut chordal force was recorded simultaneously with the marginal chordal force, to serve as a verification of the employed equipment. Results The marginal chordal force in porcine and human averaged to 0.012 N ± 0.008 N and 0.006 N ± 0.008 N respectively at peak systolic pressure of 120 mmHg. Additionally, a simplified finite element study was conducted and supports low marginal forces relative to intermediary chords. Discussion & Conclusion This low force calls into question the traditionally-described role of the marginal chordae in preventing mitral prolapse at closure. The chords do, however, still show signs of assisting with the leaflets’ positioning. The relationship between marginal chordal forces and transvalvular pressure varies significantly across experiments, further obfuscating their role in normal valvular function.

Beyond evaporites: Assessing hypersalinity using boron-based salinity proxies - Mariano N. Remírez; Geoffrey J. Gilleaudeau; Swapan K. Sahoo; Lucía Guerra; Chelsea Pederson; Eduardo Piovano; Alan J. Kaufman; Adrian Immenhauser; Stephen W. Lokier; Thomas J. Algeo (Chemical Geology, 2026)

Taeniolabis simmonsae (Multituberculata, Taeniolabididae) from the early Paleocene of the Denver Basin, Colorado: implications for taeniolabidid taxonomy and biochronology of the Puercan North American Land Mammal Age - David W. Krause; Lucas N. Weaver; Stephen G. B. Chester; Craig S. Scott; Ken Weissenburger; Jordan W. Crowell; Rudolph R. Hummel; Tyler R. Lyson (Journal of Mammalian Evolution, 2026)

MATHFI: A Multi-scale Adaptive Thresholding and Hierarchical Feature Integration Network for Retinal Vessel Segmentation and Quantitative Biomarker Analysis - Michelle N. Tolentino; Stephen Lloyd C. Abenoja; Jonathan C. Morano; Dan Michael A. Cortez; Ymir M. Garcia; Kuo-Sheng Cheng (Journal of Medical and Biological Engineering, 2026)

The action of marimastat, a metalloprotease inhibitor, on the coagulant, hemorrhagic, and neuromuscular activities of Lachesis muta (South American bushmaster) venom - Vitória S. Proença-Hirata; Isabele N. Oliveira; Gabrielly C. Souza-Gomes; Samuel R. Dias; Hugo A. Ghirotti; Sofia N.S. Azevedo; Poliana J. Demico; Francis L. Pacagnelli; Rogério Giuffrida; Gisele A. Nai; Nelson J. Silva; Kristian A. Torres-Bonilla; et al. (Toxicon, 2026)

Erratum to “Air pollution is linked to divergent cortical thickness patterns in brain regions vulnerable to Alzheimer’s disease” [Neurotoxicology 115 (2026) 103495] - Lauren E. Salminen; Xinhui Wang; Andrew J. Petkus; Christine Fennema-Notestine; Jeremy A. Elman; Donald J. Hagler; Joel D. Kaufman; Joshua Millstein; Meredith N. Braskie; Joshua Liu; Hyung Jin Cho; Deydeep Kothapalli; et al. (NeuroToxicology, 2026)

Actionable knowledge for agroecological transformation: a critical realist analysis of co-innovation in a transdisciplinary project - Stephen Leitheiser; Darleen van Dam; Jonas Egmose; Cecilia Zagaria; Henrik Hauggaard-Nielsen; Yanka Kazakova; Raquel Luján Soto; Bertrand Dumont; Carla Barlagne; Linn N. Schaan; Julie Duval; Walter A. H. Rossing (Sustainability Science, 2026)
Transdisciplinarity and the production of actionable knowledge with and for societal actors is a central feature of sustainability science. Yet questions remain about whether such efforts genuinely challenge the structural roots of unsustainability or inadvertently reinforce them in pursuit of proximate impacts. This paper responds to calls for more critical monitoring and evaluation by evaluating a transdisciplinary Horizon Europe project, Agroecology-TRANSECT. We employ a critical realist approach to analyze qualitative data from project work with 11 territorially-rooted European networks focused on agroecological transition (called ‘innovation hubs’(IHs). This analysis was developed as a part of the project’s co-innovation approach, with iterative reflection and validation embedded throughout the research process. Our analysis sought to explain how observed actionable knowledge outcomes came about (or did not) by examining multi-level contextual factors. Societal effects were assessed using a conforming-transforming distinction informed by political agroecology. We found that the project’s co-innovation approach has resulted in many instances of actionable knowledge production among IHs, including new conceptual and strategic developments, and providing legitimacy and resources for instrumental gains like policy change. While the project served to amplify the agency of IHs, the extent to which this resulted in transformative societal effects varied. Effects were largely shaped by the IHs’ pre-existing strategic orientation (i.e. whether they already worked to challenge, alter, or replace dominant institutional structures and reconfigure their power relations). For some IHs, structural constraints – namely, market dependency, social acceleration, and state mediation of capital accumulation – limited the extent to which their network could generate transformative effects. We conclude that co-innovation’s complex-adaptive systems approach should widen its scope of system boundaries, integrating social structural analysis to reveal root causes of blockages and enhance agential effectiveness. For actionable knowledge to achieve societal effects that are both proximate and transformative, transdisciplinary research should prioritize involvement of partners with pre-existing transformative strategies, and devote creative focus to building enabling societal contexts.

Longitudinal analysis of decision-making deficits in binge-eating disorders using drift diffusion modeling - Glen Forester; Brianne N. Richson; Erin E. Reilly; Lisa M. Anderson; Stephen A. Wonderlich; Lauren M. Schaefer (Appetite, 2026)

Air pollution is linked to divergent cortical thickness patterns in brain regions vulnerable to Alzheimer’s disease - Lauren E. Salminen; Xinhui Wang; Andrew J. Petkus; Christine Fennema-Notestine; Jeremy A. Elman; Donald J. Hagler; Joel D. Kaufman; Joshua Millstein; Meredith N. Braskie; Joshua Liu; Hyung Jin Cho; Deydeep Kothapalli; et al. (NeuroToxicology, 2026)

Feasibility of Home-Delivery and Voucher-Based Produce Prescription Programs Among Adults with Overweight or Obesity and Nutrition Insecurity - Hailey N. Miller; Wura Olawole; Ashauna Lee; Azuka Amaka Ngige; Philip Okonkwo; Joyline Chepkorir; Janna Stephens; Cheryl R. Himmelfarb (Journal of Nutrition Education and Behavior, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Disruption of the gut microbiota in regulator of G protein signaling 14 knockout (RGS14 KO) mice alters the metabolome and reduces enhanced exercise capacity - Candace R. Longoria; Daniel D. DeSio; Marko Oydanich; Xiaoyang Su; Eric N. Chiles; Lee J. Kerkhof; Olufunmilola Ibironke; Max M. Häggblom; Nathan P. Wages; John J. Guers; Dorothy E. Vatner; Stephen F. Vatner; et al. (European Journal of Applied Physiology, 2026)

Application of a ZED-2 benchmark experiment to CANDU coolant void reactivity validation - Stephen N. Marshall; Julian E. Atfield; David R. Novog (Annals of Nuclear Energy, 2026)

Distribution, abundance and ecological associations among two species of native mussels (Gonidea angulata and Margaritifera falcata) and one invasive clam species (Corbicula fluminea) in the Columbia River Basin, North America - Nathaniel G. Neal; Stephen M. Bollens; Alexa N. Maine; Timothy D. Counihan; Gretchen Rollwagen-Bollens (Aquatic Sciences, 2026)
Native freshwater mussels are declining globally, thus, determining factors associated with bivalve distribution and abundance is critical for native mussel conservation. In the Columbia River Basin, Gonidea angulata (western ridged mussel) is highly threatened, while Margaritifera falcata (western pearlshell) and the invasive clam Corbicula fluminea (Asian clam) are more common. We conducted 147 snorkel surveys, collected environmental data and performed statistical tests to quantify which variables were significantly associated with presence and abundance of these taxa. Variation in G. angulata presence and/or abundance were best explained by impervious surface proportion and annual air temperatures (mean and maximum). Margaritifera falcata presence and/or abundance were best explained by host fish presence, G. angulata presence, dissolved oxygen, and elevation. Corbicula fluminea presence and/or abundance were best explained by substrate size, impervious surface proportion, and annual air temperatures. Microhabitat and landscape variables explained some variation in bivalve presence and abundance, but the inclusion of watershed as a random effect increased the explanatory value. Consideration of species-specific habitat preferences and watershed-level variation could improve regional management in response to native mussel declines and invasive clam expansion.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Unveiling the Biosynthetic Landscape of Endophytic Streptomyces sp. PGLac3x via Growth Optimization and Whole-Genome Analysis - C. E. Ezeobiora; N. E. Maningi; D. H. Amin; N. H. Igbokwe; C. F. Okpalanwa; C. M. Stephen; U. E. Mendie (Indian Journal of Microbiology, 2026)

An Integrated Biostratigraphy and Chemostratigraphy for the Dawn of the Jurassic (the Hettangian Stage in the Cheshire Basin, UK) - Clemens V. Ullmann; Magret Damaschke; Stephen P. Hesselbo; Mengjie Jiang; Kathryn Lawrence; Melanie J. Leng; Emanuela Mattioli; Jérold Bancalin; Kevin N. Page; Nour Pudal; Micha Ruhl; Ricardo L. Silva (Journal of Earth Science, 2026)
Highly resolved Earth System reconstructions of the Earliest Jurassic are hampered by complexities of existing reference sections. Here, an integrated stratigraphy of two core records is constructed, representing the expanded Hettangian sequence of the Cheshire Basin, UK. The combined record is based on ammonite and calcareous nannofossil biostratigraphy, organic carbon isotope ratios, and bulk rock chemical properties of legacy core material (Wilkesley) and Prees 2C, cored in 2020. Combination of ammonite records of these cores allows for substantial reductions in the uncertainties of ammonite zonal and subzonal boundaries. The new organic carbon isotope chemostratigraphy for the Hettangian of the Cheshire Basin improves temporal resolution compared to other published records, in particular for the Tilmanni and Planorbis zones. The limited occurrence of organic matter enrichment intervals associated with negative organic carbon isotope spikes in the Cheshire Basin allows for the identification of minor drifts throughout the Hettangian and into the Sinemurian which are likely of global significance. Organic carbon and macrofossil carbonate carbon isotope ratios largely follow the same trends in the Hettangian, but exhibit contrasting changes in the early Liasicus Zone, commensurate with a decrease in the isotopic difference of both records of ca. 2‰.

Regulation of survival, growth, and metabolism by neuronal mTOR - Stacy A. Hussong; Raquel Burbank Roberts; Jonathan J. Halloran; Stephen F. Hernandez; Candice E. Van Skike; Angela O. Dorigatti; Nicholas DeRosa; Michael E. Walsh; Vanessa Y. Soto; Daniel A. Pulliam; Holly Van Remmen; Steven N. Austad; et al. (GeroScience, 2026)

Scientists’ warning on the global destruction of rock outcrop ecosystems - Luiza F. A. de Paula; Lucas N. Perillo; Gianluigi Ottaviani; Flávio F. Carmo; Mandar N. Datar; Katherine C. Enebeli‐Ekwutoziam; Bruno Fogliani; Stephen D. Hopper; Aboli Kulkarni; Hans Lambers; Rafael F. Magalhães; Frederico S. Neves; et al. (Conservation Biology, 2026)
Rock outcrops are geological formations that harbor a highly specialized biota adapted to harsh environmental conditions that differ from their surrounding landscapes. They are globally distributed, especially in old, highly weathered landscapes, and can function as habitat islands containing high levels of endemism and distinct evolutionary lineages. Despite their ecoevolutionary importance, rock outcrops remain largely overlooked in global conservation policy, ecosystem typologies, and biodiversity monitoring frameworks. Extractive activities directly remove the geological substrate that underpins these habitats, and climate change intensifies drought, heatwaves, and hydrological instability. Rising global demand for energy‐transition metals required for decarbonization is expected to further accelerate these pressures, particularly in biodiverse regions of the Global South where governance is weaker. Given that rock outcrop ecosystems are ecologically and evolutionarily significant, we devised a policy‐relevant conservation roadmap structured around prevention, mitigation, restoration, and governance issues. Priority actions include recognizing rock outcrops as unique ecosystems in global classifications and ecosystem typologies, integrating them into biodiversity monitoring frameworks, and improving the identification of key biodiversity areas and the International Union for Conservation of Nature (IUCN) Red List of Ecosystems assessments. We call for stronger environmental impact assessments, cumulative‐impact evaluations for mining and quarrying projects, and the designation of mining and quarrying exclusion sites of high irreplaceability. Coordinated international policy, improved ecological data, and meaningful engagement with local and Indigenous communities are essential to safeguard these ancient ecosystems before further, irreversible losses occur.

The Impact of Pulp Mill Closures on Pine Plantation Investment Returns in the US South - Bruno Kanieski da Silva; Mateus N. I. Sanquetta; Hannah Knight; Stephen M. Kinane; Erin Lincoln; Jacek Siry; Yanshu Li (Journal of Forestry, 2026)
Pulp and paper mill closures have had a significant impact on the forest sector in the southeastern US over the last decade. These mills consume large volumes of pulpwood, and a complete shutdown of their operations has potential to significantly reduce pulpwood prices. In this study, we investigated the effects of pine pulpwood stumpage prices on financial returns in four different timber markets in the southeastern US (northeast and northwest Florida, south Georgia and east South Carolina). Through simulations of two stand densities (300 and 600 trees per acre), three thinning treatments (no-thinning, one and two thinnings), we assessed the Land Expectation Value (LEV) under scenarios of 50% and 100% reductions of pulpwood prices. In addition, through an optimization model, we estimated the changes on the stumpage prices of pine chip-n-saw and sawtimber required to offset the losses with pulpwood market. Our results indicated that although lower pulpwood prices decrease timberland investment returns, some silvicultural strategies, like thinning trees less often and planting fewer trees per acre, will suffer lower financial losses. Also, although chip-n-saw and sawtimber prices might compensate for lower pulpwood demand, it is unlikely that we will observe higher stumpage prices of any product in the near future. Our results indicate that landowners should develop adaptive strategies to ensure the economic viability of timberland investments and face these market shifts.

In situ spectroscopic analysis and kinetic modeling of plasma-enhanced methane combustion - Fatemeh Afshar Ghahremani; Mariano Rubio; Curtis Hauck; Caleb Medchill; Fokion N. Egolfopoulos; Stephen B. Cronin (Fuel, 2026)

Greater recalled pain and movement-evoked pain are associated with longer 400-m walk and repeat stair climb timein older adults: the study of muscle, mobility, and aging - Theresa Mau; Corey B. Simon; Haley N. Barnes; Megan Hetherington-Rauth; Scott R. Bauer; Elsa S. Strotmeyer; Nancy E. Lane; Michael C. Rowbotham; Ashley A. Weaver; Terri L. Blackwell; Yurun Cai; Nancy W. Glynn; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Achieving self-healing in emission control catalysts via atom trapping - Hien N. Pham; Andrew DeLaRiva; Chase Thompson; Eric J. Peterson; Andreas Sundermann; Mikayla Romero; Stephen Porter; Hao Xu; Karl Kharas; Konstantin Khivantsev; Janos Szanyi; Xiaohong S. Li; et al. (Chemical Engineering Journal, 2026)

Nitric oxide-releasing dextran surface with enhanced albumin affinity mitigates infection and foreign body reaction - Yi Wu; Aasma Sapkota; Sarah N. Wilson; Stephen G. Thompson; Mark R. Garren; Hitesh Handa; Elizabeth J. Brisbois (Carbohydrate Polymers, 2026)

Mitigation of Extreme Salinity Stress at Flowering Stage by Piriformospora indica in Contrasting Rice Genotypes - O. P. Reshna; Ch. L. N. Manikanta; D. Lishali; Joy Michal Johnson; Roy Stephen; M. M. Viji; R. Beena (Journal of Crop Health, 2026)

At least 10 minutes of seated rest is required for stabilisation of blood-based hydration biomarkers - Kirsty M. Reynolds; Samantha N. Rowland; Mark P. Funnell; Tom Clifford; Liam M. Heaney; Stephen A. Mears; Stephen J. Bailey; Lewis J. James (European Journal of Applied Physiology, 2026)
Postural changes elicit well-described haemodynamic effects on plasma volume, affecting blood-based hydration variables. While the time required for plasma volume stabilisation is well-established for supine rest, less is known for blood samples collected in a seated position, as is commonplace in physiology and nutrition experiments. Seventeen healthy participants (9 males; 8 females) stood stationary for 20 min in an upright position before walking on a treadmill at 4 km/h for 20 min (to simulate active travel to blood sampling locations). After walking, participants sat upright (within 7 ± 1 s), and venous blood samples were drawn from a cannula at 0, 5, 10, 20, 30 and 40 min after sitting. Time points were compared to 40 min. At 0 and 5 min, blood (0 min: -3.3%; P < 0.001; 5 min: -1.2%; P = 0.034) and plasma (0 min: -5.9%; P < 0.001; 5 min: -1.7%; P = 0.035) volume were lower than 40 min values. Conversely, plasma osmolality was higher at 0 min (+ 0.61%; P = 0.005) and 5 min (+ 0.55%; P = 0.007), whilst blood/plasma volume and plasma osmolality were not different from 10 min onwards. Plasma sodium, potassium and chloride concentrations were not different from 40 min throughout the sitting period ( P ≥ 0.056). These data demonstrate that blood/plasma volume, as well as plasma osmolality were affected by posture and/or walking, but all are not significantly different from 40 min within 10 min of seated rest. Therefore, studies involving blood-based hydration measures taken in an upright seated position should allow at least 10 min of postural control prior to sampling.

HABS-BLOCKS© Reduced Harmful Algal Bloom Activity in an in-Lake Limno-Corral Mesocosm Case Study at Grand Lake St. Marys, Ohio (USA) - Stephen J. Vesper; Haley N. Hoehn; Morgan C. Grunden; Stephen J. Jacquemin (Bulletin of Environmental Contamination and Toxicology, 2026)
HABS-BLOCKS© infused with glucose have been shown to reduce cyanobacterial populations and microcystin (MC) concentrations in laboratory mesocosm studies. An in situ limno-corral (LC) mesocosm study of HABS-BLOCKS© was conducted for two weeks during the 2025 algal bloom in Grand Lake St. Marys (GLSM) (Ohio, USA). Thirty HABS-BLOCKS© or Dummy HABS-BLOCKS© (contain no glucose) were added to three treated or three control LCs, respectively. Each LC holds approximately 1,000 L of lake water. After two weeks, cyanobacterial cell densities were 89% lower in treated compared to control LCs, and chlorophyll-a and phycocyanin concentrations averaged 80% and 77% lower, respectively. Initial MC concentrations averaged 41.4 µg/L, but treated LCs showed an average 89% reduction after two weeks. At the same time point, neither physical nor chemical parameters measured (except turbidity) were significantly different in the treated and control LCs. The treatment of GLSM water with HABS-BLOCKS© resulted in suppression of the Planktothrix population and decrease in MC concentrations. Further studies of HABS-BLOCKS© are needed to evaluate their applicability and safety.

Origins and environmental impacts of distal rhyolitic tephra layers on Chatham Island, New Zealand - Anna L. Miller; Simon J. Barker; Katherine A. Holt; Stephen B. Piva; Colin J. N. Wilson (Journal of Quaternary Science, 2026)
Chatham Island, ~700 km east of mainland New Zealand, preserves several macroscopic tephra beds, sourced from the central Taupō Volcanic Zone (TVZ) some 850 km away. These layers, often enclosed within peat, provide insights into the eruptive characteristics, timing and paleoenvironmental impacts of large explosive rhyolitic eruptions in a distal setting. We report the nature, origins and impacts of these tephras by documenting bulk and centimetric‐scale stratigraphic changes in glass shard geochemistry and millimetric‐scale changes in pollen assemblages in the enclosing peats. Three layers are investigated: the ~25.5 ka Kawakawa–Ōruanui Tephra (KOT), the ~345 ka Rangitawa Tephra and one newly discovered tephra. The KOT shows no stratigraphic variability in glass composition throughout ~15 cm thickness. The Rangitawa Tephra contains three glass populations that were deposited sequentially throughout the eruption and further link this tephra to the Whakamaru supereruption. The new tephra has two glass populations and is matched to the ~322 ka Matahina caldera‐forming eruption. High‐resolution sampling of peat bracketing the KOT and Rangitawa Tephra reveals marked changes in local vegetation following the deposition of both tephras. The nature of the changes varies between events and can be explained by differing paleoenvironmental settings, climate and/or tephra thickness.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Forest conversion alters taxonomic and functional diversity of oribatid mite communities through shifts in environmental conditions in Taita Hills, Kenya - Stephen K. Kamesa; Esther N. Kioko; Yannan Chen; Jun Chen (Pedobiologia, 2026)

Firewood, charcoal or electricity? Gender gaps in cooking, heating, and lighting energy use in Zambia - John N. Ng'ombe; Cleopas G. Sambo; Fafanyo Asiseh; Stephen Prah; Obed Quaicoe; Wisdom Takumah (Energy Policy, 2026)

Emerging tools to advance neuroethology in butterflies and moths - Francesco Cicconardi; Max S. Farnworth; Robin Grob; Donya N. Shodja; Caroline N. Bacquet; Basil el Jundi; Arnaud Martin; Stephen H. Montgomery (Journal of Comparative Physiology A, 2026)
Butterflies and moths have played historically important roles in developing our understanding of both ecology and evolutionary biology, and neuroethology. In both contexts, the diversity of behavioral strategies and specializations displayed by different Lepidoptera make them informative case studies. However, as in neuroscience more broadly, lepidopteran neuroethology has tended to focus on intricate functional studies within a small number of the most tractable species. In contrast, ecologists and evolutionary biologists have often taken a broader view, using phylogenetic and comparative approaches to extract general patterns of diversification, and to exploit the diversity of butterflies and moths to understand general evolutionary processes. Uniting these approaches and traditions has been restricted, largely due to technical challenges of working with unestablished study systems and a lack of resources beyond basic tools. Now, however, the prospects for broader comparative studies of the neural basis of behavior within a phylogenetic and/or ecological framework are increasingly positive. This is in large part due to the emergence of new molecular sequencing approaches and associated tools. These allow for the survey of cell types, the spatial location of their soma, development of new cell-type markers for targeted analyses, and quantification of the dynamic regulation of gene expression at a tissue or cell specific level. Results of these molecular methods can be combined with technical developments in free flying behavioral experiments in tethered animals that permit neural recordings of natural behavior, and functional genetics tools that can allow for more precise manipulation of these behaviors or the neural structures that support them. Here, we review these new approaches, their potential application, and discuss how we can use them to advance the development of new, integrative systems for studying the neural basis of behavior in butterflies and moths.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A comparison of dating models for reservoir sediment records using mass accumulation, radioisotopes, and Bayesian statistics - Benjamin C. Webster; Joseph M. Smoak; Richard S. Vachula; Matthew N. Waters; Stephen W. Golladay (Journal of Paleolimnology, 2026)
Paleolimnological investigations of reservoirs (i.e. human-made lakes) are becoming more common, establishing a need to explore dating approaches for sediment records from reservoirs. Traditional dating methodologies such as Constant Rate of Supply (CRS), 137 Cs, and Mass Accumulation Rate (MAR) have been utilized for sediment records from reservoirs for decades. However, with the advent of newer Bayesian approaches, such as the Bacon and Plum models, ambiguity persists for researchers when selecting a particular dating model. This study aims to quantify and compare the output differences among various dating models for the same sediment records and provide a discission-making framework based on practical constrains, rather than to validate which model is most accurate. Here we investigated the differences among age model outputs (dates and sedimentation rates) generated with CRS, MAR, Plum, and Bacon for three reservoirs in the Southeastern United States. Though they are all viable age models, their utility varies with research question, application, and financial cost. MAR and Bacon produced similar linear age models. The sedimentation rate for MAR was a static value throughout the record, while Bacon’s had more variable and significantly larger sedimentation rate than MAR for each reservoir studied. Both MAR and Bacon are more practical when there is a limited budget or less time for analysis. CRS and Plum produced similar non-linear age models, with CRS and Plum having the smallest and second smallest region of error, respectively. Similarly, CRS and Plum sedimentation rates exhibited aligned variations of sedimentation rates for two of the three sediment records analyzed. CRS and Plum dates and sedimentation rates were more similar when sediment records had a larger excess 210 Pb total inventory. We found the smallest differences among model outputs, < 5% difference based on a RMSE normalized ‘record age ratio’, when models utilized the same input data (i.e. top–bottom dates for MAR with Bacon and radioisotope for CRS with Plum). Generally, CRS and Plum would be preferred when there is ample time and funds for the lengthy radioisotope analysis and its higher costs. If there are additional known dates to incorporate into a model, we encourage the use of Plum.

Biomechanical Risk Factors for Head Impact during Falls in Mountain Biking - Rickie Ma; Sukhman Gosal; Freddie Kim; Gurvansh Mann; Stephen N. Robinovitch (Annals of Biomedical Engineering, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Association between late-life air pollution exposure and medial temporal lobe atrophy in older women - Xinhui Wang; Lauren E. Salminen; Andrew J. Petkus; Ira Frahmand; Joshua Millstein; Daniel P. Beavers; Mark A. Espeland; Guray Erus; Meredith N. Braskie; Paul M. Thompson; Margaret Gatz; Helena C. Chui; et al. (NeuroToxicology, 2026)

Recycling of ash particles during highly explosive eruptions: multiple glass populations in the 1.8 ka Taupō tephra - Simon J. Barker; Stephen B. Piva; Colin J. N. Wilson; David J. Lowe; Bruce L. A. Charlier; Alan R. Orpin (Bulletin of Volcanology, 2025)

Editorial perspective: How to minimize the risk of your manuscript being rejected: Perspectives to get your paper published in ‘Crop Protection’ - Jay Ram Lamichhane; Francis P.F. Reay-Jones; Sheng Qiang; Stephen N. Wegulo (Crop Protection, 2025)

Cognitive Intra-individual Variability in Cognitively Healthy APOE ε4 Carriers, Mild Cognitive Impairment, and Alzheimer’s Disease: a Meta-analysis - Stephen L. Aita; Victor A. Del Bene; Donald L. Knapp; Claire E. Demming; Vasilios C. Ikonomou; Tyler Owen; Ivan A. Campbell; Bailey N. Wagaman; Nicholas C. Borgogna; Joshua E. Caron; Robert M. Roth; Benjamin D. Hill (Neuropsychology Review, 2025)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Light and temperature as triggers for surface filamentous green algal blooms in shallow freshwater systems - Hannah R. Kemp; Alexandra Zieritz; Stephen J. Dugdale; Nico R. Helmsing; Suzanne Wiezer; Lisette N. de Senerpont Domis; Stephen C. Maberly; Martyn Kelly; Suzanne McGowan (Limnology and Oceanography, 2025)
Blooms of filamentous green algae (FGA) form dense mats at the surface of shallow freshwaters and have multiple negative impacts on aquatic ecosystem functions, services, and aesthetics. Although nutrient enrichment in freshwaters is a primary driver of excessive FGA growth, much less is known about other abiotic factors controlling bloom growth rate, extent, and timing. We performed a series of indoor mesocosm (Limnotron) experiments to investigate the effects of photosynthetically active radiation irradiance, photoperiod, and water temperature on the growth and surface bloom formation of FGA using underwater and surface photography. The results revealed that a minimum daily light integral of ~ 13.2 mol m −2 d −1 (a combination of photosynthetically active radiation irradiance measured at the water surface and daylength) was required for bloom formation and substantial FGA growth. Surface blooms did not occur at short daylengths (i.e., 8 h), whereas a long daylength (i.e., 16 h) allowed more time for photosynthetically derived gas bubbles to accrue in the FGA masses, making them rise to the water surface through buoyancy. We also found that temperatures between 16°C and 22°C were optimal for FGA to form surface blooms. As freshwater ecosystems are increasingly impacted by climate change, our study sheds new light on factors affecting the occurrence of surface blooms and helps identify when waterbodies may be at risk of FGA blooms in the future.

Microbial community response to spent mushroom substrate composting methods by phospholipid fatty acid analysis - Siobhan N. Jordan; Michael P. Farrell; Caroline T. Gilleran Stephens (Biocatalysis and Agricultural Biotechnology, 2025)

Correction to: Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Significant mortality of old trees across a dry forest landscape, Oregon, USA - James D. Johnston; Paige N. Stephens; Micah R. Schmidt; Sean M.A. Jeronimo; Amanda E. Brackett; Amarina E. Wuenschel; Danielle E.M. Ulrich; Riley H. Paine; Lou F. Duloisy; Skye M. Greenler; Andrew J. Larson; Derek J. Churchill (Forest Ecology and Management, 2025)

Integrating disturbance to improve our understanding of range-wide patterns in tree species abundance and demography - Andrew V. Gougherty; Hannah L. Clipp; Anantha M. Prasad; Matthew P. Peters; Stephen N. Matthews (Forest Ecology and Management, 2025)

Management of a restored wetland: challenges and lessons associated with the nutrient reduction potential of Beaver Creek Wetland in Grand Lake St. Marys Watershed - Morgan C. Grunden; Haley N. Hoehn; Theresa A. Dirksen; Stephen J. Jacquemin (Wetlands Ecology and Management, 2025)
Wetlands are becoming increasingly used as tools to help watersheds mitigate nutrient runoff as part of efforts to reduce the frequency of harmful algal blooms. Wetland restoration is needed given that the majority of these habitats have been lost to development/draining efforts on a global scale over the past few centuries. The objective of this study was to monitor nutrient reductions achieved with the restored (constructed in 2017) Beaver Creek Wetlands in the Grand Lake St. Marys Watershed (Ohio) as a result of active management incorporating communication and data driven decision making among collaborators as part of efforts to curtail runoff. A hydrologic budget was created by collecting flow measurements coupled with water samples collected weekly from 2018–2024 at the Stream Inflow and Wetland Outflow that were then analyzed for nutrients (SRP, TP, NO 3 -N) and sediment (TSS). As a result of active management, the wetland was able to capture approximately 1.2% (108 million m 3 ) of the total Beaver Creek flows over the monitoring period and reduce the total SRP, TP, NO 3 -N, and TSS loads of captured water by 78.4%, 78.1%, 95.7%, and 87.5%, respectively. Nutrients were removed at an average rate of 2.2, 3.8, 135, and 416 g/m 2 /yr for SRP, TP, NO 3 -N, and TSS, respectively, while only occupying a 0.23% footprint in the subwatershed. Despite these successes, however, GLSM remains hypereutrophic largely resultant of still untreated tributary loading flowing into the lake–thus, this study reinforces the importance of continued wetland restoration and management for meeting overarching nutrient reduction goals.

Cognitive flexibility of male rats is increased by augmented punishment in a reversal learning task but ketamine has no detectable long-term effects - Anthony N. Nist; Stephen J. Walsh; Timothy A. Shahan (Psychopharmacology, 2025)

The effect of dietary nitrate supplementation on resistance exercise performance: A dose–response investigation - Rachel Tan; Isabella G. Lincoln; Keonabelle K. Paniagua; Justin M. Foster; Lauren E. Wideen; Raymond T. Gerardo; Nathan J. Ornelas; Isaac Tchaprazian; Jeffrey Li; Michael Egiazarian; Samantha N. Rowland; Stephen J. Bailey; et al. (European Journal of Applied Physiology, 2025)
Dietary nitrate (NO 3 − ) can enhance skeletal muscle contractile function and explosive-type exercise by modulating type II muscle fibers; however, limited attention has been directed at exploring the optimal dosing guidelines and potential performance-enhancing effects of NO 3 − supplementation during resistance-type exercise. The purpose of our investigation was to examine potential dose–response effects of concentrated NO 3 − -rich beetroot juice on neuromuscular performance during resistance exercise. Eighteen resistance-trained men were assigned in a double-blind, randomized, crossover design, to four conditions to consume beetroot juice containing: negligible NO 3 − (PL); ~ 6 mmol NO 3 − (BR-LOW); ~ 12 mmol NO 3 − (BR-MOD); and ~ 24 mmol NO 3 − (BR-HIGH). Participants completed 1 set of vertical countermovement jumps (CMJ), 2 sets × 3 repetitions of barbell back squats, and 2 sets × 3 repetitions of barbell bench press 2.5 h post-supplementation. Plasma [NO 3 − ] increased in a dose-dependent manner ( P < 0.01). Plasma [nitrite] ([NO 2 − ]) increased in all BR conditions compared to PL ( P < 0.05), such that BR-MOD vs. BR-LOW ( P < 0.01) and BR-LOW vs. PL ( P < 0.01), but BR-HIGH was not different compared to BR-MOD ( P > 0.05). Performance was not different between conditions in CMJ, 50% one-repetition maximum (1RM) and 75%1RM back squats, or 50%1RM and 75%1RM bench press ( P > 0.05). The change in plasma [NO 2 − ] was significantly correlated with peak power ( r = − 0.65, P = 0.003), mean power ( r = − 0.52, P = 0.03), and mean velocity ( r = − 0.48, P = 0.04) during 50%1RM back squats following BR-LOW vs. PL but not in other conditions ( P > 0.05). This study indicates that dietary NO 3 − does not impact resistance exercise performance at any of the doses assessed in the current study.

Decadal Shifts in Southern Right Whale ( Eubalaena australis ) Recovery in South Australian Waters: Implications for Conservation and Management - Bridgette O’Shannessy; Luciana Möller; Robert D. McCauley; Guido J. Parra; Joshua N. Smith; Stephen Burnell; Claire M. Charlton (Marine Mammal Science, 2025)
Southern right whales ( Eubalaena australis ) have shown population recovery since protection from commercial whaling and are considered a flagship species for successful conservation management. However, recovery remains incomplete, with recent evidence suggesting slowed growth and variability in reproductive success. This project used 30 years of count data in Australia (1992–2022) to investigate long‐term trends in relative abundance at three key reproductive areas in South Australia. Varied rates of increase were observed, while recovery trends have moderated at the major aggregation area of Head of Bight (3.34%/year, 95% CI: 2.24, 4.44); higher growth rates were observed at Fowlers Bay, where recolonization has occurred (15.29%/year, 95% CI: 7.54, 24.33). Results support that recovery trends for the Australian population are dynamic and variable across decades. Drivers of variability may include saturation of certain areas, reoccupation of suitable habitats, spatio‐temporal disturbance, and changes to factors driving migration, including body condition, prey availability, and climate change. Decadal shifts in relative abundance indicate an expanding habitat range, highlighting the importance of suitable habitat and connective migration corridors, which are increasingly important during critical life stages. Adaptive conservation management and effective threat mitigation are essential to secure recovery of this threatened species in Australia.

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Late Quaternary Montane Forest Dynamics From Equatorial East Africa: A Biome Perspective - Esther N. Githumbi; Jemma Finch; Rahab N. Kinyanjui; Colin Courtney‐Mustaphi; Paul Musili; Stephen Rucina; Julius Lejju; Peter Liljenberg; Rob Marchant (Journal of Biogeography, 2025)
Aim Understanding environmental change over large spatial and temporal scales requires working at a broad ecological scale to enable cross‐site comparisons. This allows data‐based comparisons to dynamic vegetation model outputs, with utility for climate and land cover modelling. We synthesise multisite pollen data at the biome level to understand Equatorial Afromontane ecosystem response to climate change over the last 50,000 years and quantitatively document the timing, character and spatial patterns of ecosystem transitions. Location Mountains of Equatorial East Africa. Time Period Late Quaternary (50,000 cal year BP–present). Taxon Angiosperms (trees, shrubs and grasses), gymnosperms (conifers), pteridophytes (ferns) and bryophytes (clubmosses). Methods A literature review revealed 58 available published pollen sites from Equatorial East African Mountains. Original geochronological and palynological data were collated from 34 sites from the African Pollen Database (APD) and directly from authors. Pollen taxonomies were updated and harmonised using the African Plant Database. The geochronologies were reanalysed and radiocarbon data ( n = 219) were IntCal20 calibrated to develop linearly interpolated age‐depth models. The 636 pollen taxa were grouped into 21 plant functional types and combined into seven biomes that represent the range of montane ecosystems. A rate of change analysis at each site provided a scale of the change through time at each site. Results Mesic montane forest biomes were present throughout the 50,000 cal year BP. Cold and dry montane biomes expanded during and after the Last Glacial Maximum (LGM). Warm and wet forest biomes expanded from the early Holocene and more open biomes expanded in the Late Holocene. Regional differences were observed, such as the Eastern Arc Mountain sites recording relatively little change in comparison with isolated volcanic mountains. The rate of change analysis highlights periods with a high rate of change (45,000–35,000, 11,000–5000 and 5000–present) while 35,000–20,000 is relatively stable. Main Conclusions Equatorial East African Montane forests are driven by local to regional vegetation responses to past climate changes. The research highlights that both the pace and nature of interactions in ecological systems vary widely across these montane forests.

Detection of multi-year ex-fast ice in the Weddell Sea, Antarctica, using ICESat-2 satellite altimeter data - Younghyun Koo; Hongjie Xie; Walter N. Meier; Stephen F. Ackley; Nathan T. Kurtz (Remote Sensing of Environment, 2025)

Environmental history of northwestern Vancouver Island (British Columbia, Canada) during the Holocene: A high-resolution dinoflagellate cyst record from Kyuquot Sound - Pieter R. Gurdebeke; Vera Pospelova; Kenneth N. Mertens; Zhen Li; Bjarn Van Riet; Audrey Dallimore; Stephen Louwye (Marine Micropaleontology, 2025)

The influence of core self-evaluation, mindful awareness, & anger rumination on forgiveness - James J. Collard; Amanda N. Stephens (Cognitive Processing, 2025)

Spatiotemporal variation in the reproductive dynamics of female American lobsters, Homarus americanus, on the northeastern continental shelf of the United States - Stephen A. Arnott; Noelle A. Olsen; Linus O. Stoltz; N. David Bethoney (Fisheries Research, 2025)

Multi-omics reveal microbial succession and metabolomic adaptations to flood in a hypersaline coastal lagoon - Christopher Keneally; Daniel Chilton; Tyler N. Dornan; Stephen P. Kidd; Virginie Gaget; Adam Toomes; Charlotte Lassaline; Reuben Petrovski; Lisa Wood; Justin D. Brookes (Water Research, 2025)

The Response and Recovery of Carbon and Water Fluxes in Australian Ecosystems Exposed to Severe Drought - C. Stephens; B. Medlyn; L. Williams; J. Knauer; A. Inbar; E. Pendall; S. K. Arndt; J. Beringer; C. M. Ewenz; N. Hinko‐Najera; L. B. Hutley; P. Isaac; et al. (Global Change Biology, 2025)
Climate change‐driven increases in drought risk pose a critical threat to global carbon and water cycles. However, ecosystem‐scale responses remain poorly quantified, particularly for severe, multiyear drought events. We addressed this gap by examining ecosystem‐scale carbon and water flux sensitivity to the extreme 2018–19 drought in Australia using data from 14 eddy covariance flux sites. The ecosystems span grasslands and semi‐arid woodlands to tropical and temperate forests. The driest sites (classed as “grass” and “very dry”) experienced drastic productivity impacts, with a 65% decrease in Gross Primary Productivity (GPP) over 2 years relative to the pre‐drought average. However, fluxes in “dry,” “seasonally wet” and “wet” ecosystems showed remarkable resistance, with no overall change in GPP. All sites recovered rapidly; carbon fluxes in the first post‐drought year matched (and generally exceeded) those of a climatically similar pre‐drought year. Drought responses were strongly mediated by ecosystem‐specific strategies. The driest ecosystems showed direct coupling of productivity to water availability, while intermediate ecosystems (dry and seasonally wet) leveraged stored soil water to maintain evapotranspiration and productivity under drought. At these sites, water was conserved over wet periods (evapotranspiration rainfall). This mechanism mitigating periodic water stress under high rainfall variability likely contributed to the notable drought resistance of the dry and seasonally wet sites. The monthly water deficit index (MWDI) emerged as a robust predictor of productivity across space, highlighting that short‐term water availability deficits strongly influence overall ecosystem composition. Analysis of drought response mechanisms suggested rapid leaf loss under water stress, particularly at the driest sites. Our findings underscore the importance of accounting for sub‐surface water storage and diverse drought response strategies in vegetation models. We provide critical benchmarks for improving parameterization of plant‐water relations, aiding efforts to inform climate‐robust management strategies.

Correction to: Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

Factors influencing landslide occurrence in low-relief formerly glaciated landscapes: landslide inventory and susceptibility analysis in Minnesota, USA - Laura D. Triplett; Morena N. Hammer; Stephen B. DeLong; Karen B. Gran; Carrie E. Jennings; Zachary T. Engle; Julie K. Bartley; Dylan J. Blumentritt; Andy J. Breckenridge; Stephanie Day; Melissa A. Kohout; Phil H. Larson; et al. (Natural Hazards, 2025)
In landscapes recently impacted by continental glaciation, landslides may occur where topographic relief has been generated by the drainage of glacial lakes and ensuing post-glacial fluvial network development into unconsolidated glacially derived sediments and exhumed bedrock. To investigate linkages among environmental variables, post-glacial landscape development, and landslides, we created a landslide inventory of nearly 10,000 landslides in five regions of the formerly glaciated low-relief state of Minnesota, United States. Multivariate logistic regression indicates the importance of slope angle, lithology, and the development of stream valleys to landslide distribution. Areas underlain by fine-grained glaciolacustrine and nearshore deposits that are incised by streams are particularly prone to shallow (< 1–2 m depth) landslides. Landslides also occur in a wide range of glacial and fluvial deposits, and as rockfall in layered Paleozoic sedimentary rocks in central and southern Minnesota and Precambrian igneous and sedimentary rocks in northeastern Minnesota. Although no more than 1–2% of the studied regions are susceptible to landslides, they can pose risk to life and safety, damage infrastructure, and impact water quality. The combination of recently generated low-relief steep slopes, extensive unconsolidated sediments, and layered sedimentary bedrock make this formerly glaciated landscape more susceptible to landslides than current national-scale models indicate.

Diet of the Florida spotted skunk (Spilogale putorius ambarvalis) in a dry prairie ecosystem - Stephen N. Harris; Elizabeth A. Flaherty; Terry J. Doonan; Erin L. Hewett Ragheb; David S. Jachowski (Mammalian Biology, 2025)
The Florida spotted skunk ( Spilogale putorius ambarvalis ) is disjunct from other eastern spotted skunk ( S. putorius ) subspecies and has rarely been studied. Declines in eastern spotted skunk populations elsewhere underscore the importance of better understanding the Florida subspecies’ ecology and resource use, including its potential impacts as a nest predator of imperiled ground-nesting birds. The objective of our study was to gather baseline information on Florida spotted skunk diet in the dry prairie ecosystem of Central Florida. We conducted a stable isotope analysis using hair samples from 39 skunks and compared these with 106 samples from potential food items in dry prairie in 2016 and 2017 at Three Lakes Wildlife Management Area in Osceola County, Florida. Our resultant Bayesian mixing model indicated that the most prevalent food items in the Florida spotted skunk diet were millipedes (Diplopoda; ~ 42% of the diet) and a group consisting of amphibians and reptiles (~ 16%). Less prevalent were the groups including ground-nesting birds—one group containing granivorous or herbivorous species (~ 15%) and another containing insectivorous species (~ 13%). Our study provides evidence that Florida spotted skunks in the dry prairie ecosystem likely have a generalist diet, like spotted skunks outside of Florida, as no food item composed a majority (> 50%) of their diet. This study provides the first insights into the diet of free-ranging Florida spotted skunks and fills a key knowledge gap in the ecology of this important predator of the Florida dry prairie ecosystem.

Staying hooked: effective science engagement and communication in recreational fisheries - Pablo Pita; Sean Tracey; Robert Arlinghaus; Eneko Bachiller; Filipa Pinho-Duarte; Keno Ferter; Filipe Henriques; Samantha Hook; Kieran Hyder; Alejo Irigoyen; María P. Jiménez; Martín Laporta; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries. ● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions. ● Public involvement and stakeholder engagement are essential for effective management. ● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding. ● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks. ● Funding for communication efforts is often insufficient but remains crucial for success. ● Participatory workshops and data-sharing arrangements enhance collaboration and involvement. ● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Adrenergic receptor subtypes differentially influence acrolein-induced ventilatory, vascular leakage, and inflammatory responses - Devin I. Alewel; Stephen H. Gavett; Katherine M. Rentschler; Mette C. Schladweiler; Colette N. Miller; Paul A. Evansky; Thomas W. Jackson; Wanda C. Williams; Urmila P. Kodavanti (Toxicology and Applied Pharmacology, 2025)

Climate‐Induced Physiological Stress Drives Rainforest Mammal Population Declines - Alejandro de la Fuente; Natalie J. Briscoe; Michael R. Kearney; Stephen E. Williams; Kara N. Youngentob; Karen J. Marsh; Lucas A. Cernusak; Lily Leahy; Johan Larson; Andrew K. Krockenberger (Global Change Biology, 2025)
Climate change is a major driver of global biodiversity loss, yet the precise mechanisms linking climate change to population declines remain poorly understood. We developed a novel, broadly applicable framework that integrates biophysical, nutritional, and population modeling to capture fundamental physiological constraints on mammalian herbivores and applied it to investigate the causes of declines in ringtail possums of the Australian Wet Tropics ( Pseudochirops archeri and Hemibelideus lemuroides ). Our approach bridges the gap between mechanistic (“bottom‐up”) models, which simulate species' responses based solely on their traits and local microclimates, and the more common (“top‐down”) statistical models, which infer species' responses from occurrence or abundance data and standard environmental variables. We quantified population dynamics over a 30‐year period by generating species‐specific estimates of temperature and water stress, foraging limitations, and linking these with annual monitoring and nutritional quality within an open population model. Our findings demonstrate that climate change has impacted populations through physiological stress, but in a species‐specific manner. Both species have experienced population collapses at lower elevations and in low‐nutritional sites. For P. archeri , we found evidence that population changes were driven by reduced survival due to overheating and dehydration, alongside diminished recruitment from limited foraging. In contrast, our model suggests that H. lemuroides populations were primarily affected by foraging constraints, emphasizing the importance of considering climate‐driven limitations on foraging activity in addition to direct physiological stress. These mechanistic insights offer a foundation for targeted conservation strategies to mitigate the impacts of climate pressures on wild populations.

Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Effects of microbial alteration of oceanic crust on sulfur cycling in hydrothermal systems - Sarah N. Moriarty; Emma Bertran; James W. Dottin; James Farquhar; David T. Johnston; Stephen J. Piercey; Dennis Sánchez-Mora; Michael G. Babechuk; Jason B. Sylvan; John W. Jamieson (Geochimica et Cosmochimica Acta, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Design and Process Considerations for Preparation of Modified Release Ivermectin and Praziquantel Tablets by Wet Granulation - R. Gary Hollenbeck; Raafat Fahmy; Marilyn N. Martinez; Ahmed Ibrahim; Stephen W. Hoag (AAPS PharmSciTech, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The Breeding Bird Survey of the United Kingdom - Dario Massimino; Stephen R. Baillie; Dawn E. Balmer; Richard I. Bashford; Richard D. Gregory; Sarah J. Harris; James J. N. Heywood; Leah A. Kelly; David G. Noble; James W. Pearce‐Higgins; Michael J. Raven; Kate Risely; et al. (Global Ecology and Biogeography, 2025)
Motivation Information on species' population trends is essential to assess species' conservation status, make informed environmental decisions and ultimately reduce biodiversity loss. Robust population trends require a long‐term monitoring programme, often using citizen scientists, that ideally generates representative and unbiased data from the study area. Here we present the dataset of the Breeding Bird Survey, the main scheme for monitoring the population changes of common and widespread breeding birds in the United Kingdom, which achieves this through a randomised sampling scheme and defined field methodology. We also describe the modelling approach used to calculate the population trends, which are the main output of the survey. Main Types of Variable Contained The main published dataset contains 7,070,577 records detailing counts of 217 bird species in 7010 grid cells over 30 years. Data for 78 species that are currently regarded as too sensitive to be released at fine resolution are omitted. As an illustration of the main use of this dataset, we provide population change estimates for 119 bird species. Spatial Location and Grain Grid squares (1 × 1 km) are randomly selected using a stratified sampling scheme throughout the United Kingdom, Isle of Man and Channel Islands. Data in a grid square are collected along two 1‐km‐long transects which are subdivided into 200‐m‐long sections. Time Period and Grain Data have been collected every year since 1994, with two major disruptions in 2001 and 2020, when people's movements were nationally restricted. Grid squares are surveyed twice a year during the main breeding season (April to June). Here we present the data collected from 1994 to 2023. Major Taxa Studied and Level of Measurement Bird species. Software Format Data are supplied as comma‐separated text files.

Evaluating the role of binge planning and binge inevitability within affect regulation models of binge eating - Glen Forester; Lauren M. Schaefer; Jeffrey S. Johnson; Brianne N. Richson; Robert D. Dvorak; Ross D. Crosby; Carol B. Peterson; Stephen A. Wonderlich (Appetite, 2024)

A global blueberry phylogeny: Evolution, diversification, and biogeography of Vaccinieae (Ericaceae) - Anna L. Becker; Andrew A. Crowl; James L. Luteyn; Andre S. Chanderbali; Walter S. Judd; Paul S. Manos; Douglas E. Soltis; Stephen A. Smith; Deise J.P. Goncalves; Christopher W. Dick; William N. Weaver; Pamela S. Soltis; et al. (Molecular Phylogenetics and Evolution, 2024)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Relationships between abiotic factors, foliage chemistry and herbivory in a tropical montane ecosystem - Alejandro de la Fuente; Kara N. Youngentob; Karen J. Marsh; Andrew K. Krockenberger; Stephen E. Williams; Lucas A. Cernusak (Oecologia, 2024)
Herbivore–plant interactions are fundamental processes shaping ecosystems, yet their study is challenged by their complex connections within broader ecosystem processes, requiring a nuanced understanding of ecosystem dynamics. This study investigated the relationship between nutrient availability and insect herbivory in the Australian Wet Tropics. Our objectives were threefold. Firstly, to understand what factors influence nutrient availability for plants and herbivores across the landscape; secondly, to investigate how trees of different species respond to nutrient availability; and thirdly, to unravel how the relationships between resources and plant chemistry affect herbivory. We established a network of 25 study sites covering important abiotic gradients, including temperature, precipitation, and geology. Employing a hierarchical modelling approach, we assessed the influence of climate and geology on resource availability for plants, primarily in the form of soil nutrients. Then, we explored the influence of the above factors on the interaction between herbivory and foliage chemistry across three widespread rainforest tree species, comparing how these relationships emerged across genera. Our findings suggest an overarching influence of climate and geology over soil chemistry, foliar nitrogen, and insect herbivory, both directly and indirectly. However, individual constituents of soil fertility showed equivocal influences on spatial patterns of foliage chemistry once site geological origin was accounted for, suggesting a questionable relationship between individual soil nutrients and foliar composition. We have demonstrated that herbivore–plant interactions are complex dynamics regulated by an intricate web of relationships spanning different biogeochemical processes. While our results provide some support to the notion that herbivory is affected by resource availability, different species growing under the same conditions can show differing responses to the same resources, highlighting the importance of identifying specific limiting factors rather than simpler proxies of resource availability.

Acute inorganic nitrate ingestion does not impact oral microbial composition, cognitive function, or high-intensity exercise performance in female team-sport athletes - Rachel Tan; Courtney Merrill; Chandler F. Riley; Maya A. Hammer; Ryan T. Kenney; Alyssa A. Riley; Jeffrey Li; Alexandra C. Zink; Sean T. Karl; Katherine M. Price; Luka K. Sharabidze; Samantha N. Rowland; et al. (European Journal of Applied Physiology, 2024)
The purpose of this study was to investigate the effects of acute nitrate (NO 3 − )-rich beetroot juice ingestion on explosive and high-intensity exercise performance, oral microbiota composition, and cognitive flexibility (i.e., function), before and after maximal intermittent running exercise. Fifteen women team-sport athletes were assigned in a randomized, double-blind, crossover design to consume concentrated NO 3 – -depleted beetroot juice (PL; 0.1 mmol NO 3 − ) and NO 3 − -rich beetroot juice (BR; 12.0 mmol NO 3 − ) 2.5 h prior to performing a battery of exercise performance tasks and cognitive testing before and after the Yo–Yo intermittent recovery level 1 (YYIR1) running test. Resting plasma [NO 3 − ] and plasma nitrite ([NO 2 − ]) were elevated following BR ( P < 0.001). BR did not impact global composition or relative abundance of taxa in the oral microbiome ( P > 0.05) or cognitive flexibility before or after exercise ( P > 0.05). There was no significant difference in performance during 20-m (PRE, PL: 4.38 ± 0.27 vs. BR: 4.38 ± 0.32 s; POST, PL: 4.45 ± 0.29 vs. BR: 4.43 ± 0.35 s) and 10-m sprints (PRE, PL 2.78 ± 0.15 vs. BR 2.79 ± 0.18 s; POST, PL: 2.82 ± 0.16 vs. BR: 2.81 ± 0.19 s), isokinetic handgrip dynamometry, medicine ball throw, horizontal countermovement jump, or YYIR1 (PL: 355 ± 163 m vs. BR: 368 ± 184 m) between BR and PL ( P > 0.05). These findings indicate that acute dietary NO 3 − may not influence the oral microbiome, explosive and high-intensity exercise performance, or cognitive function in women team-sport athletes.

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

Habitat quality in farmland influences the activity patterns of giant Galapagos tortoises - Kyana N. Pike; Stephen Blake; Iain J. Gordon; Lin Schwarzkopf (Biodiversity and Conservation, 2024)
Many Galapagos giant tortoises make seasonal migrations from arid lowlands in the wet season, to humid highlands in the dry season. However, for critically endangered Western Santa Cruz giant tortoises ( Chelonoidis porteri ), at least 88% of the habitat in the highlands is now used for agriculture. To understand the impact of agricultural land use on tortoise behavior, we conducted 242 30-minute observations of tortoises on farms. We (1) recorded the time tortoises spent eating, walking, and resting in three different land-use types, (2) measured their temperature, and (3) quantified their selection of fine-scale vegetation characteristics. We found that tortoises rest for significantly longer periods when they are in abandoned land, compared to livestock, grazing, and touristic land. Generally, tortoises rested for longer when they were cooler. Time spent eating was increased by the density and proportion of ground vegetation, while time spent walking was reduced by tall vegetation. These findings suggest that the distribution of land-use types and the fine-scale composition of thermoregulatory and grazing resources within farmland have important implications for the behavior of tortoises while in human-modified land. Wildlife managers and landowners wishing to support tortoises on farms should focus on rehabilitating abandoned land and encouraging a heterogenous mix of sun and shade, and short ground vegetation across land-use types.

Climate, Host Abundance and Spread: Unravelling the Drivers of Forest Pest Distributions in North America - Andrew V. Gougherty; Ashley D. Walters; Anantha Prasad; Matthew P. Peters; Stephen N. Matthews; Ian DeMerchant (Journal of Biogeography, 2024)
Aim Forest pathogens, insect pests and parasitic plants are among the most important disturbance agents in forested ecosystems. Understanding where pests occur and where they might occur in the future will be important for understanding their impacts on host trees, and planning for future pest outbreaks. Location North America. Taxon Insect pests, pathogens and parasitic plants of forest trees. Methods Here, we develop and implement a framework to predict the contemporary distributions of 26 pest species that accounts for climate, host abundance and, for non‐native species, their spread on the landscape. Results We show that pest distributions can be predicted primarily by climatic variables. The abundance of individual host trees had only minor explanatory power, but the summed total of host abundance frequently had greater importance—suggesting forest composition and the relative frequency of hosts and non‐hosts place strong limits on pest distributions. Non‐native pests were strongly impacted by the distance from their original discovery location in North America, which tended to interact with climate variables—suggesting most non‐native pests are not yet at equilibrium with their potential climatic ranges in North America. Main Conclusions This work helps to clarify the generalised controls on pest distributions and provide a framework for predicting pest distributions in future climates.

Climate Change and the Emergence of No‐Analog Forest Assemblages in North America - Andrew V. Gougherty; Anantha M. Prasad; Matthew P. Peters; Stephen N. Matthews; Bryce T. Adams (Global Change Biology, 2024)
Future climate change is expected to result in tree species shifting their geographic distributions in ways that could reorganize species into assemblages with no contemporary analog. These projected no‐analog forests raise concern as their ecological function could similarly shift, which may challenge established conservation and management efforts. Here, we implement a community‐level modelling approach to identify the key climatic and topographic drivers of forest composition in North America, and then use these models to predict the distribution of “disappearing” and “novel” forest assemblages in future climate. We applied this modelling technique to both the taxonomic and phylogenetic composition of forest trees, to identify where species turnover may be greatest, and whether species are likely to be replaced with close relatives. Our work shows that approximately 11.9% of contemporary North American forests have low predicted similarity to future forests, and 26.2% of future forests could be compositionally novel compared with contemporary forests, but there was substantial geographic variability in the magnitude of these metrics across the continent. High‐elevation regions in the west tend to be nearest to their closest compositional analog, suggesting these regions may be most likely to realize the future predicted composition. This work provides a new approach to understanding how forest composition may shift in future climates in a way that avoids the need for individual species predictions and extends climate‐matching approaches with meaningful biological data.

Artificial Light Increases Nighttime Prevalence of Predatory Fishes, Altering Community Composition on Coral Reefs - Emma Weschke; Jules Schligler; Isla Hely; Thibaut Roost; Jo‐Ann Schies; Ben Williams; Bartosz Dworzanski; Suzanne C. Mills; Ricardo Beldade; Stephen D. Simpson; Andrew N. Radford (Global Change Biology, 2024)
Artificial light at night (ALAN) is an anthropogenic pollutant that is intensifying and expanding in marine environments, but experimental studies of community‐level effects are generally lacking. The inshore, shallow, and clear‐water locations of coral reefs and their diverse photosensitive inhabitants make these ecosystems highly susceptible to biological disturbances; at the same time, their biodiversity and accessibility make them model systems for wider insight. Here, we experimentally manipulated ALAN using underwater LED lights on a Polynesian reef system to investigate the influence on localised nighttime fish communities compared to control sites without ALAN. We collected infrared video censuses of baseline communities prior to manipulation, which we repeated following short‐term (mean of three nights) and prolonged (mean of 25 nights) exposures to ALAN. Short‐term ALAN exposure did not induce any significant alterations to the nighttime fish community, but prolonged ALAN exposure increased nighttime species richness. Species compositions exposed to prolonged ALAN were more dissimilar from their baseline compared to control sites. The difference between community compositions at prolonged ALAN exposure and control sites was not apparent at the family level; instead, it was observed from the composition of trait guilds. Following prolonged ALAN exposure, more diurnal and nocturnal predatory species (piscivores, invertivores, and planktivores)—particularly those that are site‐attached or mobile within reefs—were present in nighttime assemblages. Our experimental findings show that coastal ALAN could cause trophic imbalances and circadian disturbances in localised nighttime reef fish communities. Given that community‐wide consequences were only apparent after prolonged ALAN exposure suggests that management of the duration of artificial lighting could potentially be used to reduce impacts on marine ecosystems.

The Demographic Basis of Population Growth: A 32‐Year Transient Life Table Response Experiment - F. Stephen Dobson; David N. Koons; Claire Saraux; Anouch Tamian; Madan K. Oli; Vincent A. Viblanc (Ecology Letters, 2024)
It has recently been recognised that populations are rarely in demographic equilibrium, but rather in a ‘transient’ state. To examine how transient dynamics influence our empirical understanding of the links between changes in demographic rates and population growth, we conducted a 32‐year study of Columbian ground squirrels. The population increased rapidly for 10 years, followed by a 2‐year crash, and a gradual 19‐year recovery. Transient life table response experiment (LTRE) analysis showed that demographic stochasticity accounted for approximately one‐fourth of the variation in population growth, leaving the majority to be explained by environmental influences. These relatively small rodents appeared to have a slow pace of life. But unlike the general pattern for large mammals with slow life histories, ground squirrel survival did not exhibit low variation associated with environmental ‘buffering’; instead, survival varied substantially over time and contributed substantially (78%) to changes in abundance over the long‐term study, with minor contributions from reproduction and unstable stage structure.

Icing‐related injuries in polar bears ( Ursus maritimus ) at high latitudes - Kristin L. Laidre; Stephen N. Atkinson (Ecology, 2024)

Linking reservoir annual residence time to nitrogen deposition using paleolimnological techniques - Benjamin C. Webster; Matthew N. Waters; Stephen W. Golladay (Water Research, 2024)

Genetic parameters for Mycoplasma ovipneumoniae nasal DNA copy number provide progress to promote domestic and bighorn sheep coexistence on public lands - Carrie S. Wilson; J. Bret Taylor; Michelle R. Mousel; Stephen N. White; Lindsay M.W. Piel; Hailey Wilmer; Brenda M. Murdoch (Small Ruminant Research, 2024)

Effects of a large-scale bioretention installation on the species composition of an urban bird community as determined by passive acoustic monitoring - David Wituszynski; Donald Hayford; Angelika Poesel; Gautam Apte; Stephen N. Matthews; Jay Martin (Environmental Monitoring and Assessment, 2024)

Investigation of geochemically induced permeability alteration in geothermal reservoirs and its implications for sustainable geothermal energy production - Taylor Smith; Adedapo N. Awolayo; Stephen E. Grasby; Benjamin M. Tutolo (Applied Geochemistry, 2024)

Heterogeneous Mechanical Stress and Interstitial Fluid Flow Predictions Derived from DCE-MRI for Rat U251N Orthotopic Gliomas - Julian A. Rey; Katelynn G. Spanick; Glauber Cabral; Isabel N. Rivera-Santiago; Tavarekere N. Nagaraja; Stephen L. Brown; James R. Ewing; Malisa Sarntinoranont (Annals of Biomedical Engineering, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Long-term patterns and trends in water column biogeochemistry in a changing environment - Paul Julian; James W. Fourqurean; Stephen E. Davis; Donatto Surratt; Evelyn E. Gaiser; John S. Kominoski; Tiffany G. Troxler; Joseph N. Boyer; Serge Thomas; Henry O. Briceño; Christopher J. Madden; Enrique Montes; et al. (Estuarine, Coastal and Shelf Science, 2024)

Warming reduces trophic diversity in high‐latitude food webs - Michelle C. Jackson; Eoin J. O'Gorman; Bruno Gallo; Sarah F. Harpenslager; Kate Randall; Danielle N. Harris; Hannah Prentice; Mark Trimmer; Ian Sanders; Alex J. Dumbrell; Tom C. Cameron; Katrin Layer‐Dobra; et al. (Global Change Biology, 2024)
The physical effects of climate warming have been well documented, but the biological responses are far less well known, especially at the ecosystem level and at large (intercontinental) scales. Global warming over the next century is generally predicted to reduce food web complexity, but this is rarely tested empirically due to the dearth of studies isolating the effects of temperature on complex natural food webs. To overcome this obstacle, we used ‘natural experiments’ across 14 streams in Iceland and Russia, with natural warming of up to 20°C above the coldest stream in each high‐latitude region, where anthropogenic warming is predicted to be especially rapid. Using biomass‐weighted stable isotope data, we found that community isotopic divergence (a universal, taxon‐free measure of trophic diversity) was consistently lower in warmer streams. We also found a clear shift towards greater assimilation of autochthonous carbon, which was driven by increasing dominance of herbivores but without a concomitant increase in algal stocks. Overall, our results support the prediction that higher temperatures will simplify high‐latitude freshwater ecosystems and provide the first mechanistic glimpses of how warming alters energy transfer through food webs at intercontinental scales.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Coupled atmosphere-ocean response of the southwest Pacific to deglacial changes in Atlantic meridional overturning circulation - Shaun R. Eaves; Andrew N. Mackintosh; Joel B. Pedro; Helen C. Bostock; Matthew T. Ryan; Kevin P. Norton; Bruce W. Hayward; Brian M. Anderson; Feng He; Richard S. Jones; Andrew M. Lorrey; Rewi M. Newnham; et al. (Earth and Planetary Science Letters, 2024)

The Use of Systemically Absorbed Drugs to Explore An In Vitro Bioequivalence Approach For Comparing Non-Systemically Absorbed Active Pharmaceutical Ingredients in Drug Products For Use in Dogs - Marilyn N. Martinez; Raafat Fahmy; Linge Li; Kithsiri Herath; R. Gary Hollenbeck; Ahmed Ibrahim; Stephen W. Hoag; David Longstaff; Shasha Gao; Michael J. Myers (Pharmaceutical Research, 2024)
Purpose Currently, for veterinary oral formulations containing one or more active pharmaceutical ingredient (API) that are not systemically absorbed and act locally within the gastrointestinal (GI) tract, the use of terminal clinical endpoint bioequivalence (BE) studies is the only option for evaluating product BE. This investigation explored the use of a totality of evidence approach as an alternative to these terminal studies. Methods Three formulations of tablets containing ivermectin plus praziquantel were manufactured to exhibit distinctly different in vitro release characteristics. Because these APIs are highly permeable, plasma drug concentrations served as a biomarker of in vivo dissolution. Tablets were administered to 27 healthy Beagle dogs (3-way crossover) and the rate and extent of exposure of each API for each formulation was compared in a pairwise manner. These results were compared to product relative in vitro dissolution profiles in 3 media. In vivo and in vitro BE predictions were compared. Results In vivo/in vitro inconsistencies in product relative performance were observed with both compounds when considering product performance across the 3 dissolution media. Formulation comparisons flagged major differences that could explain this outcome. Conclusions The finding of an inconsistent in vivo/in vitro relationship confirmed that in vitro dissolution alone cannot assure product BE for veterinary locally acting GI products. However, when combined with a comparison of product composition and manufacturing method, this totality of evidence approach can successfully alert scientists to potential therapeutic inequivalence, thereby supporting FDA’s efforts to Replace, Reduce, and/or Refine terminal animal studies.

Endothelial dysfunction influences augmented aortic hemodynamic responses to metaboreflex activation in postmenopausal women - Mauricio A. Martinez; Katherine N. Dillon; Yejin Kang; Arun Maharaj; Stephen M. Fischer; Arturo Figueroa (European Journal of Applied Physiology, 2024)

Genomic insights into hybrid zone formation: The role of climate, landscape, and demography in the emergence of a novel hybrid lineage - Constance E. Bolte; Tommy Phannareth; Michelle Zavala‐Paez; Brianna N. Sutara; Muhammed F. Can; Matthew C. Fitzpatrick; Jason A. Holliday; Stephen R. Keller; Jill A. Hamilton (Molecular Ecology, 2024)
Population demographic changes, alongside landscape, geographic and climate heterogeneity, can influence the timing, stability and extent of introgression where species hybridise. Thus, quantifying interactions across diverged lineages, and the relative contributions of interspecific genetic exchange and selection to divergence at the genome‐wide level is needed to better understand the drivers of hybrid zone formation and maintenance. We used seven latitudinally arrayed transects to quantify the contributions of climate, geography and landscape features to broad patterns of genetic structure across the hybrid zone of Populus trichocarpa and P. balsamifera and evaluated the demographic context of hybridisation over time. We found genetic structure differed among the seven transects. While ancestry was structured by climate, landscape features influenced gene flow dynamics. Demographic models indicated a secondary contact event may have influenced contemporary hybrid zone formation with the origin of a putative hybrid lineage that inhabits regions with higher aridity than either of the ancestral groups. Phylogenetic relationships based on chloroplast genomes support the origin of this hybrid lineage inferred from demographic models based on the nuclear data. Our results point towards the importance of climate and landscape patterns in structuring the contact zones between P. trichocarpa and P. balsamifera and emphasise the value whole genome sequencing can have to advancing our understanding of how neutral processes influence divergence across space and time.

Skull of a new periptychid mammal from the lower Paleocene Denver Formation of Colorado (Corral Bluffs, El Paso County) - Lucas N. Weaver; Jordan W. Crowell; Stephen G. B. Chester; Tyler R. Lyson (Journal of Mammalian Evolution, 2024)
The Periptychidae, an extinct group of archaic ungulates (‘condylarths’), were the most speciose eutherian mammals in the earliest Paleocene of North America, epitomizing mammalian ascendency after the Cretaceous–Paleogene (K–Pg) mass extinction. Although periptychids are mostly known from fragmentary gnathic remains, the Corral Bluffs area within the Denver Basin, Colorado, has yielded numerous exceptionally well-preserved mammalian fossils, including periptychids, from the earliest Paleocene. Here we describe a partial cranium and articulated dentaries plus an additional unassociated dentary fragment of a small-bodied (~273–455 g) periptychid from ca. 610 thousand years after the K–Pg mass extinction (Puercan 2 North American Land Mammal ‘age’) at Corral Bluffs. Based on these new fossils we erect Militocodon lydae gen. et sp. nov. The dentition of M. lydae exhibits synapomorphies that diagnose the Conacodontinae, but it is plesiomorphic relative to Oxyacodon , resembling putatively basal periptychids like Mimatuta and Maiorana in several dental traits. As such, we interpret M. lydae as a basal conacodontine. Its skull anatomy does not reveal clear periptychid synapomorphies and instead resembles that of arctocyonids and other primitive eutherians. M. lydae falls along a dental morphocline from basal periptychids to derived conacodontines, which we hypothesize reflects a progressive, novel modification of the hypocone to enhance orthal shearing and crushing rather than grinding mastication. The discovery and thorough descriptions and comparisons of the partial M. lydae skull represent an important step toward unraveling the complex evolutionary history of periptychid mammals.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Assessing the space between science and practice in endangered species conservation - David S. Jachowski; Stephen N. Harris; Alex J. Jensen; Meghan P. Keating; Michael S. Muthersbaugh; Dana L. Nelson; Brianna R. Pruitt; Eduardo Rosales; Elizabeth A. Saldo; Keifer L. Titus (Biological Conservation, 2024)

Influence of acute dietary nitrate supplementation timing on nitrate metabolism, central and peripheral blood pressure and exercise tolerance in young men - Samantha N. Rowland; Lewis J. James; Emma O’Donnell; Stephen J. Bailey (European Journal of Applied Physiology, 2024)
Purpose Dietary nitrate (NO 3 − ) supplementation can lower systolic blood pressure (SBP) and improve exercise performance. Salivary flow rate (SFR) and pH are key determinants of oral NO 3 − reduction and purported to peak in the afternoon. We tested the hypotheses that NO 3 − -rich beetroot juice (BR) would increase plasma [nitrite] ([NO 2 − ]), lower SBP and improve exercise performance to a greater extent in the afternoon (AFT) compared to the morning (MORN) and evening (EVE). Method Twelve males completed six experimental visits in a repeated-measures, crossover design. NO 3 − -depleted beetroot juice (PL) or BR (~ 13 mmol NO 3 − ) were ingested in the MORN, AFT and EVE. SFR and pH, salivary and plasma [NO 3 − ] and [NO 2 − ], brachial SBP and central SBP were measured pre and post supplementation. A severe-intensity exercise tolerance test was completed to determine cycling time to exhaustion (TTE). Results There were no between-condition differences in mean SFR or salivary pH. The elevation in plasma [NO 2 − ] after BR ingestion was not different between BR-MORN, BR-AFT and BR-EVE. Brachial SBP was unchanged following BR supplementation in all conditions. Central SBP was reduced in BR-MORN (− 3 ± 4 mmHg), BR-AFT (− 4 ± 3 mmHg), and BR-EVE (− 2 ± 3 mmHg), with no differences between timepoints. TTE was not different between BR and PL at any timepoint. Conclusion Acute BR supplementation was ineffective at improving TTE and brachial SBP and similarly effective at increasing plasma [NO 2 − ] and lowering central SBP across the day, which may have implications for informing NO 3 − supplementation strategies.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Swimming and acoustic calling behavior attributed to Bryde’s whales in the central North Pacific - Tyler A. Helble; Gabriela C. Alongi; Regina A. Guazzo; Dylan R. Allhusen; Cameron R. Martin; Stephen W. Martin; Ian N. Durbach; E. Elizabeth Henderson (Frontiers in Marine Science, 2024)
A unique acoustic call type was identified and attributed to Bryde’s whales in the central North Pacific in 2015, but little is known about the distribution, calling behavior, or swimming behavior of Bryde’s whales in the region. Acoustic detections attributed to Bryde’s whales were used to localize and track individual whales on the U.S. Pacific Missile Range Facility (PMRF) in Kaua‘i, Hawai‘i. This study included 150 acoustically derived tracks from recordings spanning the years 2011–2022 with recording effort in nearly every month. Bryde’s whale movement was examined relative to calendar year, day of year, hour of day, wind speed, and acoustic calling rate. Hidden Markov models were used to identify two kinematic states (slower, less directional movement and faster, more directional movement). The findings indicate that Bryde’s whales were more likely to travel in a faster and more directional state during the daytime than at night and between May and August when compared to other times of year. The along-track acoustic cue rate was examined for 118 tracks, and the findings indicate a possible lengthening of the median inter-call interval over the duration of the study period. These results are an important first step in understanding more about behavior in Bryde’s whales, a relatively under-studied species.

Ketamine produces no detectable long-term positive or negative effects on cognitive flexibility or reinforcement learning of male rats - Anthony N. Nist; Stephen J. Walsh; Timothy A. Shahan (Psychopharmacology, 2024)

Playing both fig sides: the presence and host-switch of Pleistodontes imperialis (Hymenoptera: Agaonidae) is confirmed in Greece and Cyprus - Evangelos Koutsoukos; Jakovos Demetriou; Angeliki F. Martinou; Stephen G. Compton; Dimitrios N Avtzis; Jean-Yves Rasplus (Phytoparasitica, 2024)
Several Oriental and Australian species of Ficus have been introduced outside their native range and planted as ornamentals in urban habitats throughout the Mediterranean. This translocation of plant species has led to the introduction of host-specific insects such as their pollinating fig wasps (Hymenoptera: Agaonidae). Here, the Australian fig wasp Pleistodontes imperialis Saunders, 1882 is reported for the first time from Greece. Partial COI genes were sequenced for specimens sampled in Greece and Cyprus, and they appear to share identical haplotypes. Interestingly, this species-specific wasp not only develops in figs of its usual host, Ficus rubiginosa , but also in figs of Ficus watkinsiana , another Australian species introduced in Greece, which is pollinated by a second agaonid species ( Pleistodontes nigriventris Girault, 1915) in its native range. Although no negative economic or environmental impacts have been observed yet, monitoring of alien Ficus spp. in the region is encouraged to prevent their possible establishment in natural habitats.

Associations of plasma proteomics and age-related outcomes with brain age in a diverse cohort - Ramon Casanova; Keenan A. Walker; Jamie N. Justice; Andrea Anderson; Michael R. Duggan; Jenifer Cordon; Ryan T. Barnard; Lingyi Lu; Fang-Chi Hsu; Sanaz Sedaghat; Anna Prizment; Stephen B. Kritchevsky; et al. (GeroScience, 2024)
Machine learning models are increasingly being used to estimate “brain age” from neuroimaging data. The gap between chronological age and the estimated brain age gap (BAG) is potentially a measure of accelerated and resilient brain aging. Brain age calculated in this fashion has been shown to be associated with mortality, measures of physical function, health, and disease. Here, we estimate the BAG using a voxel-based elastic net regression approach, and then, we investigate its associations with mortality, cognitive status, and measures of health and disease in participants from Atherosclerosis Risk in Communities (ARIC) study who had a brain MRI at visit 5 of the study. Finally, we used the SOMAscan assay containing 4877 proteins to examine the proteomic associations with the MRI-defined BAG. Among N = 1849 participants (age, 76.4 (SD 5.6)), we found that increased values of BAG were strongly associated with increased mortality and increased severity of the cognitive status. Strong associations with mortality persisted when the analyses were performed in cognitively normal participants. In addition, it was strongly associated with BMI, diabetes, measures of physical function, hypertension, prevalent heart disease, and stroke. Finally, we found 33 proteins associated with BAG after a correction for multiple comparisons. The top proteins with positive associations to brain age were growth/differentiation factor 15 (GDF-15), Sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SEVP 1), matrilysin (MMP7), ADAMTS-like protein 2 (ADAMTS), and heat shock 70 kDa protein 1B (HSPA1B) while EGF-receptor (EGFR), mast/stem-cell-growth-factor-receptor (KIT), coagulation-factor-VII, and cGMP-dependent-protein-kinase-1 (PRKG1) were negatively associated to brain age. Several of these proteins were previously associated with dementia in ARIC. These results suggest that circulating proteins implicated in biological aging, cellular senescence, angiogenesis, and coagulation are associated with a neuroimaging measure of brain aging.

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Potential of stable isotope analysis to deduce anaerobic biodegradation of ethyl tert-butyl ether (ETBE) and tert-butyl alcohol (TBA) in groundwater: a review - Marcelle J. van der Waals; Steven F. Thornton; Stephen A. Rolfe; Luc Rock; Jonathan W. N. Smith; Tom N.P. Bosma; Jan Gerritse (Environmental Science and Pollution Research, 2024)
Understanding anaerobic biodegradation of ether oxygenates beyond MTBE in groundwater is important, given that it is replaced by ETBE as a gasoline additive in several regions. The lack of studies demonstrating anaerobic biodegradation of ETBE, and its product TBA, reflects the relative resistance of ethers and alcohols with a tertiary carbon atom to enzymatic attack under anoxic conditions. Anaerobic ETBE- or TBA-degrading microorganisms have not been characterized. Only one field study suggested anaerobic ETBE biodegradation. Anaerobic (co)metabolism of ETBE or TBA was reported in anoxic microcosms, indicating their biodegradation potential in anoxic groundwater systems. Non-isotopic methods, such as the detection of contaminant loss, metabolites, or ETBE- and TBA-degrading bacteria are not sufficiently sensitive to track anaerobic biodegradation in situ . Compound- and position-specific stable isotope analysis provides a means to study MTBE biodegradation, but isotopic fractionation of ETBE has only been studied with a few aerobic bacteria (εC −0.7 to −1.7‰, εH −11 to −73‰) and at one anoxic field site (δ 2 H-ETBE +14‰). Similarly, stable carbon isotope enrichment (δ 13 C-TBA +6.5‰) indicated TBA biodegradation at an anoxic field site. CSIA and PSIA are promising methods to detect anaerobic ETBE and TBA biodegradation but need to be investigated further to assess their full potential at field scale. Graphical abstract

Enviromic prediction enables the characterization and mapping of Eucalyptus globulus Labill breeding zones - Andrew N. Callister; Germano Costa-Neto; Ben P. Bradshaw; Stephen Elms; Jose Crossa; Jeremy T. Brawner (Tree Genetics & Genomes, 2024)
Genotype-environment interaction is pervasive in forest genetics. Delineation of spatial breeding zones (BZs) is fundamental for accommodating genotype-environment interaction. Here we developed a BZ classification pipeline for the forest tree Eucalyptus globulus in 2 Australian regions based on phenotypic, genomic, and pedigree data, as well on a detailed environmental characterization (“envirotyping”) and spatial mapping of BZs. First, the factor analytic method was used to model additive genetic variance and site–site genetic correlations ( r B ) in stem volume across 48 trials of 126,467 full-sib progeny from 2 separate breeding programs. Thirty-three trials were envirotyped using 145 environmental variables (EVs), involving soil and landscape (71), climate (73), and management (1) EVs. Next, sparse partial least squares-discriminant analysis was used to identify EVs that were required to predict classification of sites into 5 non-exclusive BZ classes based on r B . Finally, these BZs were spatially mapped across the West Australian and “Green Triangle” commercial estates by enviromic prediction using EVs for 80 locations and 15 sets of observed climate data to represent temporal variation. The factor analytic model explained 85.9% of estimated additive variance. Our environmental classification system produced within-zone mean r B between 0.76 and 0.84, which improves upon the existing values of 0.62 for Western Australia and 0.67 for Green Triangle as regional BZs. The delineation of 5 BZ classes provides a powerful framework for increasing genetic gain by matching genotypes to current and predicted future environments.

Description, life cycle, and phylogenetics of Proterometra wigglewomble n. sp. (Digenea: Azygiidae) from the Cahaba River, Alabama, U.S.A. - Triet N. Truong; Nathan V. Whelan; Paul D. Johnson; Michael L. Buntin; Stephen A. Bullard (Systematic Parasitology, 2024)

Trace element chemistry and strontium isotope ratios of atmospheric particulate matter reveal air quality impacts from mineral dust, urban pollution, and fireworks in the Wasatch Front, Utah, USA - Micah J. Marcy; Gregory T. Carling; Alyssa N. Thompson; Barry R. Bickmore; Stephen T. Nelson; Kevin A. Rey; Diego P. Fernandez; Matthew Heiner; Bradley R. Adams (Applied Geochemistry, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Network Analysis Reveals Species-Specific Organization of Microbial Communities in Four Co-Occurring Elasmobranch Species along the Georgia Coast - Kady Lyons; Christine N. Bedore; Aaron B. Carlisle; Lauren Moniz; Timothy L. Odom; Rokeya Ahmed; Stephen E. Greiman; Ryan M. Freedman (Fishes, 2024)
Comparing co-occurring species may provide insights into how aspects of ecology may play a role in influencing their microbial communities. During the 2019 commercial shrimp trawl season off coastal Georgia, swabs of skin, gills, cloaca, and gut were taken for three species of batoids (Butterfly Ray, Bluntnose Stingray, and Atlantic Stingray) and one shark species (Atlantic Sharpnose) for high-throughput sequencing of the V4 region of the bacterial 16S rRNA gene. White muscle was analyzed for stable isotopes (δ13C and δ15N) to evaluate potential niche overlap in these four sympatric mesopredators. Significant differences were found in both δ13C and δ15N signatures across species, suggesting a degree of resource partitioning. When examined within tissue type, the host species had a weak effect on β-diversity for cloaca and skin, with no differences found for gill and gut samples. However, network analysis metrics demonstrated a stronger species-specific effect and distinct microbial community relationships were apparent between the shark and batoids, with the former having tighter networks for both internally- and externally-influenced tissues (gut/cloaca and skin/gills, respectively). Despite overlapping habitat use, species’ microbiomes differed in their organizational structuring that paralleled differences in stable isotope results, suggesting a mediating role of species-specific ecology on bacterial microbiomes.

Degradation kinetics of veterinary antibiotics and estrogenic hormones in a claypan soil - Adam H. Moody; Robert N. Lerch; Keith W. Goyne; Stephen H. Anderson; David G. Mendoza-Cózatl; David A. Alvarez (Chemosphere, 2024)

Microbes, the ‘silent third partners’ of bee–angiosperm mutualisms - Shawn A. Steffan; Prarthana S. Dharampal; Jordan G. Kueneman; Alexander Keller; Magda P. Argueta-Guzmán; Quinn S. McFrederick; Stephen L. Buchmann; Rachel L. Vannette; Anna F. Edlund; Celeste C. Mezera; Nolan Amon; Bryan N. Danforth (Trends in Ecology & Evolution, 2024)

Yes, size does matter (for cycling safety)! Comparing behavioral and safety outcomes in S, M, L, and XL cities from 18 countries - Sergio A. Useche; Francisco Alonso; Aleksey Boyko; Polina Buyvol; Isaac D. Castañeda; Boris Cendales; Arturo Cervantes; Tomas Echiburu; Mireia Faus; Javier Gene-Morales; Jozef Gnap; Victor Gonzalez; et al. (Journal of Transport Geography, 2024)

Snag dynamics and surface fuel loads in the Sierra Nevada: Predicting the impact of the 2012–2016 drought - Hudson Northrop; Jodi N. Axelson; Adrian J. Das; Nathan L. Stephenson; Emilio Vilanova; Scott L. Stephens; John J. Battles (Forest Ecology and Management, 2024)

In vitro regeneration of immature zygotic embryos of Melia Volkensii Gürke for accelerated breeding - Priscilla N. Kimani; Lydia N. Wamalwa; Kahiu Ngugi; Stephen F. Omondi; Joseph M. Machua; Titus Magomere; Jackson Mulatya; Stefaan P. O. Werbrouck (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Biogeographic influences on the evolution and historical dispersal of the Australo‐Pacific Dacini fruit flies (Tephritidae: Dacinae) - Melissa L. Starkie; Stephen L. Cameron; Matt N. Krosch; Andrew D. Sweet; Anthony R. Clarke (Zoologica Scripta, 2024)
Fruit flies (Tephritidae: Dacini) are a frugivorous insect group that exhibit high endemic diversity in the rainforests of Australia and the western Pacific. In this region, biogeography has been influenced by tectonic plate movements and cycles of isolation and re‐connection of landmasses and rainforest habitats during glacial periods. However, how such factors have influenced the speciation and historical dispersal of the regional Dacini is largely unknown. To address this, we use a dated phylogeny to reconstruct the biogeographical history of the tribe. We found the Dacini radiated eastward into the Pacific islands largely from sources in New Guinea. We also found evidence for historical dispersal from both Australia and New Guinea into New Caledonia, a pathway unique to this island compared with neighbouring islands. There was also evidence for multiple, bidirectional dispersal events between Papua New Guinea and Australia, likely facilitated by the cyclically exposed Torres Strait land bridge. Cape York in far northern Australia was likely the only entry point for species dispersing into Australia; there was no evidence for entry of flies into Australia directly from West Papua or Wallacea. Several lineages radiated after entering Australia, such as members of the Bactrocera dorsalis species group. Within Australia, speciation was not associated with the biogeographic barriers known to have impacted other rainforest fauna in eastern Australia. Overall, we demonstrate that isolation between islands and large landmasses is important in the evolution of the Australo‐Pacific Dacini, but the reason for their extensive radiation within Australia and Papua New Guinea remains unclear.

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Genome-scale phylogeny and comparative genomics of the fungal order Sordariales - Noah Hensen; Lucas Bonometti; Ivar Westerberg; Ioana Onut Brännström; Sonia Guillou; Sandrine Cros-Aarteil; Sara Calhoun; Sajeet Haridas; Alan Kuo; Stephen Mondo; Jasmyn Pangilinan; Robert Riley; et al. (Molecular Phylogenetics and Evolution, 2023)

The “Golden Zone” temperature distribution of oil and gas occurrence examined using a global empirical database - Paul H. Nadeau; Shaoqing Sun; Stephen N. Ehrenberg (Marine and Petroleum Geology, 2023)

Home range, movement, and activity patterns of the Florida spotted skunk (Spilogale putorius ambarvalis) in prairie habitat - Stephen N. Harris; Terry J. Doonan; Erin L. Hewett Ragheb; David S. Jachowski (Mammalian Biology, 2023)

A new species of Ellipsomyxa Køie, 2003 (Bivalvulida) infecting the gall bladder of Pangasius macronema Bleeker (Siluriformes: Pangasiidae) from the Mekong River Delta, Vietnam - Steven P. Ksepka; Triet N. Truong; Stephen A. Bullard (Systematic Parasitology, 2023)

Utilisation of probiotics for disease management in giant freshwater prawn ( Macrobrachium rosenbergii ): Administration methods, antagonistic effects and immune response - Mirja Kaizer Ahmmed; Shuva Bhowmik; Fatema Ahmmed; Stephen G. Giteru; Shikder Saiful Islam; Mayssa Hachem; Md. Ashraf Hussain; Osman N. Kanwugu; Dominic Agyei; Tom Defoirdt (Journal of Fish Diseases, 2023)
The giant freshwater prawn ( Macrobrachium rosenbergii ) is a high‐yielding prawn variety well‐received worldwide due to its ability to adapt to freshwater culture systems. Macrobrachium rosenbergii is an alternative to shrimp typically obtained from marine and brackish aquaculture systems. However, the use of intensive culture systems can lead to disease outbreaks, particularly in larval and post‐larval stages, caused by pathogenic agents such as viruses, bacteria, fungi, yeasts and protozoans. White tail disease (viral), white spot syndrome (viral) and bacterial necrosis are examples of economically significant diseases. Given the increasing antibiotic resistance of disease‐causing microorganisms, probiotics have emerged as promising alternatives for disease control. Probiotics are live active microbes that are introduced into a target host in an adequate number or dose to promote its health. In the present paper, we first discuss the diseases that occur in M. rosenbergii production, followed by an in‐depth discussion on probiotics. We elaborate on the common methods of probiotics administration and explain the beneficial health effects of probiotics as immunity enhancers. Moreover, we discuss the antagonistic effects of probiotics on pathogenic microorganisms. Altogether, this paper provides a comprehensive overview of disease control in M. rosenbergii aquaculture through the use of probiotics, which could enhance the sustainability of prawn culture.

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

Unveiling the molecular identity of the diminutive cyprinid, Horadandia brittani (Teleostei: Cyprinidae), a species endemic to Southern India - N. Daniel; Hemam Nanaobi; J. Praveenraj; V. Balaji; J. Stephen Sampath Kumar (Molecular Biology Reports, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

Development and Validation of a Stability-indicating UPLC-DAD Method for the Simultaneous Determination of Ivermectin and Praziquantel in Pharmaceutical Tablets and Dissolution Media - Ahmed Ibrahim; Fang Wang; R. Gary Hollenbeck; Marilyn N. Martinez; Raafat Fahmy; Stephen W. Hoag (AAPS PharmSciTech, 2023)

Involvement of phospholipase A2 in the neuromuscular blockade caused by coralsnake (Micrurus spp.) venoms in mouse phrenic nerve-diaphragm preparations in vitro - Fernanda Y.G.M. Couceiro; Poliana J. Demico; Samuel R. Dias; Isabele N. Oliveira; Francis L. Pacagnelli; Elisangela O. Silva; Sávio S. Sant’Anna; Kathleen F. Grego; Karen Morais-Zani; Kristian A. Torres-Bonilla; Stephen Hyslop; Rafael S. Floriano (Toxicon, 2023)

Deep and ultra-deep basin brittle deformation with focus on China - Stephen E. Laubach; Lianbo Zeng; John N. Hooker; Qiqi Wang; RongHu Zhang; Junpeng Wang; Bo Ren (Journal of Structural Geology, 2023)

Den site selection by eastern spotted skunks (Spilogale putorius) in the Blue Ridge Mountains, North Carolina - Anna C. Siegfried; Stephen N. Harris; Colleen Olfenbuttel; David S. Jachowski (Mammal Research, 2023)

Legacy and current-use pesticides in Western Canadian mountain air: Influence of pesticide sales, source proximity, and altitude - Yang Ding; Stephen J. Hayward; John N. Westgate; Trevor N. Brown; Ying D. Lei; Frank Wania (Atmospheric Environment, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Effect of planning policies on land use dynamics and livelihood opportunities under global environmental change: Evidence from the Mekong Delta - Tristan Berchoux; Craig W. Hutton; Oliver Hensengerth; Hal E. Voepel; Van P.D. Tri; Pham T. Vu; Nghia N. Hung; Dan Parsons; Stephen E. Darby (Land Use Policy, 2023)

Editorial: Vulnerability and resilience of marine ecosystems affected by the Deepwater Horizon oil spill - Donald F. Boesch; Just Cebrian; Vanessa F. Fonseca; Stephen C. Landers; N. Justin Marshall (Frontiers in Marine Science, 2023)

Using records of well completions to assess vulnerability of domestic wells in the Northeast U.S. to drought - Brigid Mulroe; Stephen B. Shaw; Charles N. Kroll (Climatic Change, 2023)

Millimetre‐scale pollen analysis of non‐varved lacustrine sediments from Onepoto maar palaeolake, Auckland, reveals distal vegetation responses and landscape recovery following the ~25.5‐ka Ōruanui supereruption, New Zealand - Stephen B. Piva; Simon J. Barker; Rewi M. Newnham; Andrew B. H. Rees; Colin J. N. Wilson; Lionel Carter; Nels A. Iverson; Benjamin Läuchli; Paul C. Augustinus (Journal of Quaternary Science, 2023)
The ~25.5‐ka Ōruanui supereruption (Taupō volcano, New Zealand) erupted >1100 km 3 of pyroclastic material during the Last Glacial Maximum. The impacts of this event on climate and the New Zealand environment remain unresolved, particularly on ecological timescales. Using sediment cores from Onepoto maar palaeolake, Auckland (~240 km upwind from source), we have analysed pollen assemblages at contiguous 1‐mm intervals, around an intact 3‐cm layer of the Kawakawa‐Ōruanui Tephra to resolve and assess post‐eruption vegetation impacts and landscape recovery. Sediments immediately above the tephra record a decline in the relative abundance of the dominant canopy species of Fuscospora , and concurrent increase in the abundances of grasses, herbs, ferns and shrubs. These changes reflect a brief (

Volcanic phosphorus supply boosted Mesozoic terrestrial biotas in northern China - Chao Ma; Yanjie Tang; Ross N. Mitchell; Yongfei Li; Shouliang Sun; Jichang Zhu; Stephen F. Foley; Min Wang; Chenyang Ye; Jifeng Ying; Rixiang Zhu (Science Bulletin, 2023)

Transcriptomic Profiling Reveals Discrete Poststroke Dementia Neuronal and Gliovascular Signatures - Rachel Waller; Yoshiki Hase; Julie E. Simpson; Paul R. Heath; Matthew Wyles; Rajesh N. Kalaria; Stephen B. Wharton (Translational Stroke Research, 2023)
Poststroke dementia (PSD) is associated with pathology in frontal brain regions, in particular dorsolateral prefrontal cortex (DLPFC) neurons and white matter, remote from the infarct. We hypothesised that PSD results from progressive DLPFC neuronal damage, associated with frontal white matter gliovascular unit (GVU) alterations. We investigated the transcriptomic profile of the neurons and white matter GVU cells previously implicated in pathology. Laser-capture microdissected neurons, astrocytes and endothelial cells were obtained from the Cognitive Function After Stroke cohort of control, PSD and poststroke non-dementia (PSND) human subjects. Gene expression was assessed using microarrays and pathway analysis to compare changes in PSD with controls and PSND. Neuronal findings were validated using NanoString technology and compared with those in the bilateral common carotid artery stenosis (BCAS) mouse model. Comparing changes in PSD compared to controls with changes in PSND compared to controls identified transcriptomic changes associated specifically with dementia. DLPFC neurons showed defects in energy production (tricarboxylic acid (TCA) cycle, adenosine triphosphate (ATP) binding and mitochondria), signalling and communication (MAPK signalling, Toll-like receptor signalling, endocytosis). Similar changes were identified in neurons isolated from BCAS mice. Neuronal findings accompanied by altered astrocyte communication and endothelium immune changes in the frontal white matter, suggesting GVU dysfunction. We propose a pathogenic model in PSD whereby neuronal changes are associated with frontal white matter GVU dysfunction leading to astrocyte failure in supporting neuronal circuits resulting in delayed cognitive decline associated with PSD. Therefore, targeting these processes could potentially ameliorate the dementia seen in PSD.

Valorization of waste materials from seaweed industry: An industry survey based biorefinery approach - Jin‐Ho Yun; Stephen D. Archer; Nichole N. Price (Reviews in Aquaculture, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

Minke whales change their swimming behavior with respect to their calling behavior, nearby conspecifics, and the environment in the central North Pacific - Tyler A. Helble; Regina A. Guazzo; Ian N. Durbach; Cameron R. Martin; Gabriela C. Alongi; Stephen W. Martin; E. Elizabeth Henderson (Frontiers in Marine Science, 2023)
Behavioral responses to sonar have been observed in a number of baleen whales, including minke whales ( Balaenoptera acutorostrata ). Previous studies used acoustic minke whale boing detections to localize and track individual whales on the U.S. Pacific Missile Range Facility (PMRF) in Kaua ‘i, Hawai‘i before, during, and after Navy training activities. These analyses showed significant changes in central North Pacific minke whale distribution and swimming behavior during Navy sonar events. For the purposes of contextualizing changes in animal movement relative to Navy sonar, we expanded on this research to examine the natural variation in minke whale movement when Navy sonar was not present. This study included 2,245 acoustically derived minke whale tracks spanning the years 2012–2017 over all months that minke whales were detected (October–May). Minke whale movement was examined relative to calling season, day of the year, hour of day, wind speed, calling state (nominal or rapid), and distance to the nearest calling conspecific. Hidden Markov models were used to identify two kinematic states (slower, less directional movement and faster, more directional movement). The findings indicate that minke whales were more likely to travel in a faster and more directional state when they were calling rapidly, when other vocalizing minke whales were nearby, during certain times of the day and calling seasons, and in windier conditions, but these changes in movement were less intense than the changes observed during exposure to Navy sonar, when swim speeds were the fastest. These results start to put behavioral responses to Navy sonar into an environmental context to understand the severity of responses relative to natural changes in behavior.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Marine invertebrates and noise - Marta Solé; Kenzo Kaifu; T. Aran Mooney; Sophie L. Nedelec; Frédéric Olivier; Andrew N. Radford; Mirella Vazzana; Matthew A. Wale; Jayson M. Semmens; Stephen D. Simpson; Giuseppa Buscaino; Anthony Hawkins; et al. (Frontiers in Marine Science, 2023)
Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs. Recent studies have revealed that a wide diversity of invertebrates are also sensitive to sounds, especially via sensory organs whose original function is to allow maintaining equilibrium in the water column and to sense gravity. Marine invertebrates not only represent the largest proportion of marine biomass and are indicators of ocean health but many species also have important socio-economic values. This review presents the current scientific knowledge on invertebrate bioacoustics (sound production, reception, sensitivity), as well as on how marine invertebrates are affected by anthropogenic noises. It also critically revisits the literature to identify gaps that will frame future research investigating the tolerance to noise of marine ecosystems.

Farmers' attitudes towards agricultural plastics – Management and disposal, awareness and perceptions of the environmental impacts - Clodagh D. King; Caroline Gilleran Stephens; Joseph P. Lynch; Siobhán N. Jordan (Science of The Total Environment, 2023)

Environmental and bioclimatic factors influencing yeasts and molds distribution along European shores - M. Cogliati; S. Arikan-Akdagli; A. Barac; A.C. Bostanaru; S. Brito; N. Çerikçioğlu; M.A. Efstratiou; Ç. Ergin; M.C. Esposto; M. Frenkel; J.P. Gangneux; A. Gitto; et al. (Science of The Total Environment, 2023)

Spatial modeling of Sarus Crane nest site suitability in Cambodia to help target conservation of breeding areas - Robert N. van Zalinge; Jeb Barzen; Stephen T. Garnett (Forest Ecology and Management, 2023)

Is an MRI-derived anatomical measure of dementia risk also a measure of brain aging? - Ramon Casanova; Andrea M. Anderson; Ryan T. Barnard; Jamie N. Justice; Anna Kucharska-Newton; Beverly Gwen Windham; Priya Palta; Rebecca F. Gottesman; Thomas H. Mosley; Timothy M. Hughes; Lynne E. Wagenknecht; Stephen B. Kritchevsky (GeroScience, 2023)

Fog trends in India: Relationships to fog type and western disturbances - Daniel K. E. Smith; Stephen R. Dorling; Ian A. Renfrew; Andrew N. Ross; Craig Poku (International Journal of Climatology, 2023)
Fog is a major hazard in wintertime over India, particularly in the Indo‐Gangetic Plains, leading to significant impacts for transport and human health. Using 3‐hourly surface observations, from 69 sites across India, all fog and dense fog events between 2000 and 2020 are identified. For each event, the main fog formation mechanism is objectively categorized using a classification algorithm, distinguishing between radiation, advection, evaporation, precipitation or cloud‐base lowering fog types. In contrast to the findings of other international studies, radiation fog dominates as the most common fog type at the vast majority of locations in India, accounting for 68.1% of all fog events and 70.0% of dense fog events. Statistically significant positive trends are seen in the frequency of all fog events at Delhi, Lucknow and Patna, in the Indo‐Gangetic plains, between 1997/1998 and 2018/2019, dominated by comparable statistically significant positive trends in radiation fogs. Western disturbances (WD) are often linked to the formation of fog in India. Using a climatology of WDs, we show that 46.9% of radiation fog onsets in Delhi in December and January, the primary fog months, happened in conjunction with an active WD event. Conversely, only 32.3% of WDs during these same months coincided with the onset of a radiation fog event. WD‐related radiation fog events are shown to cluster into three distinct groups, with WD centres located to the northwest (51.4% of cases), southwest (13.3%) and east (35.2%) of Delhi. Each cluster is shown to have coherent and distinct near‐surface characteristics which are conducive to fog formation. Trends in WD frequency cannot fully account for the observed trends in fog events. We argue that the fog trends are more likely the result of a complex interaction between urban expansion and the associated rapid change in aerosol loading, resulting in impacts on radiation balance, microphysics and heat‐island processes.

Examining current best-practices for the use of wild post-larvae capture, culture, and release for fisheries enhancement - Laura E. Richardson; Philippe Lenfant; Leo J. Clarke; Amelie Fontcuberta; Anaïs Gudefin; Gilles Lecaillon; Lewis Le Vay; Andrew N. Radford; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Demand for marine fisheries is rising despite global impacts on the productive capacity of wild fish stocks due to overfishing, habitat loss, and global warming. Fisheries enhancement programs—aimed at augmenting stocks by releasing juveniles into the wild—are expected to play an increasingly important auxiliary role in addressing capture-based fishery limitations into the future. However, concerns exist over the impacts and efficacy of aquaculture-based enhancement (ABE), releasing captive-bred fish into wild populations. An alternative but understudied approach for fisheries enhancement is wild post-larvae capture, culture, and release (PCCR). Here, we provide an overview of the PCCR process, from initial planning to measuring success, providing an overview of its implementation in a viable finfish fishery, the white seabream Diplodus sargus in the Mediterranean. We discuss management application of PCCR-based enhancement and its limitations, highlighting existing knowledge gaps and future research required to realize the full potential of this alternative approach. Notwithstanding some limitations–including limited uptake for full evaluation, some species restrictions, density-dependent mortality, and the remaining open challenge for stock enhancement generally of tracking released fish through to reproduction–PCCR offers potential as a credible auxiliary management tool for fisheries restoration.

The role of eating expectancies and eating motives in the association between mood and loss-of-control eating: A national sample daily diary study - Emily K. Burr; Robert D. Dvorak; Ardhys N. De Leon; Angelina V. Leary; Roselyn Peterson; Lauren M. Schaefer; Stephen A. Wonderlich (Appetite, 2023)

Evaluation of the effects of abattoir effluent on the physicochemical and bacteriological quality of River Benue, Nigeria - Victor T. Omoni; Paul O. Bankole; Ojobo Omoche; Christopher Obida; Colonel Igben; Okekporo E. Stephen; Ekeoma I. Ogwo; Doosuur N. Torjir (Environmental Monitoring and Assessment, 2023)

Shedding light on taxonomic chaos: Diversity and distribution of South Asian skipper frogs (Anura, Dicroglossidae, Euphlyctis ) - Christophe Dufresnes; Stephen Mahony; Vishal Kumar Prasad; Rachunliu G. Kamei; Rafaqat Masroor; Muazzam Ali Khan; Awadh M. Al-Johany; Kumudani Bala Gautam; Sandeep Kumar Gupta; Leo J. Borkin; Daniel A. Melnikov; Juriy M. Rosanov; et al. (Systematics and Biodiversity, 2022)

Research priorities for measuring biologic age: summary and future directions from the Research Centers Collaborative Network Workshop - Tina E. Brinkley; Jamie N. Justice; Shubhashrita Basu; Scott R. Bauer; Kah Poh Loh; Peter Mukli; Ted Kheng Siang Ng; Indira C. Turney; Luigi Ferrucci; Steven R. Cummings; Stephen B. Kritchevsky (GeroScience, 2022)
Biologic aging reflects the genetic, molecular, and cellular changes underlying the development of morbidity and mortality with advancing chronological age. As several potential mechanisms have been identified, there is a growing interest in developing robust measures of biologic age that can better reflect the underlying biology of aging and predict age-related outcomes. To support this endeavor, the Research Centers Collaborative Network (RCCN) conducted a workshop in January 2022 to discuss emerging concepts in the field and identify opportunities to move the science forward. This paper presents workshop proceedings and summarizes the identified research needs, priorities, and recommendations for measuring biologic age. The highest priorities identified were the need for more robust measures, longitudinal studies, multidisciplinary collaborations, and translational approaches.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Forecasting the Potential Effects of Climate Change on Malaria in the Lake Victoria Basin Using Regionalized Climate Projections - Ednah N. Ototo; Joseph O. Ogutu; Andrew Githeko; Mohammed Y. Said; Lucy Kamau; Didacus Namanya; Stella Simiyu; Stephen Mutimba (Acta Parasitologica, 2022)
Background Malaria epidemics are increasing in East Africa since the 1980s, coincident with rising temperature and widening climate variability. A projected 1–3.5 °C rise in average global temperatures by 2100 could exacerbate the epidemics by modifying disease transmission thresholds. Future malaria scenarios for the Lake Victoria Basin (LVB) are quantified for projected climate scenarios spanning 2006–2100. Methods Regression relationships are established between historical (1995–2010) clinical malaria and anaemia cases and rainfall and temperature for four East African malaria hotspots. The vector autoregressive moving average processes model, VARMAX ( p,q,s ), is then used to forecast malaria and anaemia responses to rainfall and temperatures projected with an ensemble of eight General Circulation Models (GCMs) for climate change scenarios defined by three Representative Concentration Pathways (RCPs 2.6, 4.5 and 8.5). Results Maximum temperatures in the long rainy (March–May) and dry (June–September) seasons will likely increase by over 2.0 °C by 2070, relative to 1971–2000, under RCPs 4.5 and 8.5. Minimum temperatures (June–September) will likely increase by over 1.5–3.0 °C under RCPs 2.6, 4.5 and 8.5. The short rains (OND) will likely increase more than the long rains (MAM) by the 2050s and 2070s under RCPs 4.5 and 8.5. Historical malaria cases are positively and linearly related to the 3–6-month running means of monthly rainfall and maximum temperature. Marked variation characterizes the patterns projected for each of the three scenarios across the eight General Circulation Models, reaffirming the importance of using an ensemble of models for projections. Conclusions The short rains (OND), wet season (MAM) temperatures and clinical malaria cases will likely increase in the Lake Victoria Basin. Climate change adaptation and mitigation strategies, including malaria control interventions could reduce the projected epidemics and cases. Interventions should reduce emerging risks, human vulnerability and environmental suitability for malaria transmission.

Black Gill in Marine Decapod Crustaceans: A Review - Marc E. Frischer; Stephen C. Landers; Anna N. Walker; Shirley A. Powell; Richard F. Lee (Reviews in Fisheries Science & Aquaculture, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

The obesity-breast cancer link: a multidisciplinary perspective - Emily N. Devericks; Meredith S. Carson; Lauren E. McCullough; Michael F. Coleman; Stephen D. Hursting (Cancer and Metastasis Reviews, 2022)
Obesity, exceptionally prevalent in the USA, promotes the incidence and progression of numerous cancer types including breast cancer. Complex, interacting metabolic and immune dysregulation marks the development of both breast cancer and obesity. Obesity promotes chronic low-grade inflammation, particularly in white adipose tissue, which drives immune dysfunction marked by increased pro-inflammatory cytokine production, alternative macrophage activation, and reduced T cell function. Breast tissue is predominantly composed of white adipose, and developing breast cancer readily and directly interacts with cells and signals from adipose remodeled by obesity. This review discusses the biological mechanisms through which obesity promotes breast cancer, the role of obesity in breast cancer health disparities, and dietary interventions to mitigate the adverse effects of obesity on breast cancer. We detail the intersection of obesity and breast cancer, with an emphasis on the shared and unique patterns of immune dysregulation in these disease processes. We have highlighted key areas of breast cancer biology exacerbated by obesity, including incidence, progression, and therapeutic response. We posit that interception of obesity-driven breast cancer will require interventions that limit protumor signaling from obese adipose tissue and that consider genetic, structural, and social determinants of the obesity–breast cancer link. Finally, we detail the evidence for various dietary interventions to offset obesity effects in clinical and preclinical studies of breast cancer. In light of the strong associations between obesity and breast cancer and the rising rates of obesity in many parts of the world, the development of effective, safe, well-tolerated, and equitable interventions to limit the burden of obesity on breast cancer are urgently needed.

Seasonal differences in the morphology and spine density of hippocampal neurons in wild ground squirrels - B. Brinkman; A. Ngwenya; K. Fjordbotten; O. Stephen; A. N. Iwaniuk (Brain Structure and Function, 2022)

Microvascular anatomy suggests varying aerobic activity levels in the adipose tissues of diving tetrapods - Molly K. Gabler-Smith; Amy J. Berger; D. Mark Gay; Stephen T. Kinsey; Andrew J. Westgate; Heather N. Koopman (Journal of Comparative Physiology B, 2022)

Na+/HCO3− cotransporter 1 (nbce1) isoform gene expression during smoltification and seawater acclimation of Atlantic salmon - Jason P. Breves; Ian S. McKay; Victor Koltenyuk; Nastasia N. Nelson; Sean C. Lema; Stephen D. McCormick (Journal of Comparative Physiology B, 2022)

North Pacific minke whales call rapidly when calling conspecifics are nearby - Cameron R. Martin; Regina A. Guazzo; Tyler A. Helble; Gabriela C. Alongi; Ian N. Durbach; Stephen W. Martin; Brian M. Matsuyama; E. Elizabeth Henderson (Frontiers in Marine Science, 2022)
North Pacific minke whale ( Balaenoptera acutorostrata ) boing calls are commonly detected in Hawaiian waters. When producing boing vocalizations, minke whales seem to be in one of two calling behavioral states. Most often minke whales produce boings with inter-call intervals of several minutes, but sometimes minke whales call rapidly with inter-call intervals of less than a minute. Since minke whales are difficult to detect visually, cue-rate-based density estimation using passive acoustic monitoring has been proposed. However, the variables that influence cue rate or calling rate are poorly understood in most whales, including minke whales. We collected passive acoustic recordings from 47 bottom-mounted hydrophones at the Pacific Missile Range Facility’s instrumented range off the coast of Kauaʻi, Hawaiʻi to test the hypothesis that minke whales call more rapidly when closer in proximity to other calling conspecifics. A total of 599 days of data were recorded between August 2012 and July 2017 and were automatically post-processed to detect, classify, and localize calls. Localized calls were grouped into tracks and manually validated, resulting in 509 individual tracks composed of 36,033 calls within a 16 x 39 km focal study area. Tracked minke whales exhibited a strong bimodal call rate with means of one call every 6.85 min ( σ = 2.54 min) and 0.63 min ( σ = 0.36 min). We ran hidden Markov models to quantify the relationship between call rate and the distance to the nearest calling conspecific. Overall, the probability of the higher call rate occurring increased as the distance to the nearest conspecific decreased, and the probability of the lower call rate occurring increased as the distance to the nearest conspecific increased. We also examined individual track data and found that minke whales may also exhibit other responses (i.e. increased speed, changes in heading, and cessation of calling) when calling conspecifics are nearby. These findings provide new information about minke whale calling behavior in what is likely a breeding area.

Hydrogeology of an urban weathered basement aquifer in Kampala, Uganda - Philip M. Nyenje; Denis Ocoromac; Stephen Tumwesige; Matt J. Ascott; James P. R. Sorensen; Andrew J. Newell; David M. J. Macdonald; Daren C. Gooddy; Callist Tindimugaya; Robinah N. Kulabako; Dan J. Lapworth; Jan Willem Foppen (Hydrogeology Journal, 2022)
Weathered basement aquifers are vital sources of drinking water in Africa. In order to better understand their role in the urban water balance, in a weathered basement aquifer in Kampala, Uganda, this study installed a transect of monitoring piezometers, carried out spring flow and high-frequency groundwater level monitoring, slug tests and hydrochemical analyses, including stable isotopes and groundwater residence time indicators. Findings showed a typical weathered basement aquifer with a 20–50-m thickness. Groundwater recharge was 3–50 mm/year, occurring during sustained rainfall. Recharge to a deep groundwater system within the saprock was slow and prolonged, while recharge to the springs on the valley slopes was quick and episodic, responding rapidly to precipitation. Springs discharged shallow groundwater, mixed with wastewater infiltrating from onsite sanitation practices and contributions from the deeper aquifer and were characterised by low flow rates (< 0.001 m 3 /s), low pH (<5), high nitrate values (61–190 mg/L as NO 3 ), and residence times of <30 years. The deeper groundwater system occurred in the saprolite/saprock, had low transmissivity (< 1 × 10 −5 m 2 /s), lower nitrate values (<20 mg/L as NO 3 ), pH 6–6.5 and longer residence times (40–60 years). Confined groundwater conditions in the valleys were created by the presence of clay-rich alluvium and gave rise to artesian conditions where groundwater had lower nitrate concentrations. The findings provide new insights into weathered basement aquifers in the urban tropics and show that small-scale abstractions are more sustainable in the deeper groundwater system in the valleys, where confined conditions are present.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Measurement of pore volume, connectivity and clogging of pervious concrete reactive barrier used to treat acid mine drainage - Stephen O. Ekolu; Fitsum Solomon; Frikkie de Beer; Louisette Bitandi; Rais N. Kilula; Khaya T. Maseko; Fatty G. Mahlangu (Environmental Science and Pollution Research, 2022)

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Correction to: Inhibition of a cortico-thalamic circuit attenuates cue-induced reinstatement of drug-seeking behavior in “relapse prone” male rats - Brittany N. Kuhn; Paolo Campus; Marin S. Klumpner; Stephen E. Chang; Amanda G. Iglesias; Shelly B. Flagel (Psychopharmacology, 2022)

Cryptic extinction risk in a western Pacific lizard radiation - Peter J. McDonald; Rafe M. Brown; Fred Kraus; Philip Bowles; Umilaela Arifin; Samuel J. Eliades; Robert N. Fisher; Maren Gaulke; L. Lee Grismer; Ivan Ineich; Benjamin R. Karin; Camila G. Meneses; et al. (Biodiversity and Conservation, 2022)
Cryptic ecologies, the Wallacean Shortfall of undocumented species’ geographical ranges and the Linnaean Shortfall of undescribed diversity, are all major barriers to conservation assessment. When these factors overlap with drivers of extinction risk, such as insular distributions, the number of threatened species in a region or clade may be underestimated, a situation we term ‘cryptic extinction risk’. The genus Lepidodactylus is a diverse radiation of insular and arboreal geckos that occurs across the western Pacific. Previous work on Lepidodactylus showed evidence of evolutionary displacement around continental fringes, suggesting an inherent vulnerability to extinction from factors such as competition and predation. We sought to (1) comprehensively review status and threats, (2) estimate the number of undescribed species, and (3) estimate extinction risk in data deficient and candidate species, in Lepidodactylus . From our updated IUCN Red List assessment, 60% of the 58 recognized species are threatened (n = 15) or Data Deficient (n = 21), which is higher than reported for most other lizard groups. Species from the smaller and isolated Pacific islands are of greatest conservation concern, with most either threatened or Data Deficient, and all particularly vulnerable to invasive species. We estimated 32 undescribed candidate species and linear modelling predicted that an additional 18 species, among these and the data deficient species, are threatened with extinction. Focusing efforts to resolve the taxonomy and conservation status of key taxa, especially on small islands in the Pacific, is a high priority for conserving this remarkably diverse, yet poorly understood, lizard fauna. Our data highlight how cryptic ecologies and cryptic diversity combine and lead to significant underestimation of extinction risk.

Enhancing plant N uptake with biochar-based fertilizers: limitation of sorption and prospects - Daniel P. Rasse; Simon Weldon; Erik J. Joner; Stephen Joseph; Claudia I. Kammann; Xiaoyu Liu; Adam O’Toole; Genxing Pan; N. Pelin Kocatürk-Schumacher (Plant and Soil, 2022)
Background Biochar-based fertilizer products (BCF) have been reported to increase both crop yield and N-use efficiency. Such positive effects are often assumed to result from the slow-release of N adsorbed on BCF structures. However, a careful review of the literature suggests that actual mechanisms remain uncertain, which hampers the development of efficient BCF products. Scope Here, we aim at reviewing BCF mechanisms responsible for enhanced N uptake by plants, and evaluate the potential for further improvement. We review the capacity of biochar structures to adsorb and release N forms, the biochar properties supporting this effect, and the methods that have been proposed to enhance this effect. Conclusions Current biochar products show insufficient sorption capacity for the retention of N forms to support the production of slow-release BCFs of high enough N concentration. Substantial slow-release effects appear to require conventional coating technology. Sorption capacity can be improved through activation and additives, but currently not to the extent needed for concentrated BCFs. Positive effects of commercial BCFs containing small amount of biochar appear to result from pyrolysis-derived biostimulants. Our review highlights three prospects for improving N retention: 1) sorption of NH 3 gas on specifically activated biochar, 2) synergies between biochar and clay porosities, which might provide economical sorption enhancement, and 3) physical loading of solid N forms within biochar. Beyond proof of concept, quantitative nutrient studies are needed to ascertain that potential future BCFs deliver expected effects on both slow-release and N use efficiency.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nocturnal light-specific temporal partitioning facilitates coexistence for a small mesopredator, the eastern spotted skunk - Courtney J. Marneweck; Cameron R. Forehand; Charles D. Waggy; Stephen N. Harris; Todd E. Katzner; David S. Jachowski (Journal of Ethology, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

Inhibition of a cortico-thalamic circuit attenuates cue-induced reinstatement of drug-seeking behavior in “relapse prone” male rats - Brittany N. Kuhn; Paolo Campus; Marin S. Klumpner; Stephen E. Chang; Amanda G. Iglesias; Shelly B. Flagel (Psychopharmacology, 2022)

Evaluation of a blood-based geroscience biomarker index in a randomized trial of caloric restriction and exercise in older adults with heart failure with preserved ejection fraction - Jamie N. Justice; Nicholas M. Pajewski; Mark A. Espeland; Peter Brubaker; Denise K. Houston; Santica Marcovina; Barbara J. Nicklas; Stephen B. Kritchevsky; Dalane W. Kitzman (GeroScience, 2022)

Development and adaptation of relative sunshine hours models for the equatorial latitudes: a case study - Stephen N. Nnamchi; Mustafa M. Mundu; Kelechi J. Ukagwu; Ismail A. Oyagbola (Modeling Earth Systems and Environment, 2022)

Annotated expression and activity data for murine recombinase alleles and transgenes: the CrePortal resource - Michelle N. Perry; Constance M. Smith; Hiroaki Onda; Martin Ringwald; Stephen A. Murray; Cynthia L. Smith (Mammalian Genome, 2022)
Recombinase alleles and transgenes can be used to facilitate spatio-temporal specificity of gene disruption or transgene expression. However, the versatility of this in vivo recombination system relies on having detailed and accurate characterization of recombinase expression and activity to enable selection of the appropriate allele or transgene. The CrePortal ( http://www.informatics.jax.org/home/recombinase ) leverages the informatics infrastructure of Mouse Genome Informatics to integrate data from the scientific literature, direct data submissions from the scientific community at-large, and from major projects developing new recombinase lines and characterizing recombinase expression and specificity patterns. Searching the CrePortal by recombinase activity or specific recombinase gene driver provides users with a recombinase alleles and transgenes activity tissue summary and matrix comparison of gene expression and recombinase activity with links to generation details, a recombinase activity grid, and associated phenotype annotations. Future improvements will add cell type-based activity annotations. The CrePortal provides a comprehensive presentation of recombinase allele and transgene data to assist researchers in selection of the recombinase allele or transgene based on where and when recombination is desired.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Cerebello-cerebral Functional Connectivity Networks in Major Depressive Disorder: a CAN-BIND-1 Study Report - Sheeba Arnold Anteraper; Xavier Guell; Yoon Ji Lee; Jovicarole Raya; Ilya Demchenko; Nathan W. Churchill; Benicio N. Frey; Stefanie Hassel; Raymond W. Lam; Glenda M. MacQueen; Roumen Milev; Tom A. Schweizer; et al. (The Cerebellum, 2022)

An on-ice aerial survey of the Kane Basin polar bear (Ursus maritimus) subpopulation - Øystein Wiig; Stephen N. Atkinson; Erik W. Born; Seth Stapleton; Todd Arnold; Markus Dyck; Kristin L. Laidre; Nicholas J. Lunn; Eric V. Regehr (Polar Biology, 2022)
There is an imminent need to collect information on distribution and abundance of polar bears ( Ursus maritimus ) to understand how they are affected by the ongoing decrease in Arctic sea ice. The Kane Basin (KB) subpopulation is a group of high-latitude polar bears that ranges between High Arctic Canada and NW Greenland around and north of the North Water polynya (NOW). We conducted a line transect distance sampling aerial survey of KB polar bears during 28 April–12 May 2014. A total of 4160 linear kilometers were flown in a helicopter over fast ice in the fjords and over offshore pack ice between 76° 50′ and 80° N′. Using a mark-recapture distance sampling protocol, the estimated abundance was 190 bears (95% lognormal CI: 87–411; CV 39%). This estimate is likely negatively biased to an unknown degree because the offshore sectors of the NOW with much open water were not surveyed because of logistical and safety reasons. Our study demonstrated that aerial surveys may be a feasible method for obtaining abundance estimates for small subpopulations of polar bears.

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Incorporating Shrub Neighborhood Dynamics to Predict Forest Succession Trajectories in an Altered Fire Regime - Carmen L. Tubbesing; Derek J. N. Young; Robert A. York; Scott L. Stephens; John J. Battles (Ecosystems, 2022)

Arboreality drives heat tolerance while elevation drives cold tolerance in tropical rainforest ants - Lily Leahy; Brett R. Scheffers; Stephen E. Williams; Alan N. Andersen (Ecology, 2022)
Determining how species thermal limits correlate with climate is important for understanding biogeographic patterns and assessing vulnerability to climate change. Such analyses need to consider thermal gradients at multiple spatial scales. Here we relate thermal traits of rainforest ants to microclimate conditions from ground to canopy (microgeographic scale) along an elevation gradient (mesogeographic scale) and calculate warming tolerance to assess climate change vulnerability in the Australian Wet Tropics Bioregion. We test the thermal adaptation and thermal niche asymmetry hypotheses to explain interspecific patterns of thermal tolerance at these two spatial scales. We tested cold tolerance (CT min ), heat tolerance (CT max ), and calculated thermal tolerance range (CT range ), using ramping assays for 74 colonies of 40 ant species collected from terrestrial and arboreal habitats at lowland and upland elevation sites and recorded microclimatic conditions for one year. Within sites, arboreal ants were exposed to hotter microclimates and on average had a 4.2°C (95% CI: 2.7–5.6°C) higher CT max and 5.3°C (95% CI: 3.5–7°C) broader CT range than ground‐dwelling ants. This pattern was consistent across the elevation gradient, whether it be the hotter lowlands or the cooler uplands. Across elevation, upland ants could tolerate significantly colder temperatures than lowland ants, whereas the change in CT max was less pronounced, and CT range did not change over elevation. Differential exposure to microclimates, due to localized niche preferences, drives divergence in CT max , while environmental temperatures along the elevation gradient drive divergence in CT min . Our results suggest that both processes of thermal adaptation and thermal niche asymmetry are at play, depending on the spatial scale of observation, and we discuss potential mechanisms underlying these patterns. Despite the broad thermal tolerance range of arboreal rainforest ants, lowland arboreal ants had the lowest warming tolerance and may be most vulnerable to climate change.

Resurrection and emendation of Pseudoparamacroderoides Gupta & Agrawal, 1968 (Digenea: Macroderoididae), description of a new species from Vietnam, and comments on the systematics of macroderoidid genera - Triet N. Truong; Stephen S. Curran; Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2021)

Local canopy disturbance as an explanation for long‐term increases in liana abundance - Stefan A. Schnitzer; David M. DeFilippis; Marco Visser; Sergio Estrada‐Villegas; Rigoberto Rivera‐Camaña; Boris Bernal; Salomé Peréz; Abelino Valdéz; Seberino Valdéz; Antonio Aguilar; James W. Dalling; Eben N. Broadbent; et al. (Ecology Letters, 2021)
Canopy disturbance explains liana abundance and distribution within tropical forests and thus may also explain the widespread pattern of increasing liana abundance; however, this hypothesis remains untested. We used a 10‐year study (2007–2017) of 117,100 rooted lianas in an old‐growth Panamanian forest to test whether local canopy disturbance explains increasing liana abundance. We found that liana density increased 29.2% and basal area 12.5%. The vast majority of these increases were associated with clonal stem proliferation following canopy disturbance, particularly in liana‐dense, low‐canopy gaps, which had far greater liana increases than did undisturbed forest. Lianas may be ecological niche constructors, arresting tree regeneration in gaps and thus creating a high‐light environment that favours sustained liana proliferation. Our findings demonstrate that liana abundance is increasing rapidly and their ability to proliferate via copious clonal stem production in canopy gaps explains much of their increase in this and possibly other tropical forests.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Singing Fin Whale Swimming Behavior in the Central North Pacific - Regina A. Guazzo; Ian N. Durbach; Tyler A. Helble; Gabriela C. Alongi; Cameron R. Martin; Stephen W. Martin; E. Elizabeth Henderson (Frontiers in Marine Science, 2021)
Male fin whales sing using 20 Hz pulses produced in regular patterns of inter-note intervals, but little is known about fin whale swimming behavior while they are singing. Even less is known about fin whales in Hawaiian waters because they have rarely been sighted during surveys and passive acoustic monitoring has been limited to sparse hydrophone systems that do not have localization capabilities. We hypothesized that fin whale kinematics may be related to their singing behavior, or external variables such as time and sea state. To investigate this hypothesis, we analyzed 115 tracks containing 50,034 unique notes generated from passive acoustic recordings on an array of 14 hydrophones from 2011 to 2017 at the U.S. Navy Pacific Missile Range Facility off Kauai, Hawaii. Fin whales swam at an average speed of 1.1 m/s over relatively direct paths. We incorporated the whales' speed and turning angle into hidden Markov models to identify different behavioral states based on the whales' movements. We found that fin whale kinematic behavioral state was related to the vocalization rate (also known as cue rate) and time of day. When cue rate was higher, fin whales were more likely to swim slower and turn more than when cue rate was lower. During the night, fin whales were also more likely to swim slower and turn more than during the day. In addition, we examined whether the presence of singing fin whales was related to time and sea state using generalized additive models. Fin whale track presence was affected by day of the year and song season, and possibly also wind speed and wave height. Although the track kinematics from the fin whale tracks presented here are limited to a subset of whales that are acoustically active, they provide some of the only detailed movements of fin whales in the region and can be compared against fin whale swim speeds in other regions. Understanding how fin whale swimming behavior varies based on their vocalization patterns, time, and environmental factors will help us to contextualize potential changes in whale behavior during Navy training and testing on the range.

Impact of heavy metals dispersion on water supplies around Oshiri and Ishiagu mine districts of Southern Benue Trough, Nigeria - Ezekiel Obinna Igwe; Christian O. Ede; Paulinus N. Nnabo; Stephen N. Ukpai (Modeling Earth Systems and Environment, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Assessing the groundwater quality of a small-scale mining drainage basin using modified water quality indices - Olufemi Victor Omonona; Amobi Chigozie Ekwe; George-Best Azuoko; Stephen N. Ukpai (Arabian Journal of Geosciences, 2021)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Changes in the Movement and Calling Behavior of Minke Whales (Balaenoptera acutorostrata) in Response to Navy Training - Ian N. Durbach; Catriona M. Harris; Cameron Martin; Tyler A. Helble; E. Elizabeth Henderson; Glenn Ierley; Len Thomas; Stephen W. Martin (Frontiers in Marine Science, 2021)
Many marine mammals rely on sound for foraging, maintaining group cohesion, navigation, finding mates, and avoiding predators. These behaviors are potentially disrupted by anthropogenic noise. Behavioral responses to sonar have been observed in a number of baleen whale species but relatively little is known about the responses of minke whales ( Balaenoptera acutorostrata ). Previous analyses demonstrated a spatial redistribution of localizations derived from passive acoustic detections in response to sonar activity, but the lack of a mechanism for associating localizations prevented discriminating between movement and cessation of calling as possible explanations for this redistribution. Here we extend previous analyses by including an association mechanism, allowing us to differentiate between movement responses and calling responses, and to provide direct evidence of horizontal avoidance responses by individual minke whales to sonar during U.S. Navy training activities. We fitted hidden Markov models to 627 tracks that were reconstructed from 3 years of minke whale ( B. acutorostrata ) vocalizations recorded before, during, and after naval training events at the U.S. Navy’s Pacific Missile Range Facility, Kauai, Hawaii. The fitted models were used to identify different movement behaviors and to investigate the effect of sonar activity on these behaviors. Movement was faster and more directed during sonar exposure than in baseline phases. The mean direction of movement differed during sonar exposure, and was consistent with movement away from sonar-producing ships. Animals were also more likely to cease calling during sonar. There was substantial individual variation in response. Our findings add large-sample support to previous demonstrations of horizontal avoidance responses by individual minke whales to sonar in controlled exposure experiments, and demonstrate the complex nature of behavioral responses to sonar activity: some, but not all, whales exhibited behavioral changes, which took the form of horizontal avoidance or ceasing to call.

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Correction to: Updates to the Regional Seismic Travel Time (RSTT) Model: 2. Path-dependent Travel-time Uncertainty - Michael L. Begnaud; Dale N. Anderson; Stephen C. Myers; Brian Young; James R. Hipp; W. Scott Phillips (Pure and Applied Geophysics, 2021)

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Genetic diversity and population structure analysis of bold type rice collection from Southern India - N. Nithya; R. Beena; P. S. Abida; J. Sreekumar; Roy Stephen; V. G. Jayalekshmi; R. V. Manju; M. M. Viji (Cereal Research Communications, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Socio-ecological Factors of Zoonotic Diseases Exposure in Colorado Dairy Workers - Jairo Enrique Palomares Velosa; Mo D. Salman; Ivette N. Roman-Muniz; Stephen Reynolds; Lyndsey Linke; Roberta Magnuson; Craig S. McConnel; Sangeeta Rao (Journal of Agromedicine, 2021)

Unveiling the Dynamics of KRAS4b on Lipid Model Membranes - Cesar A. López; Animesh Agarwal; Que N. Van; Andrew G. Stephen; S. Gnanakaran (The Journal of Membrane Biology, 2021)
Small GTPase proteins are ubiquitous and responsible for regulating several processes related to cell growth and differentiation. Mutations that stabilize their active state can lead to uncontrolled cell proliferation and cancer. Although these proteins are well characterized at the cellular scale, the molecular mechanisms governing their functions are still poorly understood. In addition, there is limited information about the regulatory function of the cell membrane which supports their activity. Thus, we have studied the dynamics and conformations of the farnesylated KRAS4b in various membrane model systems, ranging from binary fluid mixtures to heterogeneous raft mimics. Our approach combines long time-scale coarse-grained (CG) simulations and Markov state models to dissect the membrane-supported dynamics of KRAS4b. Our simulations reveal that protein dynamics is mainly modulated by the presence of anionic lipids and to some extent by the nucleotide state (activation) of the protein. In addition, our results suggest that both the farnesyl and the polybasic hypervariable region (HVR) are responsible for its preferential partitioning within the liquid-disordered (Ld) domains in membranes, potentially enhancing the formation of membrane-driven signaling platforms. Graphic Abstract

Locally abundant, endangered Mariana swiftlets impact the abundance, behavior, and body condition of an invasive predator - Page E. Klug; Amy A. Yackel Adams; Shane R. Siers; Kevin M. Brindock; Stephen M. Mosher; M. J. Mazurek; William C. Pitt; Robert N. Reed (Oecologia, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Climate change impacts and strategies for adaptation for water resource management in Indiana - Keith A. Cherkauer; Laura C. Bowling; Kyuhyun Byun; Indrajeet Chaubey; Natalie Chin; Darren L. Ficklin; Alan F. Hamlet; Stephen J. Kines; Charlotte I. Lee; Ram Neupane; Garett W. Pignotti; Sanoar Rahman; et al. (Climatic Change, 2021)

A new virus of the family Tombusviridae infecting sugarcane - Muhammad N. Tahir; Stephen Bolus; Samuel C. Grinstead; Sharon A. McFarlane; Dimitre Mollov (Archives of Virology, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Updates to the Regional Seismic Travel Time (RSTT) Model: 2. Path-dependent Travel-time Uncertainty - Michael L. Begnaud; Dale N. Anderson; Stephen C. Myers; Brian Young; James R. Hipp; W. Scott Phillips (Pure and Applied Geophysics, 2021)
The regional seismic travel time (RSTT) model and software were developed to improve travel-time prediction accuracy by accounting for three-dimensional crust and upper mantle structure. Travel-time uncertainty estimates are used in the process of associating seismic phases to events and to accurately calculate location uncertainty bounds (i.e. event location error ellipses). We improve on the current distance-dependent uncertainty parameterization for RSTT using a random effects model to estimate slowness (inverse velocity) uncertainty as a mean squared error for each model parameter. The random effects model separates the error between observed slowness and model predicted slowness into bias and random components. The path-specific travel-time uncertainty is calculated by integrating these mean squared errors along a seismic-phase ray path. We demonstrate that event location error ellipses computed for a 90% coverage ellipse metric (used by the Comprehensive Nuclear-Test-Ban Treaty Organization International Data Centre (IDC)), and using the path-specific travel-time uncertainty approach, are more representative (median 82.5% ellipse percentage) of true location error than error ellipses computed using distance-dependent travel-time uncertainties (median 70.1%). We also demonstrate measurable improvement in location uncertainties using the RSTT method compared to the current station correction approach used at the IDC (median 74.3% coverage ellipse).

Persistent COVID-19-associated neurocognitive symptoms in non-hospitalized patients - Joanna Hellmuth; T. Allen Barnett; Breton M. Asken; J. Daniel Kelly; Leonel Torres; Melanie L. Stephens; Bryan Greenhouse; Jeffrey N. Martin; Felicia C. Chow; Steven G. Deeks; Meredith Greene; Bruce L. Miller; et al. (Journal of NeuroVirology, 2021)
As cases of coronavirus disease 2019 (COVID-19) mount worldwide, attention is needed on potential long-term neurologic impacts for the majority of patients who experience mild to moderate illness managed as outpatients. To date, there has not been discussion of persistent neurocognitive deficits in patients with milder COVID-19. We present two cases of non-hospitalized patients recovering from COVID-19 with persistent neurocognitive symptoms. Commonly used cognitive screens were normal, while more detailed testing revealed working memory and executive functioning deficits. An observational cohort study of individuals recovering from COVID-19 (14 or more days following symptom onset) identified that among the first 100 individuals enrolled, 14 were non-hospitalized patients reporting persistent cognitive issues. These 14 participants had a median age of 39 years (interquartile range: 35–56), and cognitive symptoms were present for at least a median of 98 days (interquartile range: 71–120 following acute COVID-19 symptoms); no participants with follow-up evaluation reported symptom resolution. We discuss potential mechanisms to be explored in future studies, including direct viral effects, indirect consequences of immune activation, and immune dysregulation causing auto-antibody production.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Primary production and habitat stability organize marine communities - Alli N. Cramer; Stephen L. Katz (Global Ecology and Biogeography, 2021)
Aim The emergence of pattern in the natural world can carry important messages about underlying processes. For example, collections of broadly similar terrestrial ecosystems have historically been categorized as biomes – groupings of systems that sort along energetic and structural process axes. In marine systems however, a similar classification of biomes has not emerged. The aim here is to develop an effective classification scheme for marine biomes and communities. Approach Candidate predictor variables that could explain pattern and process in differentiating marine communities, such as light, nutrients, depth, etc., were collected from the existing literature with a systematic review. The candidate predictors were then evaluated in an inductive process, allowing community level observations to demonstrate patterns across marine biomes. Marine biomes and communities were identified a priori, and emergent patterns were evaluated quantitatively, via principal component ordination based on the vectors of explanatory predictors, and qualitatively via mapping. Conclusions Gross primary production and substrate mobility not only effectively sort marine biomes, but also work on finer scales discriminating communities within biomes. As a result, these predictors were more effective in classifying marine communities than other scales, such as available light and nutrients. The richness of this classification is also demonstrated in revealing other patterns, such as the distribution of human impacts. The effectiveness of this mapping provides support for, but is not a test of, the hypothesis that primary production and substrate mobility are important underlying processes that interact to structure marine ecosystems.

Hemolymph Proteomics and Gut Microbiota of Horseshoe Crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda - Zhe Qu; Thomas C. N. Leung; Wenyan Nong; Ho Yin Yip; Ivy H. T. Lee; Siu Gin Cheung; Ngai Sai Ming; Wai Lok So; William G. Bendena; Stephen S. Tobe; Jerome H. L. Hui (Frontiers in Marine Science, 2020)
Horseshoe crabs are a group of marine chelicerates that contain only four extant species, some of which are endangered. Their hemolymph has been widely used in medical applications for endotoxin detection. Nevertheless, there is limited information on the profiles of their hemolymph proteins and their gut microbial diversity. In this study, we performed the first detailed investigation of the hemolymph proteomics and gut microbiota of two Asian horseshoe crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda . Among the identified proteins being cataloged in the juvenile and adult hemolymph, unexpectedly, sesquiterpenoid signaling pathway proteins including Heat shock protein 83 (HSP83), Chd64, and a juvenile hormone binding protein (JHBP) were revealed. This provides evidence for the presence of functional sesquiterpenoid hormonal systems in these marine chelicerates. consumption of certain horseshoe crab species often leads to tetrodotoxin poisoning and the horseshoe crab is thought to possess a tetrodotoxin resistance mechanism. As such, sodium channels were analyzed and found to have critical amino acid residues that are similar to the toxin resistant pufferfish sodium channels. The source of the toxin is unknown so we investigated the gut microbiota, and found that Clostridium and Vibrio were the most dominant bacteria in T. tridentatus and C. rotundicauda , respectively. Together, this study provides a framework for further understanding of sesquiterpenoids and gut microbiota of these marine chelicerates.

Longitudinal associations between amygdala reactivity and cannabis use in a large sample of adolescents - Philip A. Spechler; Bader Chaarani; Catherine Orr; Matthew D. Albaugh; Nicholas R. Fontaine; Stephen T. Higgins; Tobias Banaschewski; Arun L. W. Bokde; Erin Burke Quinlan; Sylvane Desrivières; Herta Flor; Antoine Grigis; et al. (Psychopharmacology, 2020)

Distribution of fungi and their toxic metabolites in melon and sesame seeds marketed in two major producing states in Nigeria - Adetoun O. Esan; Stephen O. Fapohunda; Chibundu N. Ezekiel; Michael Sulyok; Rudolf Krska (Mycotoxin Research, 2020)
In this study, melon ( n = 60) and sesame ( n = 60) seeds purchased from markets within Benue and Nasarawa states, respectively, in Nigeria, during two seasons (dry and wet), were analysed for fungal and mycotoxin contamination in order to determine the safety of these foods for human consumption. Molecular analysis revealed the following seven fungal taxonomic groups in the foods: Aspergillus section Candidi , Aspergillus section Flavi , Aspergillus section Nigri , Cladosporium , Fusarium fujikuroi species group, Penicillium , and Pleosporales/Didymellaceae. A total of 78 microbial metabolites, including several mycotoxins, occurred in the foods. The most frequent mycotoxins in melon and sesame were aflatoxin B 1 (occurrence: 76%) and alternariol monomethyl ether (occurrence: 59%), respectively. However, higher mean total aflatoxin levels occurred in sesame (17 μg kg −1 ) than in melon (11 μg kg −1 ). About 28 and 5% of melon and sesame, respectively, exceeded the 4 μg kg −1 total aflatoxin limit for oilseeds intended for direct human consumption in the European Union. Additionally, fumonisin B 1 and moniliformin occurred only in sesame, whilst ochratoxins A and B occurred only in melon; ochratoxin B being reported for the first time in this food. Our data indicated seasonal variations in the fungal and mycotoxin contamination levels in both foods.

Effects of fungicide chemical class, fungicide application timing, and environment on Fusarium head blight in winter wheat - Carlos Bolanos-Carriel; Stephen N. Wegulo; P. Stephen Baenziger; Deanna Funnell-Harris; Heather E. Hallen-Adams; Kent M. Eskridge (European Journal of Plant Pathology, 2020)

Transient benefits of climate change for a high‐Arctic polar bear ( Ursus maritimus ) subpopulation - Kristin L. Laidre; Stephen N. Atkinson; Eric V. Regehr; Harry L. Stern; Erik W. Born; Øystein Wiig; Nicholas J. Lunn; Markus Dyck; Patrick Heagerty; Benjamin R. Cohen (Global Change Biology, 2020)
Kane Basin (KB) is one of the world's most northerly polar bear ( Ursus maritimus ) subpopulations, where bears have historically inhabited a mix of thick multiyear and annual sea ice year‐round. Currently, KB is transitioning to a seasonally ice‐free region because of climate change. This ecological shift has been hypothesized to benefit polar bears in the near‐term due to thinner ice with increased biological production, although this has not been demonstrated empirically. We assess sea‐ice changes in KB together with changes in polar bear movements, seasonal ranges, body condition, and reproductive metrics obtained from capture–recapture (physical and genetic) and satellite telemetry studies during two study periods (1993–1997 and 2012–2016). The annual cycle of sea‐ice habitat in KB shifted from a year‐round ice platform (~50% coverage in summer) in the 1990s to nearly complete melt‐out in summer ( p = .004). Between the 1990s and 2010s, adult female (AF) seasonal ranges more than doubled in spring and summer and were significantly larger in all months. Body condition scores improved for all ages and both sexes. Mean litter sizes of cubs‐of‐the‐year (C0s) and yearlings (C1s), and the number of C1s per AF, did not change between decades. The date of spring sea‐ice retreat in the previous year was positively correlated with C1 litter size, suggesting smaller litters following years with earlier sea‐ice breakup. Our study provides evidence for range expansion, improved body condition, and stable reproductive performance in the KB polar bear subpopulation. These changes, together with a likely increasing subpopulation abundance, may reflect the shift from thick, multiyear ice to thinner, seasonal ice with higher biological productivity. The duration of these benefits is unknown because, under unmitigated climate change, continued sea‐ice loss is expected to eventually have negative demographic and ecological effects on all polar bears.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Multiomic immune clockworks of pregnancy - Laura S. Peterson; Ina A. Stelzer; Amy S. Tsai; Mohammad S. Ghaemi; Xiaoyuan Han; Kazuo Ando; Virginia D. Winn; Nadine R. Martinez; Kevin Contrepois; Mira N. Moufarrej; Stephen Quake; David A. Relman; et al. (Seminars in Immunopathology, 2020)
Preterm birth is the leading cause of mortality in children under the age of five worldwide. Despite major efforts, we still lack the ability to accurately predict and effectively prevent preterm birth. While multiple factors contribute to preterm labor, dysregulations of immunological adaptations required for the maintenance of a healthy pregnancy is at its pathophysiological core. Consequently, a precise understanding of these chronologically paced immune adaptations and of the biological pacemakers that synchronize the pregnancy “immune clock” is a critical first step towards identifying deviations that are hallmarks of peterm birth. Here, we will review key elements of the fetal, placental, and maternal pacemakers that program the immune clock of pregnancy. We will then emphasize multiomic studies that enable a more integrated view of pregnancy-related immune adaptations. Such multiomic assessments can strengthen the biological plausibility of immunological findings and increase the power of biological signatures predictive of preterm birth

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Prospects for classical biological control of Marchalina hellenica in Australia - Dimitrios N. Avtzis; Umar K. Lubanga; Greg K. Lefoe; Raelene M. Kwong; Nikoleta Eleftheriadou; Anneliza Andreadi; Stephen Elms; Richard Shaw; Marc Kenis (BioControl, 2020)

Variation in carotenoid-containing retinal oil droplets correlates with variation in perception of carotenoid coloration - Eleanor M. Caves; Lorian E. Schweikert; Patrick A. Green; Matthew N. Zipple; Carlos Taboada; Susan Peters; Stephen Nowicki; Sönke Johnsen (Behavioral Ecology and Sociobiology, 2020)
In the context of mate choice, males may vary continuously in their expression of assessment signals, typically reflecting information about variation in mate quality. Similarly, females may exhibit variation in mate preference, which could be due to differences in how individual females perceive signals. The extent to which perception varies across individuals, however, and whether differences in sensory physiology underlie perceptual differences is poorly understood. Carotenoid pigments create the orange-red coloration of many assessment signals, and they also play a role in color discrimination in many vertebrates via their presence in retinal oil droplets. Here, we link variation in oil droplet carotenoid concentration with the ability of female zebra finches ( Taeniopygia guttata ) to discriminate an orange-red color continuum that parallels variation in male beak color, a mate assessment signal. We have shown previously that zebra finch females perceive this color range categorically, meaning they label color stimuli from this continuum as belonging to two categories and exhibit better discrimination between colors from different categories as compared with equally different colors from within a category. We quantified behavioral color discrimination and R-type (red) cone oil droplet spectral absorption, a proxy for carotenoid concentration. Oil droplet absorption was strongly predictive of variation in behavioral color discrimination ability. In particular, higher carotenoid concentration in oil droplets correlated with increased discrimination of colors from different sides of the previously identified category boundary. These data show that differences in the sensory periphery can correlate with individual variation in perception of a signal-relevant color range. Significance statement Signal receivers vary in their preferences for signaling traits, but whether this is due to variation in how different receivers perceive signals is not well-understood. We show that variation between individual zebra finch females in perception of an orange-red continuum range correlates with the carotenoid concentration of retinal oil droplets. These data provide the first direct evidence that individual variation in oil droplet carotenoid concentration can lead to variation in color discrimination ability. Linking variation in signal-relevant color discrimination ability with variation in retinal physiology suggests a potential mechanism contributing to individual variation in signal assessment.

Water stress mediated root trait dynamics and identification of microsatellite markers associated with root traits in rice (Oryza sativa L.) - R. Rejeth; Ch. L. N. Manikanta; R. Beena; Roy Stephen; R. V. Manju; M. M. Viji (Physiology and Molecular Biology of Plants, 2020)

Structural insights into the role of the acid-alcohol pair of residues required for dioxygen activation in cytochrome P450 enzymes - Tom Coleman; Jeanette E. Stok; Matthew N. Podgorski; John B. Bruning; James J. De Voss; Stephen G. Bell (JBIC Journal of Biological Inorganic Chemistry, 2020)

The effects of lutein and zeaxanthin on resting state functional connectivity in older Caucasian adults: a randomized controlled trial - Cutter A. Lindbergh; Jinglei Lv; Yu Zhao; Catherine M. Mewborn; Antonio N. Puente; Douglas P. Terry; Lisa M. Renzi-Hammond; Billy R. Hammond; Tianming Liu; L. Stephen Miller (Brain Imaging and Behavior, 2020)

Acute zoster plasma contains elevated amyloid, correlating with Aβ42 and amylin levels, and is amyloidogenic - Andrew N. Bubak; Cheryl Beseler; Christina N. Como; Stephen K. Tyring; Christopher Haley; Teresa Mescher; James E. Hassell; Randall J. Cohrs; Huntington Potter; Maria A. Nagel (Journal of NeuroVirology, 2020)

Nuclear and plastid SNP markers for tracing Cedrela timber in the tropics - Kathelyn Paredes-Villanueva; Celine Blanc-Jolivet; Malte Mader; Eurídice N. Honorio Coronado; Carmen Garcia-Davila; Alexandre M. Sebbenn; Barbara Rocha Venancio Meyer-Sand; Henri Caron; Niklas Tysklind; Stephen Cavers; Bernd Degen (Conservation Genetics Resources, 2020)

Polar bear denning distribution in the Canadian Arctic - Katie R. N. Florko; Andrew E. Derocher; C-Jae C. Breiter; Maha Ghazal; Daryll Hedman; Jeff W. Higdon; Evan S. Richardson; Vicki Sahanatien; Vicki Trim; Stephen D. Petersen (Polar Biology, 2020)
Declines in Arctic sea ice associated with climate change have resulted in habitat loss for ice-adapted species, while facilitating increased human development at higher latitudes. Development increases land-use and shipping traffic, which can threaten ecologically and culturally important species. Female polar bears ( Ursus maritimus ) and cubs are susceptible to disturbance during denning; a better understanding of denning habitat distribution may aid management. We compiled existing location data on polar bear denning ( n = 64 sources) in Canada between 1967 and 2018, including traditional ecological knowledge (TEK) studies, government and consultant reports, peer-reviewed scientific articles, and unpublished data acquired through data-sharing agreements. We synthesized these data to create a map of known denning locations. Most coastal regions in northern Canada supported denning, but large areas exist where denning is unreported. Gaps remain in the knowledge of polar bear denning in Canada and filling these will aid the conservation and management of polar bears in a changing Arctic.

Fluid–Structure Interaction Models of Bioprosthetic Heart Valve Dynamics in an Experimental Pulse Duplicator - Jae H. Lee; Alex D. Rygg; Ebrahim M. Kolahdouz; Simone Rossi; Stephen M. Retta; Nandini Duraiswamy; Lawrence N. Scotten; Brent A. Craven; Boyce E. Griffith (Annals of Biomedical Engineering, 2020)
Computer modeling and simulation is a powerful tool for assessing the performance of medical devices such as bioprosthetic heart valves (BHVs) that promises to accelerate device design and regulation. This study describes work to develop dynamic computer models of BHVs in the aortic test section of an experimental pulse-duplicator platform that is used in academia, industry, and regulatory agencies to assess BHV performance. These computational models are based on a hyperelastic finite element extension of the immersed boundary method for fluid–structure interaction (FSI). We focus on porcine tissue and bovine pericardial BHVs, which are commonly used in surgical valve replacement. We compare our numerical simulations to experimental data from two similar pulse duplicators, including a commercial ViVitro system and a custom platform related to the ViVitro pulse duplicator. Excellent agreement is demonstrated between the computational and experimental results for bulk flow rates, pressures, valve open areas, and the timing of valve opening and closure in conditions commonly used to assess BHV performance. In addition, reasonable agreement is demonstrated for quantitative measures of leaflet kinematics under these same conditions. This work represents a step towards the experimental validation of this FSI modeling platform for evaluating BHVs.

Storm impacts on phytoplankton community dynamics in lakes - Jason D. Stockwell; Jonathan P. Doubek; Rita Adrian; Orlane Anneville; Cayelan C. Carey; Laurence Carvalho; Lisette N. De Senerpont Domis; Gaël Dur; Marieke A. Frassl; Hans‐Peter Grossart; Bas W. Ibelings; Marc J. Lajeunesse; et al. (Global Change Biology, 2020)
In many regions across the globe, extreme weather events such as storms have increased in frequency, intensity, and duration due to climate change. Ecological theory predicts that such extreme events should have large impacts on ecosystem structure and function. High winds and precipitation associated with storms can affect lakes via short‐term runoff events from watersheds and physical mixing of the water column. In addition, lakes connected to rivers and streams will also experience flushing due to high flow rates. Although we have a well‐developed understanding of how wind and precipitation events can alter lake physical processes and some aspects of biogeochemical cycling, our mechanistic understanding of the emergent responses of phytoplankton communities is poor. Here we provide a comprehensive synthesis that identifies how storms interact with lake and watershed attributes and their antecedent conditions to generate changes in lake physical and chemical environments. Such changes can restructure phytoplankton communities and their dynamics, as well as result in altered ecological function (e.g., carbon, nutrient and energy cycling) in the short‐ and long‐term. We summarize the current understanding of storm‐induced phytoplankton dynamics, identify knowledge gaps with a systematic review of the literature, and suggest future research directions across a gradient of lake types and environmental conditions.

Food and temperature stressors have opposing effects in determining flexible migration decisions in brown trout ( Salmo trutta ) - Louise C. Archer; Stephen A. Hutton; Luke Harman; Stephen D. McCormick; Michael N. O’Grady; Joseph P. Kerry; W. Russell Poole; Patrick Gargan; Philip McGinnity; Thomas E. Reed (Global Change Biology, 2020)
With rapid global change, organisms in natural systems are exposed to a multitude of stressors that likely co‐occur, with uncertain impacts. We explored individual and cumulative effects of co‐occurring environmental stressors on the striking, yet poorly understood, phenomenon of facultative migration. We reared offspring of a brown trout population that naturally demonstrates facultative anadromy (sea migration), under different environmental stressor treatments and measured life history responses in terms of migratory tactics and freshwater maturation rates. Juvenile fish were exposed to reduced food availability, temperatures elevated to 1.8°C above natural conditions or both treatments in combination over 18 months of experimental tank rearing. When considered in isolation, reduced food had negative effects on the size, mass and condition of fish across the experiment. We detected variable effects of warm temperatures (negative effects on size and mass, but positive effect on lipids). When combined with food restriction, temperature effects on these traits were less pronounced, implying antagonistic stressor effects on morphological traits. Stressors combined additively, but had opposing effects on life history tactics: migration increased and maturation rates decreased under low food conditions, whereas the opposite occurred in the warm temperature treatment. Not all fish had expressed maturation or migration tactics by the end of the study, and the frequency of these ‘unassigned’ fish was higher in food deprivation treatments, but lower in warm treatments. Fish showing migration tactics were smaller and in poorer condition than fish showing maturation tactics, but were similar in size to unassigned fish. We further detected effects of food restriction on hypo‐osmoregulatory function of migrants that may influence the fitness benefits of the migratory tactic at sea. We also highlight that responses to multiple stressors may vary depending on the response considered. Collectively, our results indicate contrasting effects of environmental stressors on life history trajectories in a facultatively migratory species.

Taxonomic revision, phylogeny, and cyst wall composition of the dinoflagellate cyst genus Votadinium Reid (Dinophyceae, Peridiniales, Protoperidiniaceae) - Pieter R. Gurdebeke; Kenneth N. Mertens; Vera Pospelova; Kazumi Matsuoka; Zhen Li; Kristin E. Gribble; Haifeng Gu; Kara Bogus; Henk Vrielinck; Stephen Louwye (Palynology, 2020)

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

Strain-specificity in the hydrogen sulphide signalling network following dietary restriction in recombinant inbred mice - Stephen E. Wilkie; Lorna Mulvey; William A. Sands; Diana E. Marcu; Roderick N. Carter; Nicholas M. Morton; Christopher Hine; James R. Mitchell; Colin Selman (GeroScience, 2020)
Modulation of the ageing process by dietary restriction (DR) across multiple taxa is well established. While the exact mechanism through which DR acts remains elusive, the gasotransmitter hydrogen sulphide (H 2 S) may play an important role. We employed a comparative-type approach using females from three ILSXISS recombinant inbred mouse strains previously reported to show differential lifespan responses following 40% DR. Following long-term (10 months) 40% DR, strain TejJ89—reported to show lifespan extension under DR—exhibited elevated hepatic H 2 S production relative to its strain-specific ad libitum (AL) control. Strain TejJ48 (no reported lifespan effect following 40% DR) exhibited significantly reduced hepatic H 2 S production, while H 2 S production was unaffected by DR in strain TejJ114 (shortened lifespan reported following 40% DR). These differences in H 2 S production were reflected in highly divergent gene and protein expression profiles of the major H 2 S production and disposal enzymes across strains. Increased hepatic H 2 S production in TejJ89 mice was associated with elevation of the mitochondrial H 2 S-producing enzyme 3-mercaptopyruvate sulfurtransferase (MPST). Our findings further support the potential role of H 2 S in DR-induced longevity and indicate the presence of genotypic-specificity in the production and disposal of hepatic H 2 S in response to 40% DR in mice.

A Highly Conductive 3D Cardiac Patch Fabricated Using Cardiac Myocytes Reprogrammed from Human Adipogenic Mesenchymal Stem Cells - Reza Abbasgholizadeh; Jose Francisco Islas; Stephen Navran; Vladimir N. Potaman; Robert J. Schwartz; Ravi K. Birla (Cardiovascular Engineering and Technology, 2020)

A newly recorded Rickettsia of the Torix group is a recent intruder and an endosymbiont in the whitefly Bemisia tabaci - Hua‐Ling Wang; Teng Lei; Xiao‐Wei Wang; M. N. Maruthi; Dan‐Tong Zhu; Stephen L. Cameron; Qiong Rao; Hong‐Wei Shan; John Colvin; Yin‐Quan Liu; Shu‐Sheng Liu (Environmental Microbiology, 2020)
Summary The bacterium Rickettsia is found widely in phytophagous insects and often exerts profound effects on the phenotype and fitness of its hosts. Here, we decrypt a new, independent, phylogenetically ancient Torix Rickettsia endosymbiont found constantly in a laboratory line of an economically important insect Asia II 7, a putative species of the Bemisia tabaci whitefly complex (Hemiptera: Aleyrodidae), and occasionally in field whitefly populations. This new Rickettsia distributes throughout the body of its whitefly host. Genetically, compared to Rickettsia_ bellii_MEAM1 found earlier in whiteflies, the new Rickettsia species has more gene families and pathways, which may be important factors in shaping specific symbiotic relationships. We propose the name ‘ Candidatus Rickettsia_Torix_ Bemisia_tabaci (RiTBt)’ for this new endosymbiont associated with whiteflies. Comparative genomic analyses indicate that RiTBi may be a relatively recent intruder in whiteflies given its low abundance in the field and relatively larger genome compared to Rickettsia _bellii_MEAM1.

Effects of Elevated Sea Levels and Waves on Southern California Estuaries During the 2015–2016 El Niño - Madeleine E. Harvey; Sarah N. Giddings; Eric D. Stein; Jeffrey A. Crooks; Christine Whitcraft; Timu Gallien; John L. Largier; Liesl Tiefenthaler; Hallee Meltzer; Geno Pawlak; Karen Thorne; Karina Johnston; et al. (Estuaries and Coasts, 2020)
The 2015–2016 El Niño provided insight into how low-inflow estuaries might respond to future climate regimes, including high sea levels and more intense waves. High waves and water levels coupled with low rainfall along the Southern California coastline provided the opportunity to examine how extreme ocean forcing impacts estuaries independently from fluvial events. From November 2015 to April 2016, water levels were measured in 13 Southern California estuaries, including both intermittently closed and perennially open estuaries with varying watershed size, urban development, and management practices. Elevated ocean water levels caused raised water levels and prolonged inundation in all of the estuaries studied. Water levels inside perennially open estuaries mirrored ocean water levels, while those inside intermittently closed estuaries (ICEs) exhibited enhanced higher-high water levels during large waves, and tides were truncated at low tides due to a wave-built sand sill at the mouth, resulting in elevated detided water levels. ICEs closed when sufficient wave-driven sand accretion formed a barrier berm across the mouth separating the estuary from the ocean, the height of which can be estimated using estuarine lower-low water levels. During the 2015–2016 El Niño, a greater number of Southern California ICEs closed than during a typical year and ICEs that close annually experienced longer than normal closures. Overall, sill accretion and wave exposure were important contributing factors to individual estuarine response to ocean conditions. Understanding how estuaries respond to increased sea levels and waves and the factors that influence closures will help managers develop appropriate adaptation strategies.

Integrated Modeling to Evaluate Climate Change Impacts on Coupled Social-Ecological Systems in Alaska - Anne Babcock Hollowed; Kirstin Kari Holsman; Alan C. Haynie; Albert J. Hermann; Andre E. Punt; Kerim Aydin; James N. Ianelli; Stephen Kasperski; Wei Cheng; Amanda Faig; Kelly A. Kearney; Jonathan C. P. Reum; et al. (Frontiers in Marine Science, 2020)

Aerosol Pirfenidone Pharmacokinetics after Inhaled Delivery in Sheep: a Viable Approach to Treating Idiopathic Pulmonary Fibrosis - Lisa M Kaminskas; Cornelia B Landersdorfer; Robert J Bischof; Nathania Leong; Jibriil Ibrahim; Andrew N Davies; Stephen Pham; Steven Beck; A. Bruce Montgomery; Mark W Surber (Pharmaceutical Research, 2020)

Fish Diet Shifts Associated with the Northern Gulf of Mexico Hypoxic Zone - Cassandra N. Glaspie; Melissa Clouse; Klaus Huebert; Stuart A. Ludsin; Doran M. Mason; James J. Pierson; Michael R. Roman; Stephen B. Brandt (Estuaries and Coasts, 2019)

Assessment of the Suitability of Mine Water Treated with Pervious Concrete for Irrigation Use - Ayanda N. Shabalala; Stephen O. Ekolu (Mine Water and the Environment, 2019)

Look at the time: diel variation in the flight initiation distance of a nectarivorous bird - Stephen M. Ferguson; Lauren N. Gilson; Philip W. Bateman (Behavioral Ecology and Sociobiology, 2019)

Bambara groundnut: an exemplar underutilised legume for resilience under climate change - Sean Mayes; Wai Kuan Ho; Hui Hui Chai; Xiuqing Gao; Aloyce C. Kundy; Kumbirai I. Mateva; Muhammad Zahrulakmal; Mohd Khairul Izwan Mohd Hahiree; Presidor Kendabie; Luis C. S. Licea; Festo Massawe; Tafadzwanashe Mabhaudhi; et al. (Planta, 2019)

Determining contemporary and historical sediment sources in a large drainage basin impacted by cumulative effects: the regulated Nechako River, British Columbia, Canada - David Gateuille; Philip N. Owens; Ellen L. Petticrew; Barry P. Booth; Todd D. French; Stephen J. Déry (Journal of Soils and Sediments, 2019)

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Radiological Estimation of Intracranial Blood Volume and Occurrence of Hydrocephalus Determines Stress-Induced Hyperglycemia After Aneurysmal Subarachnoid Hemorrhage - Joshua A Santucci; Stephen R Ross; John C Greenert; Faranak Aghaei; Lance Ford; Kimberly M Hollabaugh; Benjamin O Cornwell; Dee H Wu; Bin Zheng; Bradley N Bohnstedt; Bappaditya Ray (Translational Stroke Research, 2019)

First detection and isolation of infectious haematopoietic necrosis virus from farmed rainbow trout in Nyeri County, Kenya - Isaac R. Mulei; Phillip N. Nyaga; Paul G. Mbuthia; Robert M. Waruiru; Cheng Xu; Øystein Evensen; Stephen Mutoloki (Journal of Fish Diseases, 2019)
Infectious haematopoietic necrosis virus (IHNV) is the causative agent of infectious haematopoietic necrosis, a disease of salmonid responsible for great economic losses. The disease occurs in most parts of the world where rainbow trout is reared but has not been previously reported in Kenya. In this study, rainbow trout fry and growers from two farms in Nyeri County were screened for IHNV. Whole fry ( n = 4 from each farm) and kidney samples from growers ( n = 15 and n = 6 from the two farms, respectively) were collected and preserved for cell culture examination or PCR analysis. Screening of samples was done by PCR followed by sequencing of the glycoprotein gene of the virus. Demonstration of the virus was done by propagation in EPC cells followed by the indirect fluorescence antibody test (IFAT). The results revealed the presence of IHNV at low prevalence of 0.1 and 0.4 for the two farms. The virus was confirmed both by IFAT and by partial sequencing of the G gene. Phylogenetic analysis revealed that the Kenyan isolates were identical to those of the J genogroup found mostly in Asia. The findings have implications for biosecurity measures and import regulations for the Kenyan rainbow trout industry.

Cardiovascular response of postmenopausal women to 8 weeks of sprint interval training - Daniel Zhang; Tornike Janjgava; Stephen H. Boutcher; Yati N. Boutcher (European Journal of Applied Physiology, 2019)

Root biomass variation of cocoa and implications for carbon stocks in agroforestry systems - Kira A. Borden; Luke C. N. Anglaaere; Stephen Adu-Bredu; Marney E. Isaac (Agroforestry Systems, 2019)

The ICES Working Group on Oceanic Hydrography: A Bridge From In-situ Sampling to the Remote Autonomous Observation Era - César González-Pola; Paula Fratantoni; Karin M. H. Larsen; N. Penny Holliday; Stephen Dye; Kjell Arne Mork; Agnieszka Beszczynska-Möller; Hedinn Valdimarsson; Alexander Trofimov; Hjalte Parner; Holger Klein; Boris Cisewski; et al. (Frontiers in Marine Science, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Impact of Future Climate Change on Water Temperature and Thermal Habitat for Keystone Fishes in the Lower Saint John River, Canada - Stephen J. Dugdale; R. Allen Curry; André St-Hilaire; Samuel N. Andrews (Water Resources Management, 2018)

Outlier SNPs detect weak regional structure against a background of genetic homogeneity in the Eastern Rock Lobster, Sagmariasus verreauxi - Laura N. Woodings; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; Geoffrey W. Liggins; Bridget S. Green; Ira R. Cooke; James J. Bell; Jan M. Strugnell (Marine Biology, 2018)

A framework for selection of blood-based biomarkers for geroscience-guided clinical trials: report from the TAME Biomarkers Workgroup - Jamie N. Justice; Luigi Ferrucci; Anne B. Newman; Vanita R. Aroda; Judy L. Bahnson; Jasmin Divers; Mark A. Espeland; Santica Marcovina; Michael N. Pollak; Stephen B. Kritchevsky; Nir Barzilai; George A. Kuchel (GeroScience, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Late Holocene wetland transgression and 500 years of vegetation and fire variability in the semi-arid Amboseli landscape, southern Kenya - Esther N. Githumbi; Colin J. Courtney Mustaphi; Kevin J. Yun; Veronica Muiruri; Stephen M. Rucina; Rob Marchant (Ambio, 2018)

What are the Conditions of Riparian Ecosystems? Identifying Impaired Floodplain Ecosystems across the Western U.S. Using the Riparian Condition Assessment (RCA) Tool - William W. Macfarlane; Jordan T. Gilbert; Joshua D. Gilbert; William C. Saunders; Nate Hough-Snee; Chalese Hafen; Joseph M. Wheaton; Stephen N. Bennett (Environmental Management, 2018)

Ocean warming has a greater effect than acidification on the early life history development and swimming performance of a large circumglobal pelagic fish - Sue‐Ann Watson; Bridie J. M. Allan; David E. McQueen; Simon Nicol; Darren M. Parsons; Stephen M. J. Pether; Stephen Pope; Alvin N. Setiawan; Neville Smith; Carly Wilson; Philip L. Munday (Global Change Biology, 2018)
Ocean warming and acidification are serious threats to marine life; however, their individual and combined effects on large pelagic and predatory fishes are poorly understood. We determined the effects of projected future temperature and carbon dioxide ( CO 2 ) levels on survival, growth, morphological development and swimming performance on the early life stages of a large circumglobal pelagic fish, the yellowtail kingfish Seriola lalandi . Eggs, larvae and juveniles were reared in cross‐factored treatments of temperature (21 and 25°C) and p CO 2 (500 and 985 μatm) from fertilisation to 25 days post hatching (dph). Temperature had the greatest effect on survival, growth and development. Survivorship was lower, but growth and morphological development were faster at 25°C, with surviving fish larger and more developed at 1, 11 and 21 dph. Elevated p CO 2 affected size at 1 dph, but not at 11 or 21 dph, and did not affect survival or morphological development. Elevated temperature and p CO 2 had opposing effects on swimming performance at 21 dph. Critical swimming speed ( U crit ) was increased by elevated temperature but reduced by elevated p CO 2 . Additionally, elevated temperature increased the proportion of individuals that responded to a startle stimulus, reduced latency to respond and increased maximum escape speed, potentially due to the more advanced developmental stage of juveniles at 25°C. By contrast, elevated p CO 2 reduced the distance moved and average speed in response to a startle stimulus. Our results show that higher temperature is likely to be the primary driver of global change impacts on kingfish early life history; however, elevated p CO 2 could affect critical aspects of swimming performance in this pelagic species. Our findings will help parameterise and structure fisheries population dynamics models and improve projections of impacts to large pelagic fishes under climate change scenarios to better inform adaptation and mitigation responses.

Neuromotor and cognitive responses of adults with autism spectrum disorder compared to neurotypical adults - Steven Morrison; Cortney N. Armitano; C. Teal Raffaele; Stephen I. Deutsch; Serina A. Neumann; Hope Caracci; Maria R. Urbano (Experimental Brain Research, 2018)

Risk of diabetes complications among those with diabetes receiving androgen deprivation therapy for localized prostate cancer - Marie C. Bradley; Yingjun Zhou; Andrew N. Freedman; Marianne Ulcickas Yood; Charles P. Quesenbery; Reina Haque; Stephen K. Van Den Eeden; Andrea E. Cassidy-Bushrow; David Aaronson; Arnold L. Potosky (Cancer Causes & Control, 2018)

The Presence of Hydraulic Barriers in Layered Snowpacks: TOUGH2 Simulations and Estimated Diversion Lengths - Ryan W. Webb; Steven R. Fassnacht; Michael N. Gooseff; Stephen W. Webb (Transport in Porous Media, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Decreasing sea ice conditions in western Hudson Bay and an increase in abundance of harbour seals (Phoca vitulina) in the Churchill River - Katie R. N. Florko; Warren Bernhardt; C-Jae C. Breiter; Steven H. Ferguson; Meagan Hainstock; Brent G. Young; Stephen D. Petersen (Polar Biology, 2018)

Rivers to reservoirs: hydrological drivers control reservoir function by affecting the abundance of submerged and floating macrophytes - Stephen D. Shivers; Stephen W. Golladay; Matthew N. Waters; Susan B. Wilde; Alan P. Covich (Hydrobiologia, 2018)

Temporal Changes in Seawater Carbonate Chemistry and Carbon Export from a Southern California Estuary - May-Linn Paulsen; Andreas J. Andersson; Lihini Aluwihare; Tyler Cyronak; Sydney D’Angelo; Charlie Davidson; Hany Elwany; Sarah N. Giddings; Heather N. Page; Magali Porrachia; Stephen Schroeter (Estuaries and Coasts, 2018)

The initial hours of post-excision light are critical for adventitious root regeneration from Arabidopsis thaliana (L.) Heynh. cotyledon explants - M. Blair Nameth; Travis L. Goron; Stephen J. Dinka; Adam D. Morris; Jenny English; Dorrett Lewis; Rosalinda Oro; Manish N. Raizada (In Vitro Cellular & Developmental Biology - Plant, 2018)

Multiple non-catalytic ADAMs are novel integrin α4 ligands - Lei Wang; Jason A. Hoggard; Erica D. Korleski; Gideon V. Long; Brandy C. Ree; Kenneth Hensley; Stephen R. Bond; Tyra G. Wolfsberg; JianMing Chen; Tonya N. Zeczycki; Lance C. Bridges (Molecular and Cellular Biochemistry, 2018)

Transport properties of olivine grain boundaries from electrical conductivity experiments - Anne Pommier; David L. Kohlstedt; Lars N. Hansen; Stephen Mackwell; Miki Tasaka; Florian Heidelbach; Kurt Leinenweber (Contributions to Mineralogy and Petrology, 2018)

A boundary current drives synchronous growth of marine fishes across tropical and temperate latitudes - Joyce J. L. Ong; Adam N. Rountrey; Bryan A. Black; Hoang Minh Nguyen; Peter G. Coulson; Stephen J. Newman; Corey B. Wakefield; Jessica J. Meeuwig; Mark G. Meekan (Global Change Biology, 2018)
Entrainment of growth patterns of multiple species to single climatic drivers can lower ecosystem resilience and increase the risk of species extinction during stressful climatic events. However, predictions of the effects of climate change on the productivity and dynamics of marine fishes are hampered by a lack of historical data on growth patterns. We use otolith biochronologies to show that the strength of a boundary current, modulated by the El Niño‐Southern Oscillation, accounted for almost half of the shared variance in annual growth patterns of five of six species of tropical and temperate marine fishes across 23° of latitude (3000 km) in Western Australia. Stronger flow during La Niña years drove increased growth of five species, whereas weaker flow during El Niño years reduced growth. Our work is the first to link the growth patterns of multiple fishes with a single oceanographic/climate phenomenon at large spatial scales and across multiple climate zones, habitat types, trophic levels and depth ranges. Extreme La Niña and El Niño events are predicted to occur more frequently in the future and these are likely to have implications for these vulnerable ecosystems, such as a limited capacity of the marine taxa to recover from stressful climatic events.

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Photodissolution of copper from resuspended coastal marine sediments - Stephen A. Skrabal; Alyssa M. McBurney; Linda A. Webb; G. Brooks Avery; Robert J. Kieber; Ralph N. Mead (Limnology and Oceanography, 2018)
Total dissolved Cu (TDCu) was photoproduced from suspensions of estuarine and coastal marine sediments from varied biogeochemical settings after exposure to the equivalent of 1 day of sunlight. Net photorelease (defined as the difference between mean light and dark concentrations) of TDCu occurred in 10 of 13 experiments and ranged from 1.1 nM to 11.8 nM (0.88–46.1 nmol Cu g −1 dry sediment). Photorelease was observed over environmentally relevant total suspended sediment concentrations ranging from 38 mg L −1 to 460 mg L −1 . The magnitude of photorelease was directly correlated to the 1 M HCl‐extractable Cu and Fe contents of sediments. Photoreleased Cu was likely associated with organic matter and/or Fe oxyhydroxides, both of which are photoreactive. Photoreleased TDCu persisted for at least 24 h after irradiation indicating that the Cu was not immediately scavenged back onto particles, most likely because it was stabilized by complexation with dissolved organic matter. Results of this study are important because a conservative estimate of the areal flux of TDCu from irradiation of a modest suspended sediment loading of 100 mg L −1 in the top 100 cm of a sunlit water column would be 460 nmol m −2 d −1 , which is comparable to or significantly larger than benthic and riverine fluxes of the metal in estuarine and coastal environments. These results suggest that photolytic fluxes are a significant yet previously unrecognized source of bioactive Cu to natural waters.

Modelling Marine Sediment Biogeochemistry: Current Knowledge Gaps, Challenges, and Some Methodological Advice for Advancement - Gennadi Lessin; Yuri Artioli; Elin Almroth-Rosell; Jerry C. Blackford; Andrew W. Dale; Ronnie N. Glud; Jack J. Middelburg; Roberto Pastres; Ana M. Queirós; Christophe Rabouille; Pierre Regnier; Karline Soetaert; et al. (Frontiers in Marine Science, 2018)

Coniella lustricola, a new species from submerged detritus - Daniel B. Raudabaugh; Teresa Iturriaga; Akiko Carver; Stephen Mondo; Jasmyn Pangilinan; Anna Lipzen; Guifen He; Mojgan Amirebrahimi; Igor V. Grigoriev; Andrew N. Miller (Mycological Progress, 2018)

The First Hop: Use of Beaufort Sea Deltas by Hatch-Year Semipalmated Sandpipers - Roy T. Churchwell; Steve Kendall; Stephen C. Brown; Arny L. Blanchard; Tuula E. Hollmen; Abby N. Powell (Estuaries and Coasts, 2018)

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Relationships of depressive behavior and sertraline treatment with walking speed and activity in older female nonhuman primates - Jamie N. Justice; Marnie G. Silverstein-Metzler; Beth Uberseder; Susan E. Appt; Thomas B. Clarkson; Thomas C. Register; Stephen B. Kritchevsky; Carol A. Shively (GeroScience, 2017)

Glutamine supplementation reduces markers of intestinal permeability during running in the heat in a dose-dependent manner - Jamie N. Pugh; Stephen Sage; Mark Hutson; Dominic A. Doran; Simon C. Fleming; Jamie Highton; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2017)
Purpose To examine the dose–response effects of acute glutamine supplementation on markers of gastrointestinal (GI) permeability, damage and, secondary, subjective symptoms of GI discomfort in response to running in the heat. Methods Ten recreationally active males completed a total of four exercise trials; a placebo trial and three glutamine trials at 0.25, 0.5 and 0.9 g kg −1 of fat-free mass (FFM) consumed 2 h before exercise. Each exercise trial consisted of a 60-min treadmill run at 70% of $$\dot {V}{{\text{O}}_{{\text{2max}}}}$$ V ˙ O 2max in an environmental chamber set at 30 °C. GI permeability was measured using ratio of lactulose to rhamnose (L:R) in serum. Plasma glutamine and intestinal fatty acid binding protein (I-FABP) concentrations were determined pre and post exercise. Subjective GI symptoms were assessed 45 min and 24 h post-exercise. Results Relative to placebo, L:R was likely lower following 0.25 g kg −1 (mean difference: − 0.023; ± 0.021) and 0.5 g kg −1 (− 0.019; ± 0.019) and very likely following 0.9 g kg − 1 (− 0.034; ± 0.024). GI symptoms were typically low and there was no effect of supplementation. Discussion Acute oral glutamine consumption attenuates GI permeability relative to placebo even at lower doses of 0.25 g kg −1 , although larger doses may be more effective. It remains unclear if this will lead to reductions in GI symptoms. Athletes competing in the heat may, therefore, benefit from acute glutamine supplementation prior to exercise in order to maintain gastrointestinal integrity.

Why are nitrogen‐fixing trees rare at higher compared to lower latitudes? - Duncan N. L. Menge; Sarah A. Batterman; Lars O. Hedin; Wenying Liao; Stephen W. Pacala; Benton N. Taylor (Ecology, 2017)
Symbiotic nitrogen (N) fixation provides a dominant source of new N to the terrestrial biosphere, yet in many cases the abundance of N‐fixing trees appears paradoxical. N‐fixing trees, which should be favored when N is limiting, are rare in higher latitude forests where N limitation is common, but are abundant in many lower latitude forests where N limitation is rare. Here, we develop a graphical and mathematical model to resolve the paradox. We use the model to demonstrate that N fixation is not necessarily cost effective under all degrees of N limitation, as intuition suggests. Rather, N fixation is only cost effective when N limitation is sufficiently severe. This general finding, specific versions of which have also emerged from other models, would explain sustained moderate N limitation because N‐fixing trees would either turn N fixation off or be outcompeted under moderate N limitation. From this finding, four general hypothesis classes emerge to resolve the apparent paradox of N limitation and N‐fixing tree abundance across latitude. The first hypothesis is that N limitation is less common at higher latitudes. This hypothesis contradicts prevailing evidence, so is unlikely, but the following three hypotheses all seem likely. The second hypothesis, which is new, is that even if N limitation is more common at higher latitudes, more severe N limitation might be more common at lower latitudes because of the capacity for higher N demand. Third, N fixation might be cost effective under milder N limitation at lower latitudes but only under more severe N limitation at higher latitudes. This third hypothesis class generalizes previous hypotheses and suggests new specific hypotheses. For example, greater trade‐offs between N fixation and N use efficiency, soil N uptake, or plant turnover at higher compared to lower latitudes would make N fixation cost effective only under more severe N limitation at higher latitudes. Fourth, N‐fixing trees might adjust N fixation more at lower than at higher latitudes. This framework provides new hypotheses to explain the latitudinal abundance distribution of N‐fixing trees, and also provides a new way to visualize them. Therefore, it can help explain the seemingly paradoxical persistence of N limitation in many higher latitude forests.

Phytochemical characterization and biological activity of secondary metabolites from three Limonium species - Anastassiya V. Gadetskaya; Shaymaa M. Mohamed; Amer H. Tarawneh; Nesma M. Mohamed; Guoyi Ma; Boris N. Ponomarev; Galiya E. Zhusupova; Charles L. Cantrell; Stephen J. Cutler; Samir A. Ross (Medicinal Chemistry Research, 2017)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Circadian rhythms vary over the growing season and correlate with fitness components - Matthew J. Rubin; Marcus T. Brock; Amanda M. Davis; Zachary M. German; Mary Knapp; Stephen M. Welch; Stacey L. Harmer; Julin N. Maloof; Seth J. Davis; Cynthia Weinig (Molecular Ecology, 2017)
Circadian clocks have evolved independently in all three domains of life, suggesting that internal mechanisms of time‐keeping are adaptive in contemporary populations. However, the performance consequences of either discrete or quantitative clock variation have rarely been tested in field settings. Clock sensitivity of diverse segregating lines to the environment remains uncharacterized as do the statistical genetic parameters that determine evolutionary potential. In field studies with Arabidopsis thaliana , we found that major perturbations to circadian cycle length (referred to as clock period) via mutation reduce both survival and fecundity. Subtler adjustments via genomic introgression of naturally occurring alleles indicated that clock periods slightly >24 hr were adaptive, consistent with prior models describing how well the timing of biological processes is adjusted within a diurnal cycle (referred to as phase). In segregating recombinant inbred lines ( RIL s), circadian phase varied up to 2 hr across months of the growing season, and both period and phase expressed significant genetic variances. Performance metrics including developmental rate, size and fruit set were described by principal components ( PC ) analyses and circadian parameters correlated with the first PC , such that period lengths slightly >24 hr were associated with improved performance in multiple RIL sets. These experiments translate functional analyses of clock behaviour performed in controlled settings to natural ones, demonstrating that quantitative variation in circadian phase is highly responsive to seasonally variable abiotic factors. The results expand upon prior studies in controlled settings, showing that discrete and quantitative variation in clock phenotypes correlates with performance in nature.

Typology of Nonindustrial Private Forest Landowners and Forestry Behavior: Implications for Forest Carbon Sequestration in the Southern US - Puskar N. Khanal; Donald L. Grebner; Ian A. Munn; Stephen C. Grado; Robert K. Grala; James E. Henderson (Small-scale Forestry, 2017)

Systemic Inflammation during the First Postnatal Month and the Risk of Attention Deficit Hyperactivity Disorder Characteristics among 10 year-old Children Born Extremely Preterm - Elizabeth N. Allred; Olaf Dammann; Raina N. Fichorova; Stephen R Hooper; Scott J Hunter; Robert M. Joseph; Karl Kuban; Alan Leviton; Thomas Michael O’Shea; Megan N. Scott (Journal of Neuroimmune Pharmacology, 2017)

The Adaptive Evolution Database (TAED): A New Release of a Database of Phylogenetically Indexed Gene Families from Chordates - Russell A. Hermansen; Benjamin P. Oswald; Stormy Knight; Stephen D. Shank; David Northover; Katharine L. Korunes; Stephen N. Michel; David A. Liberles (Journal of Molecular Evolution, 2017)

Pyramid Screening: Combining Three Genetic Screens into One Efficient Screen for Shoot Regeneration Mutants in Arabidopsis thaliana - May Quach Mason; Travis L. Goron; Ewa Dziewiecka Arnold; Patricia Dickinson; Arani Kajenthira; Stephen J. Dinka; Rosalinda Oro; Manish N. Raizada (Journal of Plant Growth Regulation, 2017)

Loss of developmental pluripotency occurs in two stages during leaf aging in Arabidopsis thaliana - Manish N. Raizada; Travis L. Goron; Ovik Bannerjee; May Quach Mason; Michael Pautler; Jan Brazolot; Adam D. Morris; Arani Kajenthira; Stephen J. Dinka; Natalie DiMeo (In Vitro Cellular & Developmental Biology - Plant, 2017)

Soil influences on plant growth, floral density and nectar yield in three cultivars of mānuka ( Leptospermum scoparium ) - Elizabeth M. Nickless; Christopher W. N. Anderson; Georgie Hamilton; Jonathan M. Stephens; Jason Wargent (New Zealand Journal of Botany, 2017)
Honey derived from the nectar of Leptospermum scoparium J.R. et G. Forst. Myrtaceae (mānuka) is a high‐value product and there is considerable potential for economic growth in honey‐growing regions of New Zealand through increased nectar yield from mānuka plantations. Leptospermum scoparium exhibits a significant amount of phenotypic plasticity throughout regions in New Zealand where it has established, although the influences on this plasticity are unknown. When assessing L. scoparium as a nectar source for honey in marginal land areas, the possible effect of soil on nectar chemistry and yield should be considered. We investigated whether phenological patterns of flowering, plant growth, nectar composition and nectar yield were influenced by soil composition. Three different cultivars of L. scoparium were grown on 10 different soils in glasshouse conditions. The soils chosen were representative of the range of New Zealand soils where mānuka is being considered as a commercial crop for the honey industry. ANOVA and general linear models revealed no significant effect of soils on nectar composition or production; however, significant but complex interactions between cultivars and soils influenced plant growth and flowering ( P ≤ 0.05). Accordingly, the overall nectar yield was influenced by cultivar and soil interaction. Measured attributes of the soil such as cation exchange capacity, sulphate, iron, manganese, calcium and chloride were shown to influence the plant parameters assessed. Results allowed modelling of nectar potential against each soil type and established a mānuka soil index to determine the most appropriate soil for each cultivar. The results indicated that potential nectar yield increases will be dependent on cultivars being deployed according to the nature of the soil present. Furthermore, the mānuka cultivars displayed significantly greater growth in response to increased nutrients and some cultivars increased floral density, suggesting potential to improve nectar yield by greater plant growth using targeted fertilisation.

Signatures of invasion: using an integrative approach to infer the spread of melon fly, Zeugodacus cucurbitae (Diptera: Tephritidae), across Southeast Asia and the West Pacific - Yuvarin Boontop; Mark K. Schutze; Anthony R. Clarke; Stephen L. Cameron; Matt N. Krosch (Biological Invasions, 2017)

Cross-continent comparisons reveal differing environmental drivers of growth of the coral reef fish, Lutjanus bohar - Joyce J. L. Ong; Adam N. Rountrey; Ross J. Marriott; Stephen J. Newman; Jessica J. Meeuwig; Mark G. Meekan (Coral Reefs, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Progress in Prediction and Interpretation of Clinically Relevant Metabolic Drug-Drug Interactions: a Minireview Illustrating Recent Developments and Current Opportunities - Stephen Fowler; Peter N. Morcos; Yumi Cleary; Meret Martin-Facklam; Neil Parrott; Michael Gertz; Li Yu (Current Pharmacology Reports, 2017)

Dynamic Interactions among Boundaries and the Expansion of Sustainable Aquaculture - Bernardo R. Broitman; Benjamin S. Halpern; Stefan Gelcich; Marco A. Lardies; Cristian A. Vargas; Felipe Vásquez-Lavín; Stephen Widdicombe; Silvana N. R. Birchenough (Frontiers in Marine Science, 2017)

A comparison of accuracy of fall detection algorithms (threshold-based vs. machine learning) using waist-mounted tri-axial accelerometer signals from a comprehensive set of falls and non-fall trials - Omar Aziz; Magnus Musngi; Edward J. Park; Greg Mori; Stephen N. Robinovitch (Medical & Biological Engineering & Computing, 2017)

Emergence of white pine needle damage in the northeastern United States is associated with changes in pathogen pressure in response to climate change - Stephen A. Wyka; Cheryl Smith; Isabel A. Munck; Barrett N. Rock; Beth L. Ziniti; Kirk Broders (Global Change Biology, 2017)
The defoliation of the eastern white pine ( Pinus strobus ) across the northeastern United States is an escalating concern threatening the ecological health of northern forests and economic vitality of the region's lumber industry. First documented in the spring of 2010 affecting 24 328 hectares in the state of Maine, white pine needle damage ( WPND ) has continued to spread and is now well established in all New England states. While causal agents of WPND are known, current research is lacking in both sampling distribution and the specific environmental factor(s) that affect the development and spread of this disease complex. This study aims to construct a more detailed distribution map of the four primary causal agents within the region, as well as utilize long‐term WPND monitoring plots and data collected from land‐based weather stations to develop a climatic model to predict the severity of defoliation events in the proceeding year. Sampling results showed a greater distribution of WPND than previously reported. WPND was generally found in forest stands that compromised >50% eastern white pine by basal area. No single species, nor a specific combination of species had a dominating presence in particular states or regions, thus supporting the disease complex theory that WPND is neither caused by an individual species nor by a specific combination of species. In addition, regional weather data confirmed the trend of increasing temperature and precipitation observed in this region with the previous year's May, June, and July rainfall being the best predictor of defoliation events in the following year. Climatic models were developed to aid land managers in predicting disease severity and accordingly adjust their management decisions. Our results clearly demonstrate the role changing climate patterns have on the health of eastern white pine in the northeastern United States.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Multiple rare variants in high-risk pancreatic cancer-related genes may increase risk for pancreatic cancer in a subset of patients with and without germline CDKN2A mutations - Xiaohong R. Yang; Melissa Rotunno; Yanzi Xiao; Christian Ingvar; Hildur Helgadottir; Lorenza Pastorino; Remco van Doorn; Hunter Bennett; Cole Graham; Joshua N. Sampson; Michael Malasky; Aurelie Vogt; et al. (Human Genetics, 2016)

Fornix deep brain stimulation enhances acetylcholine levels in the hippocampus - Sarah Hescham; Ali Jahanshahi; Judith V. Schweimer; Stephen N. Mitchell; Guy Carter; Arjan Blokland; Trevor Sharp; Yasin Temel (Brain Structure and Function, 2016)

Comparing Occupational Health and Safety Management System Programming with Injury Rates in Poultry Production - Daniel A. Autenrieth; William J. Brazile; David I. Douphrate; Ivette N. Román-Muñiz; Stephen J. Reynolds (Journal of Agromedicine, 2016)

Repeated exposure reduces the response to impulsive noise in European seabass - Andrew N. Radford; Laurie Lèbre; Gilles Lecaillon; Sophie L. Nedelec; Stephen D. Simpson (Global Change Biology, 2016)
Human activities have changed the acoustic environment of many terrestrial and aquatic ecosystems around the globe. Mounting evidence indicates that the resulting anthropogenic noise can impact the behaviour and physiology of at least some species in a range of taxa. However, the majority of experimental studies have considered only immediate responses to single, relatively short‐term noise events. Repeated exposure to noise could lead to a heightened or lessened response. Here, we conduct two long‐term (12 week), laboratory‐based exposure experiments with European seabass ( Dicentrarchus labrax ) to examine how an initial impact of different sound types potentially changes over time. Naïve fish showed elevated ventilation rates, indicating heightened stress, in response to impulsive additional noise (playbacks of recordings of pile‐driving and seismic surveys), but not to a more continuous additional noise source (playbacks of recordings of ship passes). However, fish exposed to playbacks of pile‐driving or seismic noise for 12 weeks no longer responded with an elevated ventilation rate to the same noise type. Fish exposed long‐term to playback of pile‐driving noise also no longer responded to short‐term playback of seismic noise. The lessened response after repeated exposure, likely driven by increased tolerance or a change in hearing threshold, helps explain why fish that experienced 12 weeks of impulsive noise showed no differences in stress, growth or mortality compared to those reared with exposure to ambient‐noise playback. Considering how responses to anthropogenic noise change with repeated exposure is important both when assessing likely fitness consequences and the need for mitigation measures.

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Evidence for climate‐driven synchrony of marine and terrestrial ecosystems in northwest Australia - Joyce J.L. Ong; Adam N. Rountrey; Jens Zinke; Jessica J. Meeuwig; Pauline F. Grierson; Alison J. O'Donnell; Stephen J. Newman; Janice M. Lough; Mélissa Trougan; Mark G. Meekan (Global Change Biology, 2016)
The effects of climate change are difficult to predict for many marine species because little is known of their response to climate variations in the past. However, long‐term chronologies of growth, a variable that integrates multiple physical and biological factors, are now available for several marine taxa. These allow us to search for climate‐driven synchrony in growth across multiple taxa and ecosystems, identifying the key processes driving biological responses at very large spatial scales. We hypothesized that in northwest ( NW ) Australia, a region that is predicted to be strongly influenced by climate change, the El Niño Southern Oscillation ( ENSO ) phenomenon would be an important factor influencing the growth patterns of organisms in both marine and terrestrial environments. To test this idea, we analyzed existing growth chronologies of the marine fish Lutjanus argentimaculatus , the coral Porites spp. and the tree Callitris columellaris and developed a new chronology for another marine fish, Lethrinus nebulosus . Principal components analysis and linear model selection showed evidence of ENSO ‐driven synchrony in growth among all four taxa at interannual time scales, the first such result for the Southern Hemisphere. Rainfall, sea surface temperatures, and sea surface salinities, which are linked to the ENSO system, influenced the annual growth of fishes, trees, and corals. All four taxa had negative relationships with the Niño‐4 index (a measure of ENSO status), with positive growth patterns occurring during strong La Niña years. This finding implies that future changes in the strength and frequency of ENSO events are likely to have major consequences for both marine and terrestrial taxa. Strong similarities in the growth patterns of fish and trees offer the possibility of using tree‐ring chronologies, which span longer time periods than those of fish, to aid understanding of both historical and future responses of fish populations to climate variation.

QTL and major genes influencing grain yield potential in soft red winter wheat adapted to the southern United States - Christopher K. Addison; R. Esten Mason; Gina Brown-Guedira; Mohammed Guedira; Yuanfeng Hao; Randall G. Miller; Nithya Subramanian; Dennis N. Lozada; Andrea Acuna; Maria N. Arguello; Jerry W. Johnson; Amir M. H. Ibrahim; et al. (Euphytica, 2016)

Kisspeptin signaling in the amygdala modulates reproductive hormone secretion - Alexander N. Comninos; Jelena Anastasovska; Meliz Sahuri-Arisoylu; Xiaofeng Li; Shengyun Li; Minghan Hu; Channa N. Jayasena; Mohammad A. Ghatei; Stephen R. Bloom; Paul M. Matthews; Kevin T. O’Byrne; Jimmy D. Bell; et al. (Brain Structure and Function, 2016)

Effects of Salinity and Inundation on Microbial Community Structure and Function in a Mangrove Peat Soil - Lisa G. Chambers; Rafael Guevara; Joseph N. Boyer; Tiffany G. Troxler; Stephen E. Davis (Wetlands, 2016)

Role of Nrf2 and Autophagy in Acute Lung Injury - Montserrat Rojo de la Vega; Matthew Dodson; Christine Gross; Heidi M. Mansour; R. Clark Lantz; Eli Chapman; Ting Wang; Stephen M. Black; Joe G. N. Garcia; Donna D. Zhang (Current Pharmacology Reports, 2016)

Corrigendum - Danielle Stephens; Alan N. Wilton; Peter J. S. Fleming; Oliver Berry (Molecular Ecology, 2016)

Farm gate level nitrogen balance and use efficiency changes post implementation of the EU Nitrates Directive - Cathal Buckley; David P. Wall; Brian Moran; Stephen O’Neill; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2016)

Controlling for hydrologic connectivity to assess the importance of catchment- and reach-scale factors on macroinvertebrate community structure - Alison N. Hale; Grace Noble; Kaitlin Piper; Keith Garmire; Stephen J. Tonsor (Hydrobiologia, 2016)

Erratum to: Will climate change increase or decrease suicide rates? The differing effects of geographical, seasonal, and irregular variation in temperature on suicide incidence - Matt N. Williams; Stephen R. Hill; John Spicer (Climatic Change, 2016)

Effects of urbanization on herbaceous forest vegetation: the relative impacts of soil, geography, forest composition, human access, and an invasive shrub - Guy N. Cameron; Theresa M. Culley; Sarah E. Kolbe; Arnold I. Miller; Stephen F. Matter (Urban Ecosystems, 2015)

Targeted demersal fish species exhibit variable responses to long-term protection from fishing at the Houtman Abrolhos Islands - Katrina R. Bornt; Dianne L. McLean; Tim J. Langlois; Euan S. Harvey; Lynda M. Bellchambers; Scott N. Evans; Stephen J. Newman (Coral Reefs, 2015)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Death by sex in an Australian icon: a continent‐wide survey reveals extensive hybridization between dingoes and domestic dogs - Danielle Stephens; Alan N. Wilton; Peter J.S. Fleming; Oliver Berry (Molecular Ecology, 2015)
Hybridization between domesticated animals and their wild counterparts can disrupt adaptive gene combinations, reduce genetic diversity, extinguish wild populations and change ecosystem function. The dingo is a free‐ranging dog that is an iconic apex predator and distributed throughout most of mainland Australia. Dingoes readily hybridize with domestic dogs, and in many Australian jurisdictions, distinct management strategies are dictated by hybrid status. Yet, the magnitude and spatial extent of domestic dog–dingo hybridization is poorly characterized. To address this, we performed a continent‐wide analysis of hybridization throughout Australia based on 24 locus microsatellite DNA genotypes from 3637 free‐ranging dogs. Although 46% of all free‐ranging dogs were classified as pure dingoes, all regions exhibited some hybridization, and the magnitude varied substantially. The southeast of Australia was highly admixed, with 99% of animals being hybrids or feral domestic dogs, whereas only 13% of the animals from remote central Australia were hybrids. Almost all free‐ranging dogs had some dingo ancestry, indicating that domestic dogs could have poor survivorship in nonurban Australian environments. Overall, wild pure dingoes remain the dominant predator over most of Australia, but the speed and extent to which hybridization has occurred in the approximately 220 years since the first introduction of domestic dogs indicate that the process may soon threaten the persistence of pure dingoes.

The relationship between temperature and assault in New Zealand - Matt N. Williams; Stephen R. Hill; John Spicer (Climatic Change, 2015)

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Three-Dimensional Morphometrics for Quantitative Trait Locus Analysis: Tackling Complex Questions with Complex Phenotypes - Heather A. Jamniczky; Stephen Campeau; Tegan N. Barry; Jase Skelton; Sean M. Rogers (Evolutionary Biology, 2015)

Erratum to: The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

Genomic deletions and mutations resulting in the loss of eight genes reduce the in vivo replication capacity of Meleagrid herpesvirus 1 - Timothy J. Mahony; Robyn N. Hall; Stephen Walkden-Brown; Joanne Meers; Jennifer L. Gravel; Lani West; Vanessa Hardy; A.F.M. Fakhrul Islam; Elizabeth V. Fowler; Neena Mitter (Virus Genes, 2015)

Field Observations of Canopy Flows over Complex Terrain - Eleanor R. Grant; Andrew N. Ross; Barry A. Gardiner; Stephen D. Mobbs (Boundary-Layer Meteorology, 2015)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

A multiproxy (micro‐XRF, pollen, chironomid and stable isotope) lake sediment record for the Lateglacial to Holocene transition from Thomastown Bog, Ireland - JONATHAN N. TURNER; NAOMI HOLMES; STEPHEN R. DAVIS; MELANIE J. LENG; CATHERINE LANGDON; ROBERT G. SCAIFE (Journal of Quaternary Science, 2015)
A multiproxy Lateglacial environmental record is presented for a ca. 3.5‐m lacustrine sequence retrieved from a small basin (ca. 2 km 2 ) at Thomastown Bog in County Meath, Ireland. Sediment chemistry, pollen, chironomid and stable isotope data provide a detailed picture of catchment and lake system changes from the end of the last glacial (GS‐2a) to the early Holocene that correspond closely to existing local and regional models of climate change. Concomitant adjustments in independent proxy records are matched to the NGRIP oxygen isotope curve giving 12 event‐episodes ranging from major climatic shifts to lower amplitude, centennial‐ to sub‐centennial‐scale adjustments, including a previously unreported regressive period of landscape instability during the north‐west European ‘Rammelbeek Phase’. The study emphasizes the potential of palaeoenvironmental reconstruction from sediment chemistry where the sediment mixing system reflects autochthonous versus allochthonous inputs. The investigation also indicates problems of interpreting isotope data derived from bulk marl due to possible lag effects controlling the delivery of soil and groundwater and multiple sources of HCO 3– (aq.). These research findings have implications for core site selection and for studies attempting to use stable isotopes for correlation purposes.

Microarthropod communities of industrially disturbed or imported soils in the High Arctic; the abandoned coal mining town of Pyramiden, Svalbard - Stephen J. Coulson; Arne Fjellberg; Elena N. Melekhina; Anastasia A. Taskaeva; Natalia V. Lebedeva; Olga A. Belkina; Stanisław Seniczak; Anna Seniczak; Dariusz J. Gwiazdowicz (Biodiversity and Conservation, 2015)

Will climate change increase or decrease suicide rates? The differing effects of geographical, seasonal, and irregular variation in temperature on suicide incidence - Matt N. Williams; Stephen R. Hill; John Spicer (Climatic Change, 2015)

Managing tropical agroforestry for conservation of flocking migratory birds - Molly E. McDermott; Amanda D. Rodewald; Stephen N. Matthews (Agroforestry Systems, 2015)

The potential effects of river regulation and watershed land use on sediment characteristics and lake primary producers in a large reservoir - Matthew N. Waters; Stephen W. Golladay; Chase H. Patrick; Joseph M. Smoak; Stephen D. Shivers (Hydrobiologia, 2015)

Diversity and bioprospection of fungal community present in oligotrophic soil of continental Antarctica - Valéria M. Godinho; Vívian N. Gonçalves; Iara F. Santiago; Hebert M. Figueredo; Gislaine A. Vitoreli; Carlos E. G. R. Schaefer; Emerson C. Barbosa; Jaquelline G. Oliveira; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; Silvane M. F. Murta; et al. (Extremophiles, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Alleviating waiting impulsivity and perseverative responding by μ-opioid receptor antagonism in two inbred mouse strains - Sandra Sanchez-Roige; Tamzin L. Ripley; David N. Stephens (Psychopharmacology, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Estimating the normal background rate of species extinction - Jurriaan M. De Vos; Lucas N. Joppa; John L. Gittleman; Patrick R. Stephens; Stuart L. Pimm (Conservation Biology, 2015)
A key measure of humanity's global impact is by how much it has increased species extinction rates. Familiar statements are that these are 100–1000 times pre‐human or background extinction levels. Estimating recent rates is straightforward, but establishing a background rate for comparison is not. Previous researchers chose an approximate benchmark of 1 extinction per million species per year (E/MSY). We explored disparate lines of evidence that suggest a substantially lower estimate. Fossil data yield direct estimates of extinction rates, but they are temporally coarse, mostly limited to marine hard‐bodied taxa, and generally involve genera not species. Based on these data, typical background loss is 0.01 genera per million genera per year. Molecular phylogenies are available for more taxa and ecosystems, but it is debated whether they can be used to estimate separately speciation and extinction rates. We selected data to address known concerns and used them to determine median extinction estimates from statistical distributions of probable values for terrestrial plants and animals. We then created simulations to explore effects of violating model assumptions. Finally, we compiled estimates of diversification—the difference between speciation and extinction rates for different taxa. Median estimates of extinction rates ranged from 0.023 to 0.135 E/MSY. Simulation results suggested over‐ and under‐estimation of extinction from individual phylogenies partially canceled each other out when large sets of phylogenies were analyzed. There was no evidence for recent and widespread pre‐human overall declines in diversity. This implies that average extinction rates are less than average diversification rates. Median diversification rates were 0.05–0.2 new species per million species per year. On the basis of these results, we concluded that typical rates of background extinction may be closer to 0.1 E/MSY. Thus, current extinction rates are 1,000 times higher than natural background rates of extinction and future rates are likely to be 10,000 times higher. Estimación de la Tasa Normal de Extinción de Especies

Blood lipids and colorectal polyps: testing an etiologic hypothesis using phenotypic measurements and Mendelian randomization - Michael N. Passarelli; Polly A. Newcomb; Karen W. Makar; Andrea N. Burnett-Hartman; John D. Potter; Melissa P. Upton; Lee-Ching Zhu; Michael E. Rosenfeld; Stephen M. Schwartz; Carolyn M. Rutter (Cancer Causes & Control, 2015)

Anthropogenic noise compromises antipredator behaviour in European eels - Stephen D. Simpson; Julia Purser; Andrew N. Radford (Global Change Biology, 2015)
Increases in noise‐generating human activities since the Industrial Revolution have changed the acoustic landscape of many terrestrial and aquatic ecosystems. Anthropogenic noise is now recognized as a major pollutant of international concern, and recent studies have demonstrated impacts on, for instance, hearing thresholds, communication, movement and foraging in a range of species. However, consequences for survival and reproductive success are difficult to ascertain. Using a series of laboratory‐based experiments and an open‐water test with the same methodology, we show that acoustic disturbance can compromise antipredator behaviour – which directly affects survival likelihood – and explore potential underlying mechanisms. Juvenile European eels ( Anguilla anguilla ) exposed to additional noise (playback of recordings of ships passing through harbours), rather than control conditions (playback of recordings from the same harbours without ships), performed less well in two simulated predation paradigms. Eels were 50% less likely and 25% slower to startle to an ‘ambush predator’ and were caught more than twice as quickly by a ‘pursuit predator’. Furthermore, eels experiencing additional noise had diminished spatial performance and elevated ventilation and metabolic rates (indicators of stress) compared with control individuals. Our results suggest that acoustic disturbance could have important physiological and behavioural impacts on animals, compromising life‐or‐death responses.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Hyaluronan in aged collagen matrix increases prostate epithelial cell proliferation - Mamatha Damodarasamy; Robert B. Vernon; Christina K. Chan; Stephen R. Plymate; Thomas N. Wight; May J. Reed (In Vitro Cellular & Developmental Biology - Animal, 2015)

Changes in the integrity of thalamocortical connections are associated with sensorimotor deficits in children with congenital hemiplegia - Henry Tsao; Kerstin Pannek; Roslyn N. Boyd; Stephen E. Rose (Brain Structure and Function, 2015)

Erratum to: Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Plasma Cytokine Levels are Related to Brain Volumes in HIV-infected Individuals - Assawin Gongvatana; Stephen Correia; Shira Dunsiger; Lynne Gauthier; Kathryn N. Devlin; Skye Ross; Bradford Navia; Karen T. Tashima; Suzanne DeLaMonte; Ronald A. Cohen (Journal of Neuroimmune Pharmacology, 2014)

High prevalence of mismatch repair deficiency in prostate cancers diagnosed in mismatch repair gene mutation carriers from the colon cancer family registry - Christophe Rosty; Michael D. Walsh; Noralane M. Lindor; Stephen N. Thibodeau; Erin Mundt; Steven Gallinger; Melyssa Aronson; Aaron Pollett; John A. Baron; Sally Pearson; Mark Clendenning; Rhiannon J. Walters; et al. (Familial Cancer, 2014)

Using Strategic Foresight to Assess Conservation Opportunity - CARLY N. COOK; BONNIE C. WINTLE; STEPHEN C. ALDRICH; BRENDAN A. WINTLE (Conservation Biology, 2014)
The nature of conservation challenges can foster a reactive, rather than proactive approach to decision making. Failure to anticipate problems before they escalate results in the need for more costly and time‐consuming solutions. Proactive conservation requires forward‐looking approaches to decision making that consider possible futures without being overly constrained by the past. Strategic foresight provides a structured process for considering the most desirable future and for mapping the most efficient and effective approaches to promoting that future with tools that facilitate creative thinking. The process involves 6 steps: setting the scope, collecting inputs, analyzing signals, interpreting the information, determining how to act, and implementing the outcomes. Strategic foresight is ideal for seeking, recognizing, and realizing conservation opportunities because it explicitly encourages a broad‐minded, forward‐looking perspective on an issue. Despite its potential value, the foresight process is rarely used to address conservation issues, and previous attempts have generally failed to influence policy. We present the strategic foresight process as it can be used for proactive conservation planning, describing some of the key tools in the foresight tool kit and how they can be used to identify and exploit different types of conservation opportunities. Scanning is an important tool for collecting and organizing diverse streams of information and can be used to recognize new opportunities and those that could be created. Scenario planning explores how current trends, drivers of change, and key uncertainties might influence the future and can be used to identify barriers to opportunities. Backcasting is used to map out a path to a goal and can determine how to remove barriers to opportunities. We highlight how the foresight process was used to identify conservation opportunities during the development of a strategic plan to address climate change in New York State. The plan identified solutions that should be effective across a range of possible futures. Illustrating the application of strategic foresight to identify conservation opportunities should provide the impetus for decision makers to explore strategic foresight as a way to support more proactive conservation policy, planning, and management.

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

Individual and interactive effects of Amur honeysuckle (Lonicera maackii) and white-tailed deer (Odocoileus virginianus) on herbs in a deciduous forest in the eastern United States - Cory C. Christopher; Stephen F. Matter; Guy N. Cameron (Biological Invasions, 2014)

Huckleberry Gold: A Specialty Market Potato Cultivar with Purple-Skin, Yellow-Flesh, High Tuber Antioxidants, and Resistance to Potato Cyst Nematode (H1) and Potato virus X (Nb and Rx1) - Jonathan L. Whitworth; Richard G. Novy; Jeffrey C. Stark; Stephen L. Love; Michael K. Thornton; Brian A. Charlton; Solomon Yilma; N. Richard Knowles; Mark J. Pavek; Xiaohong Wang; Joseph J. Pavek (American Journal of Potato Research, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

A single codon insertion in PICALM is associated with development of familial subvalvular aortic stenosis in Newfoundland dogs - Joshua A. Stern; Stephen N. White; Linda B. Lehmkuhl; Yamir Reina-Doreste; Jordan L. Ferguson; Nanette M. Nascone-Yoder; Kathryn M. Meurs (Human Genetics, 2014)

Deletion of the GABAA α2-subunit does not alter self administration of cocaine or reinstatement of cocaine seeking - C. I. Dixon; B. Halbout; S. L. King; D. N. Stephens (Psychopharmacology, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Assessing changes in the distribution and range size of demersal fish populations in the Benguela Current Large Marine Ecosystem - Dawit Yemane; Stephen P. Kirkman; John Kathena; Silvi E. N’siangango; Bjørn Erik Axelsen; Toufiek Samaai (Reviews in Fish Biology and Fisheries, 2014)

Alpha-synuclein deletion decreases motor impulsivity but does not affect risky decision making in a mouse Gambling Task - Yolanda Peña-Oliver; Sandra Sanchez-Roige; David N. Stephens; Tamzin L. Ripley (Psychopharmacology, 2014)

Post-transcriptional regulation of ITGB6 protein levels in damaged skeletal muscle - Melissa Ducceschi; Lisa G. Clifton; Stephen A. Stimpson; Andrew N. Billin (Journal of Molecular Histology, 2014)

Fish assemblages across a vegetation gradient in a restoring tidal freshwater wetland: diets and potential for resource competition - Sarah N. Whitley; Stephen M. Bollens (Environmental Biology of Fishes, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Reduced lignin content and altered lignin composition in the warm season forage grass Paspalum dilatatum by down-regulation of a Cinnamoyl CoA Reductase Gene - Andrea Giordano; Zhiqian Liu; Stephen N. Panter; Adam M. Dimech; Yongjin Shang; Hewage Wijesinghe; Karen Fulgueras; Yidong Ran; Aidyn Mouradov; Simone Rochfort; Nicola J. Patron; German C. Spangenberg (Transgenic Research, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Cross-scale ensemble projections of dissolved organic carbon dynamics in boreal forest streams - Stephen K. Oni; Martyn N. Futter; Claudia Teutschbein; Hjalmar Laudon (Climate Dynamics, 2014)

Effectiveness of ecosystem-based approaches for adaptation: review of the evidence-base - N. Doswald; R. Munroe; D. Roe; A. Giuliani; I. Castelli; J. Stephens; I. Möller; T. Spencer; B. Vira; H. Reid (Climate and Development, 2014)

Amphetamine and cocaine suppress social play behavior in rats through distinct mechanisms - E. J. Marijke Achterberg; Viviana Trezza; Stephen M. Siviy; Laurens Schrama; Anton N. M. Schoffelmeer; Louk J. M. J. Vanderschuren (Psychopharmacology, 2014)

Biogeochemical effects of simulated sea level rise on carbon loss in an Everglades mangrove peat soil - Lisa G. Chambers; Stephen E. Davis; Tiffany Troxler; Joseph N. Boyer; Alan Downey-Wall; Leonard J. Scinto (Hydrobiologia, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

The tomato leaf miner (Tuta absoluta): Conventional pest problem, organic management solutions? - Anastasios N. Terzidis; Stephen Wilcockson; Carlo Leifert (Organic Agriculture, 2014)

Roots of the Invasive Species Carduus nutans L. and C. acanthoides L. Produce Large Amounts of Aplotaxene, a Possible Allelochemical - Ferdinando M. L. Silva; Mateus A. Donega; Antonio L. Cerdeira; Natália Corniani; Edivaldo D. Velini; Charles L. Cantrell; Franck E. Dayan; Mariana N. Coelho; Katriona Shea; Stephen O. Duke (Journal of Chemical Ecology, 2014)

A novel method based on combination of semi-in vitro and in vivo conditions in Agrobacterium rhizogenes-mediated hairy root transformation of Glycine species - Manijeh Mohammadi-Dehcheshmeh; Esmaeil Ebrahimie; Stephen D. Tyerman; Brent N. Kaiser (In Vitro Cellular & Developmental Biology - Plant, 2014)

Long‐term response of a Mojave Desert winter annual plant community to a whole‐ecosystem atmospheric CO 2 manipulation ( FACE ) - Stanley D. Smith; Therese N. Charlet; Stephen F. Zitzer; Scott R. Abella; Cheryl H. Vanier; Travis E. Huxman (Global Change Biology, 2014)
Desert annuals are a critically important component of desert communities and may be particularly responsive to increasing atmospheric ( CO 2 ) because of their high potential growth rates and flexible phenology. During the 10‐year life of the Nevada Desert FACE (free‐air CO 2 enrichment) Facility, we evaluated the productivity, reproductive allocation, and community structure of annuals in response to long‐term elevated ( CO 2 ) exposure. The dominant forb and grass species exhibited accelerated phenology, increased size, and higher reproduction at elevated ( CO 2 ) in a wet El Niño year near the beginning of the experiment. However, a multiyear dry cycle resulted in no increases in productivity or reproductive allocation for the remainder of the experiment. At the community level, early indications of increased dominance of the invasive Bromus rubens at elevated ( CO 2 ) gave way to an absence of Bromus in the community during a drought cycle, with a resurgence late in the experiment in response to higher rainfall and a corresponding high density of Bromus in a final soil seed bank analysis, particularly at elevated ( CO 2 ). This long‐term experiment resulted in two primary conclusions: (i) elevated ( CO 2 ) does not increase productivity of annuals in most years; and (ii) relative stimulation of invasive grasses will likely depend on future precipitation, with a wetter climate favoring invasive grasses but currently predicted greater aridity favoring native dicots.

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Involvement of facultative apomixis in inheritance of EPSPS gene amplification in glyphosate-resistant Amaranthus palmeri - Daniela N. Ribeiro; Zhiqiang Pan; Stephen O. Duke; Vijay K. Nandula; Brian S. Baldwin; David R. Shaw; Franck E. Dayan (Planta, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

A physiological analysis of color vision in batoid elasmobranchs - Christine N. Bedore; Ellis R. Loew; Tamara M. Frank; Robert E. Hueter; D. Michelle McComb; Stephen M. Kajiura (Journal of Comparative Physiology A, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Determining the heritability of ethanol-induced locomotor sensitization in mice using short-term behavioral selection - David N. Linsenbardt; Stephen L. Boehm (Psychopharmacology, 2013)

Detecting genomic clustering of risk variants from sequence data: cases versus controls - Daniel J. Schaid; Jason P. Sinnwell; Shannon K. McDonnell; Stephen N. Thibodeau (Human Genetics, 2013)

TMEM43 mutations associated with arrhythmogenic right ventricular cardiomyopathy in non-Newfoundland populations - Berivan Baskin; Jon R. Skinner; Shubhayan Sanatani; Deborah Terespolsky; Andrew D. Krahn; Peter N. Ray; Stephen W. Scherer; Robert M. Hamilton (Human Genetics, 2013)

Extent of linkage disequilibrium in large-breed dogs: chromosomal and breed variation - Joshua A. Stern; Stephen N. White; Kathryn M. Meurs (Mammalian Genome, 2013)

Epigenomic association analysis identifies smoking-related DNA methylation sites in African Americans - Yan V. Sun; Alicia K. Smith; Karen N. Conneely; Qiuzhi Chang; Weiyan Li; Alicia Lazarus; Jennifer A. Smith; Lynn M. Almli; Elisabeth B. Binder; Torsten Klengel; Dorthie Cross; Stephen T. Turner; et al. (Human Genetics, 2013)

Growth and Competition Response in Intensively Established Loblolly Pine Plantations at Crown Closure - Tamara N. Campbell; Phillip D. Jones; Andrew W. Ezell; Stephen Demarais (Journal of Forestry, 2013)

Detection of large scale 3′ deletions in the PMS2 gene amongst Colon-CFR participants: have we been missing anything? - Mark Clendenning; Michael D. Walsh; Judith Balmana Gelpi; Stephen N. Thibodeau; Noralane Lindor; John D. Potter; Polly Newcomb; Loic LeMarchand; Robert Haile; Steve Gallinger; John L. Hopper; Mark A. Jenkins; et al. (Familial Cancer, 2013)

Parapatric divergence of sympatric morphs in a salamander: incipient speciation on Long Island? - M. Caitlin Fisher‐Reid; Tag N. Engstrom; Caitlin A. Kuczynski; Patrick R. Stephens; John J. Wiens (Molecular Ecology, 2013)
Speciation is often categorized based on geographic modes (allopatric, parapatric or sympatric). Although it is widely accepted that species can arise in allopatry and then later become sympatrically or parapatrically distributed, patterns in the opposite direction are also theoretically possible (e.g. sympatric lineages or ecotypes becoming parapatric), but such patterns have not been shown at a macrogeographic scale. Here, we analyse genetic, climatic, ecological and morphological data and show that two typically sympatric colour morphs of the salamander Plethodon cinereus (redback and leadback) appear to have become parapatrically distributed on Long Island, New York, with pure‐redback populations in the west and pure‐leadback populations in the east (and polymorphic populations in between and on the mainland). In addition, the pure‐leadback populations in eastern Long Island are genetically, ecologically and morphologically divergent from both mainland and other Long Island populations, suggesting the possibility of incipient speciation. This parapatric separation seems to be related to the different ecological preferences of the two morphs, preferences which are present on the mainland and across Long Island. These results potentially support the idea that spatial segregation of sympatric ecotypes may sometimes play an important part in parapatric speciation.

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

Paths to selection on life history loci in different natural environments across the native range of A rabidopsis thaliana - Alexandre Fournier‐Level; Amity M. Wilczek; Martha D. Cooper; Judith L. Roe; Jillian Anderson; Deren Eaton; Brook T. Moyers; Renee H. Petipas; Robert N. Schaeffer; Bjorn Pieper; Matthieu Reymond; Maarten Koornneef; et al. (Molecular Ecology, 2013)
Selection on quantitative trait loci ( QTL ) may vary among natural environments due to differences in the genetic architecture of traits, environment‐specific allelic effects or changes in the direction and magnitude of selection on specific traits. To dissect the environmental differences in selection on life history QTL across climatic regions, we grew a panel of interconnected recombinant inbred lines ( RIL s) of Arabidopsis thaliana in four field sites across its native European range. For each environment, we mapped QTL for growth, reproductive timing and development. Several QTL were pleiotropic across environments, three colocalizing with known functional polymorphisms in flowering time genes ( CRY 2 , FRI and MAF 2‐5 ), but major QTL differed across field sites, showing conditional neutrality. We used structural equation models to trace selection paths from QTL to lifetime fitness in each environment. Only three QTL directly affected fruit number, measuring fitness. Most QTL had an indirect effect on fitness through their effect on bolting time or leaf length. Influence of life history traits on fitness differed dramatically across sites, resulting in different patterns of selection on reproductive timing and underlying QTL . In two oceanic field sites with high prereproductive mortality, QTL alleles contributing to early reproduction resulted in greater fruit production, conferring selective advantage, whereas alleles contributing to later reproduction resulted in larger size and higher fitness in a continental site. This demonstrates how environmental variation leads to change in both QTL effect sizes and direction of selection on traits, justifying the persistence of allelic polymorphism at life history QTL across the species range.

A report on six cases of seagrass‐associated gastric impaction in bottlenose dolphins ( Tursiops sp.) - E. Krzyszczyk; A. M. Kopps; K. Bacher; H. Smith; N. Stephens; N. A. Meighan; J. Mann (Marine Mammal Science, 2013)

Exploring tree species colonization potentials using a spatially explicit simulation model: implications for four oaks under climate change - Anantha M. Prasad; Judith D. Gardiner; Louis R. Iverson; Stephen N Matthews; Matthew Peters (Global Change Biology, 2013)
Climate change impacts tree species differentially by exerting unique pressures and altering their suitable habitats. We previously predicted these changes in suitable habitat for current and future climates using a species habitat model ( DISTRIB ) in the eastern United States. Based on the accuracy of the model, the species assemblages should eventually reflect the new quasi‐equilibrium suitable habitats (~2100) after accounting for the lag in colonization. However, it is an open question if and when these newly suitable habitats will be colonized under current fragmented landscapes and realistic migration rates. To evaluate this, we used a spatially explicit cell‐based model ( SHIFT ) that estimates colonization potentials under current fragmented habitats and several estimates of historical migration rates at a 1 km resolution. Computation time, which was previously the biggest constraint, was overcome by a novel application of convolution and Fast Fourier Transforms. SHIFT outputs, when intersected with future suitable habitats predicted by DISTRIB , allow assessment of colonization potential under future climates. In this article, we show how our approach can be used to screen multiple tree species for their colonization potentials under climate change. In particular, we use the DISTRIB and SHIFT models in combination to assess if the future dominant forest types in the north will really be dominated by oaks, as modelled via DISTRIB . Even under optimistic scenarios, we conclude that only a small fraction of the suitable habitats of oaks predicted by DISTRIB is likely to be occupied within 100 years, and this will be concentrated in the first 10–20 km from the current boundary. We also show how DISTRIB and SHIFT can be used to evaluate the potential for assisted migration of vulnerable tree species, and discuss the dynamics of colonization at range limits.

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Tracing the history and biogeography of the Australian blindsnake radiation - Julie Marin; Stephen C. Donnellan; S. Blair Hedges; Paul Doughty; Mark N. Hutchinson; Corinne Cruaud; Nicolas Vidal (Journal of Biogeography, 2013)
Aim We investigated the biogeographical history of Australian blindsnakes ( Ramphotyphlops ) with reference to Australia's palaeoclimatic history over the past 20 Myr, particularly the development of an extensive arid zone over this period. Terrestrial vertebrate lineages dating back to the Miocene or earlier are predicted to display some or all of the following patterns: (1) for taxa including mesic, arid and monsoonal representatives, a mesic distribution should be phylogenetically ancestral; (2) mesic and monsoon tropical lineages should have diverged before the onset of aridification (with arid lineages appearing later); and (3) refuges may have allowed local persistence and diversification of lineages in the monsoon tropical and mesic zones since the mid‐Miocene. Location Continental Australia. Methods We compiled a molecular data set comprising one mitochondrial and three nuclear genes for 107 individuals belonging to 28 blindsnake species. Phylogenetic relationships were reconstructed using maximum likelihood and Bayesian inference with RA x ML and MrBayes , respectively. Divergence times were assessed using multidivtime . Ancestral habitat states (arid and non arid) were reconstructed using the maximum likelihood method implemented in Mesquite . Results The age of the Australian Ramphotyphlops radiation was estimated at 21.9 Ma (95% credibility interval: 30.2–15.1 Ma). Mesic and monsoon tropical lineages are older than the onset of aridification, with mesic distribution appearing as ancestral on phylogenies. After the onset of aridification, lineages persisted and diversified in mesic, tropical and/or rocky refugia. Arid lineages diversified more recently ( Main conclusions Australian blindsnakes join several other Australian squamate lineages with tropical‐mesic origins that successfully adapted to the expansion of aridity since the mid‐Miocene ( c . 17 Ma) and now show evidence of multiple relatively recent evolutionary radiations across Australia. We further demonstrate that localized refugia permitted persistence and diversification of mesic taxa, with arid lineages diversifying much later (

Genetic variants associated with VLDL, LDL and HDL particle size differ with race/ethnicity - Alexis C. Frazier-Wood; Ani Manichaikul; Stella Aslibekyan; Ingrid B. Borecki; David C. Goff; Paul N. Hopkins; Chao-Qiang Lai; Jose M. Ordovas; Wendy S. Post; Stephen S. Rich; Michèle M. Sale; David Siscovick; et al. (Human Genetics, 2013)

The 1815 Tambora ash fall: implications for transport and deposition of distal ash on land and in the deep sea - Jessica Kandlbauer; Steven N. Carey; R. Stephen J. Sparks (Bulletin of Volcanology, 2013)

Antioxidant properties and chemical constituents of ethanolic extract and its fractions of Ocimum gratissimum - Xilin Ouyang; Liuxin Wei; Yingming Pan; Shiwen Huang; Hengshan Wang; Gregorio B. Begonia; Stephen I. N. Ekunwe (Medicinal Chemistry Research, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Development of microsatellite loci for the western slimy salamander (Plethodon albagula) using 454 sequencing - Brett N. Spatola; William E. Peterman; Nathan T. Stephens; Grant M. Connette; Donald B. Shepard; Kenneth H. Kozak; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

Effects of 17α-trenbolone and melengestrol acetate on Xenopus laevis growth, development, and survival - Bryson E. Finch; Brett R. Blackwell; Derek R. Faust; Kimberly J. Wooten; Jonathan D. Maul; Stephen B. Cox; Philip N. Smith (Environmental Science and Pollution Research, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Introduction of invertebrates into the High Arctic via imported soils: the case of Barentsburg in the Svalbard - Stephen J. Coulson; Arne Fjellberg; Dariusz J. Gwiazdowicz; Natalia V. Lebedeva; Elena N. Melekhina; Torstein Solhøy; Christer Erséus; Kristine Maraldo; Ladislav Miko; Heinrich Schatz; Rüdiger M. Schmelz; Geir Søli; et al. (Biological Invasions, 2013)

Breeding together: modeling synchrony in productivity in a seabird community - José J. Lahoz-Monfort; Byron J. T. Morgan; Michael P. Harris; Francis Daunt; Sarah Wanless; Stephen N. Freeman (Ecology, 2013)
With environmental conditions changing rapidly, there is a need to move beyond single‐species models and consider how communities respond to environmental drivers. We present a modeling approach that allows estimation of multispecies synchrony in productivity, or its components, and the contribution of environmental covariates as synchronizing and desynchronizing agents. We apply the model to long‐term breeding success data for five seabird species at a North Atlantic colony. Our Bayesian analysis reveals varying degrees of synchrony in overall productivity, with a common signal indicating a significant decline in productivity between 1986 and 2009. Productivity in seabirds reflects conditions in the marine ecosystem so the estimated synchronous component is a useful indicator of local marine environment health. For the two species for which we have most data, the environmental contribution to overall productivity synchrony is driven principally by effects operating at the chick stage rather than during incubation. Our results emphasize the importance of studying together species that coexist in a community. The framework, which accommodates interspecific clutch‐size variation, is readily applicable to any species assemblage in any ecosystem where long‐term productivity data are available.

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Epidemiology and potential associated risk factors of drug-related problems in hospitalised children in the United Kingdom and Saudi Arabia - Asia N. Rashed; Antje Neubert; Stephen Tomlin; John Jackman; Hani Alhamdan; Adnan AlShaikh; Ahmed Attar; Mohammed Aseeri; Lynda Wilton; Ian C. K. Wong (European Journal of Clinical Pharmacology, 2012)

Multiple jejunal cancers resulting from combination of germline APC and MLH1 mutations - Noralane M. Lindor; Tom C. Smyrk; Sheila Buehler; Shanaka R. Gunawardena; Brittany C. Thomas; Paul Limburg; Salman Kirmani; Stephen N. Thibodeau (Familial Cancer, 2012)

Prevalence of bovine tuberculosis in slaughter cattle in Kenya: a postmortem, microbiological and DNA molecular study - Stephen M. Gathogo; Joseph K. N. Kuria; Jackson N. Ombui (Tropical Animal Health and Production, 2012)

Species traits as predictors for intrinsic sensitivity of aquatic invertebrates to the insecticide chlorpyrifos - Mascha N. Rubach; Donald J. Baird; Marie-Claire Boerwinkel; Stephen J. Maund; Ivo Roessink; Paul J. Van den Brink (Ecotoxicology, 2012)

Effects of the organophosphate fenthion for control of the red-billed quelea Quelea quelea on cholinesterase and haemoglobin concentrations in the blood of target and non-target birds - Robert A. Cheke; Andrew N. McWilliam; Collen Mbereki; Etienne van der Walt; Boaz Mtobesya; Richard N. Magoma; Stephen Young; J. Patrick Eberly (Ecotoxicology, 2012)

Securing the Demographic and Genetic Future of Tuatara through Assisted Colonization - KIMBERLY A. MILLER; HILARY C. MILLER; JENNIFER A. MOORE; NICOLA J. MITCHELL; ALISON CREE; FRED W. ALLENDORF; STEPHEN D. SARRE; SUSAN N. KEALL; NICOLA J. NELSON (Conservation Biology, 2012)
Climate change poses a particular threat to species with fragmented distributions and little or no capacity to migrate. Assisted colonization, moving species into regions where they have not previously occurred, aims to establish populations where they are expected to survive as climatic envelopes shift. However, adaptation to the source environment may affect whether species successfully establish in new regions. Assisted colonization has spurred debate among conservation biologists and ecologists over whether the potential benefits to the threatened species outweigh the potential disruption to recipient communities. In our opinion, the debate has been distracted by controversial examples, rather than cases where assisted colonization may be a viable strategy. We present a strategic plan for the assisted migration of tuatara ( Sphenodon punctatus ), an endemic New Zealand reptile. The plan includes use of extant populations as reference points for comparisons with assisted‐colonization populations with respect to demography, phenotypic plasticity, and phenology; optimization of genetic variation; research to fill knowledge gaps; consideration of host and recipient communities; and inclusion of stakeholders in the planning stage. When strategically planned and monitored, assisted colonization could meet conservation and research goals and ultimately result in the establishment of long‐term sustainable populations capable of persisting during rapid changes in climate.

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

“Modeling the impact of natural resource-based poverty traps on food security in Kenya: The Crops, Livestock and Soils in Smallholder Economic Systems (CLASSES) model” - Emma C. Stephens; Charles F. Nicholson; Douglas R. Brown; David Parsons; Christopher B. Barrett; Johannes Lehmann; David Mbugua; Solomon Ngoze; Alice N. Pell; Susan J. Riha (Food Security, 2012)

Development of risk matrices for evaluating climatic change responses of forested habitats - Louis R. Iverson; Stephen N. Matthews; Anantha M. Prasad; Matthew P. Peters; Gary Yohe (Climatic Change, 2012)

A splice site mutation in a gene encoding for PDK4, a mitochondrial protein, is associated with the development of dilated cardiomyopathy in the Doberman pinscher - Kathryn M. Meurs; Sunshine Lahmers; Bruce W. Keene; Stephen N. White; Mark A. Oyama; Evan Mauceli; Kerstin Lindblad-Toh (Human Genetics, 2012)

Construction of black (Rubus occidentalis) and red (R. idaeus) raspberry linkage maps and their comparison to the genomes of strawberry, apple, and peach - J. M. Bushakra; M. J. Stephens; A. N. Atmadjaja; K. S. Lewers; V. V. Symonds; J. A. Udall; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Fish body condition and recruitment success reflect antecedent flows in an Australian dryland river - Stephen R. Balcombe; Jaye S. Lobegeiger; Sharon M. Marshall; Jonathan C. Marshall; Diana Ly; Darryl N. Jones (Fisheries Science, 2012)

Risk factors associated with adverse drug reactions in hospitalised children: international multicentre study - Asia N. Rashed; Ian C. K. Wong; Noel Cranswick; Stephen Tomlin; Wolfgang Rascher; Antje Neubert (European Journal of Clinical Pharmacology, 2012)

Agrobacterium-mediated transformation of the medicinal plant Centaurea montana - Wissam A. Abou-Alaiwi; Shobha D. Potlakayala; Stephen L. Goldman; Puthiyaparambil C. Josekutty; Deepkamal N. Karelia; Sairam V. Rudrabhatla (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Acoustic levitation: recent developments and emerging opportunities in biomaterials research - Richard J. K. Weber; Chris J. Benmore; Sonia K. Tumber; Amit N. Tailor; Charles A. Rey; Lynne S. Taylor; Stephen R. Byrn (European Biophysics Journal, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Matrix population models from 20 studies of perennial plant populations - Martha M. Ellis; Jennifer L. Williams; Peter Lesica; Timothy J. Bell; Paulette Bierzychudek; Marlin Bowles; Elizabeth E. Crone; Daniel F. Doak; Johan Ehrlén; Albertine Ellis-Adam; Kathryn McEachern; Rengaian Ganesan; et al. (Ecology, 2012)
Demographic transition matrices are among the most commonly applied population models for both basic and applied ecological research. The relatively simple framework of these models and simple, easily interpretable summary statistics they produce have prompted the wide use of these models across an exceptionally broad range of taxa. Here, we provide annual transition matrices and observed stage structures/population sizes for 20 perennial plant species which have been the focal species for long‐term demographic monitoring. These data were assembled as part of the “Testing Matrix Models” working group through the National Center for Ecological Analysis and Synthesis (NCEAS). The data represent 82 populations with >460 total population‐years of observations. It is our hope that making these data available will help promote and improve our ability to monitor and understand plant population dynamics. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Frontogenesis and Frontal Progression of a Trapping-Generated Estuarine Convergence Front and Its Influence on Mixing and Stratification - Sarah N. Giddings; Derek A. Fong; Stephen G. Monismith; C. Chris Chickadel; Kathleen A. Edwards; William J. Plant; Bing Wang; Oliver B. Fringer; Alexander R. Horner-Devine; Andrew T. Jessup (Estuaries and Coasts, 2012)

Functional haplotypes of Fc gamma (Fcγ) receptor (FcγRIIA and FcγRIIIB) predict risk to repeated episodes of severe malarial anemia and mortality in Kenyan children - Collins Ouma; Gregory C. Davenport; Steven Garcia; Prakasha Kempaiah; Ateefa Chaudhary; Tom Were; Samuel B. Anyona; Evans Raballah; Stephen N. Konah; James B. Hittner; John M. Vulule; John M. Ong’echa; et al. (Human Genetics, 2012)

Quantifying changes in abundance without counting animals: extensions to a method of fitting integrated population models - Stephen N. Freeman; Panagiotis Besbeas (Journal of Ornithology, 2012)

Measuring impulsivity in mice: the five-choice serial reaction time task - Sandra Sanchez-Roige; Yolanda Peña-Oliver; David N. Stephens (Psychopharmacology, 2012)

Prednisolone treatment reduces endometrial spiral artery development in women with recurrent miscarriage - Gendie E. Lash; Judith N. Bulmer; Barbara A. Innes; Josephine A. Drury; Stephen C. Robson; Siobhan Quenby (Angiogenesis, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Shadow detection and building-height estimation using IKONOS data - Yang Shao; Gregory N. Taff; Stephen J. Walsh (International Journal of Remote Sensing, 2011)

Does a bout of strength training affect 2,000 m rowing ergometer performance and rowing-specific maximal power 24 h later? - Thomas I. Gee; Duncan N. French; Glyn Howatson; Stephen J. Payton; Nicolas J. Berger; Kevin G. Thompson (European Journal of Applied Physiology, 2011)

Learning not to be impulsive: disruption by experience of alcohol withdrawal - Sophie E. Walker; Yolanda Peña-Oliver; David N. Stephens (Psychopharmacology, 2011)

Clinical contributors to cerebral white matter integrity in HIV-infected individuals - Assawin Gongvatana; Ronald A. Cohen; Stephen Correia; Kathryn N. Devlin; Jadrian Miles; Hakmook Kang; Hernando Ombao; Bradford Navia; David H. Laidlaw; Karen T. Tashima (Journal of NeuroVirology, 2011)

Lessons Learned While Integrating Habitat, Dispersal, Disturbance, and Life-History Traits into Species Habitat Models Under Climate Change - Louis R. Iverson; Anantha M. Prasad; Stephen N. Matthews; Matthew P. Peters (Ecosystems, 2011)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Candida northwykensis sp. nov., A Novel Yeast Isolated from the Gut of the Click Beetle Melanotus villosus - Sreenivas Rao Ravella; Neil Donovan; Stephen A. James; Sisinthy Shivaji; Kotakonda Arunasri; Christopher J. Bond; Ian N. Roberts; Phil J. Hobbs (Current Microbiology, 2011)

Mice defective in p53 nuclear localization signal 1 exhibit exencephaly - Anouk Regeling; Heather L. Armata; Judy Gallant; Stephen N. Jones; Hayla K. Sluss (Transgenic Research, 2011)

Soil properties associated with net nitrification following watershed conversion from Appalachian hardwoods to Norway spruce - Charlene N. Kelly; Stephen H. Schoenholtz; Mary Beth Adams (Plant and Soil, 2011)

Scale-dependent selection of greenness by African elephants in the Kruger-private reserve transboundary region, South Africa - Jason P. Marshal; Azhar Rajah; Francesca Parrini; Michelle Henley; Stephen R. Henley; Barend F. N. Erasmus (European Journal of Wildlife Research, 2011)

Antioxidant activities and UV-protective properties of melanin from the berry of Cinnamomum burmannii and Osmanthus fragrans - Shiwen Huang; Yingming Pan; Dianhua Gan; Xilin Ouyang; Shaoqing Tang; Stephen I. N. Ekunwe; Hengshan Wang (Medicinal Chemistry Research, 2011)

Accumulation of Non-Transferrin-Bound Iron by Neurons, Astrocytes, and Microglia - Glenda M. Bishop; Theresa N. Dang; Ralf Dringen; Stephen R. Robinson (Neurotoxicity Research, 2011)

Restraint stress fails to modulate cutaneous hypersensitivity responses in mice lacking the adenosine A1 receptor - Stephen J. Oliver; Sneha Mathew; Tuère F. Wilder; Bruce N. Cronstein (Purinergic Signalling, 2011)

Effects of substitutions at position 180 in the Escherichia coli RNA polymerase σ70 subunit - Olga N Koroleva; Stephen JW Busby; Valeriy L Drutsa (Journal of Biosciences, 2011)

Germline PKHD1 mutations are protective against colorectal cancer - Christopher J. Ward; Yanhong Wu; Ruth A. Johnson; John R. Woollard; Eric J. Bergstralh; Mine S. Cicek; Jason Bakeberg; Sandro Rossetti; Christina M. Heyer; Gloria M. Petersen; Noralene M. Lindor; Stephen N. Thibodeau; et al. (Human Genetics, 2011)

The yin and yang of yeast: biodiversity research and systems biology as complementary forces driving innovation in biotechnology - Ian N. Roberts; Stephen G. Oliver (Biotechnology Letters, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Determining microsatellite genotyping reliability and mutation detection ability: an approach using small-pool PCR from sperm DNA - Anna J. MacDonald; Stephen D. Sarre; Nancy N. FitzSimmons; Nicola Aitken (Molecular Genetics and Genomics, 2011)

Genetic variation and structuring in the threatened koala populations of Southeast Queensland - Kristen E. Lee; Jennifer M. Seddon; Sean W. Corley; William A. H. Ellis; Stephen D. Johnston; Deidré L. de Villiers; Harriet J. Preece; Frank N. Carrick (Conservation Genetics, 2010)

Stock structure of Grey Mackerel, Scomberomorus semifasciatus (Pisces: Scombridae) across northern Australia, based on otolith stable isotope chemistry - Stephen J. Newman; Ian W. Wright; Ben M. Rome; Michael C. Mackie; Paul D. Lewis; Rik C. Buckworth; Aaron C. Ballagh; Rod N. Garrett; Jason Stapley; Damien Broderick; Jennifer R. Ovenden; David J. Welch (Environmental Biology of Fishes, 2010)

Spatial distribution of lead concentrations in urban surface soils of New Orleans, Louisiana USA - Michael T. Abel; Burton Suedel; Steven M. Presley; Thomas R. Rainwater; Galen P. Austin; Stephen B. Cox; Les N. McDaniel; Richard Rigdon; Timothy Goebel; Richard Zartman; Blair D. Leftwich; Todd A. Anderson; et al. (Environmental Geochemistry and Health, 2010)

Genome-wide association identifies a deletion in the 3′ untranslated region of Striatin in a canine model of arrhythmogenic right ventricular cardiomyopathy - Kathryn M. Meurs; Evan Mauceli; Sunshine Lahmers; Gregory M. Acland; Stephen N. White; Kerstin Lindblad-Toh (Human Genetics, 2010)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Characterization of microsatellite loci in the straw-colored fruit bat, Eidolon helvum (Pteropodidae) - Alison J. Peel; Stephen J. Rossiter; James L. N. Wood; Andrew A. Cunningham; David R. Sargan (Conservation Genetics Resources, 2010)

In-Street Wind Direction Variability in the Vicinity of a Busy Intersection in Central London - Ahmed A. Balogun; Alison S. Tomlin; Curtis R. Wood; Janet F. Barlow; Stephen E. Belcher; Robert J. Smalley; Justin J. N. Lingard; Sam J. Arnold; Adrian Dobre; Alan G. Robins; Damien Martin; Dudley E. Shallcross (Boundary-Layer Meteorology, 2010)

Feathers as bioindicators of PCB exposure in clapper rails - J. W. Summers; K. F. Gaines; N. Garvin; W. L. Stephens; J. C. Cumbee; G. L. Mills (Ecotoxicology, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Dynamics of genome evolution in facultative symbionts of aphids - Patrick H. Degnan; Teresa E. Leonardo; Bodil N. Cass; Bonnie Hurwitz; David Stern; Richard A. Gibbs; Stephen Richards; Nancy A. Moran (Environmental Microbiology, 2010)
Summary Aphids are sap‐feeding insects that host a range of bacterial endosymbionts including the obligate, nutritional mutualist Buchnera plus several bacteria that are not required for host survival. Among the latter, ‘ Candidatus Regiella insecticola’ and ‘ Candidatus Hamiltonella defensa’ are found in pea aphids and other hosts and have been shown to protect aphids from natural enemies. We have sequenced almost the entire genome of R. insecticola (2.07 Mbp) and compared it with the recently published genome of H. defensa (2.11 Mbp). Despite being sister species the two genomes are highly rearranged and the genomes only have ∼55% of genes in common. The functions encoded by the shared genes imply that the bacteria have similar metabolic capabilities, including only two essential amino acid biosynthetic pathways and active uptake mechanisms for the remaining eight, and similar capacities for host cell toxicity and invasion (type 3 secretion systems and RTX toxins). These observations, combined with high sequence divergence of orthologues, strongly suggest an ancient divergence after establishment of a symbiotic lifestyle. The divergence in gene sets and in genome architecture implies a history of rampant recombination and gene inactivation and the ongoing integration of mobile DNA (insertion sequence elements, prophage and plasmids).

Muscle activity differs with load compliance during fatiguing contractions with the knee extensor muscles - Thorsten Rudroff; Jamie N. Justice; Stephen Matthews; Rena Zuo; Roger M. Enoka (Experimental Brain Research, 2010)

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Differential Gene Expression During Smoltification of Atlantic Salmon (Salmo salar L.): a First Large-Scale Microarray Study - Paul J. Seear; Stephen N. Carmichael; Richard Talbot; John B. Taggart; James E. Bron; Glen E. Sweeney (Marine Biotechnology, 2010)

Comparison of defined culture systems for feeder cell free propagation of human embryonic stem cells - Veronika Akopian; Peter W. Andrews; Stephen Beil; Nissim Benvenisty; Jennifer Brehm; Megan Christie; Angela Ford; Victoria Fox; Paul J. Gokhale; Lyn Healy; Frida Holm; Outi Hovatta; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Tightly Regulated Expression Vectors for Ochrobactrum anthropi - Hamzeh Alqublan; Mohamed N. Seleem; Stephen M. Boyle; Nammalwar Sriranganathan (Current Microbiology, 2010)

Evaluation of Acid Leachable Trace Metals in Soils Around a Five Centuries Old Mining District in Hidalgo, Central Mexico - M. P. Jonathan; M. Jayaprakash; S. Srinivasalu; P. D. Roy; N. Thangadurai; S. Muthuraj; V. Stephen-Pitchaimani (Water, Air, & Soil Pollution, 2010)

Cryptococcus shivajii sp. nov.: A Novel Basidiomycetous Yeast Isolated from Biogas Reactor - Sreenivas Rao Ravella; Stephen A. James; Christopher J. Bond; Ian N. Roberts; Kathryn Cross; Andy Retter; Phil J. Hobbs (Current Microbiology, 2010)

Molecular characterization of global maize breeding germplasm based on genome-wide single nucleotide polymorphisms - Yanli Lu; Jianbing Yan; Claudia T. Guimarães; Suketoshi Taba; Zhuanfang Hao; Shibin Gao; Shaojiang Chen; Jiansheng Li; Shihuang Zhang; Bindiganavile S. Vivek; Cosmos Magorokosho; Stephen Mugo; et al. (Theoretical and Applied Genetics, 2009)

Comprehensive resequence analysis of a 97 kb region of chromosome 10q11.2 containing the MSMB gene associated with prostate cancer - Meredith Yeager; Zuoming Deng; Joseph Boland; Casey Matthews; Jennifer Bacior; Victor Lonsberry; Amy Hutchinson; Laura A. Burdett; Liqun Qi; Kevin B. Jacobs; Jesus Gonzalez-Bosquet; Sonja I. Berndt; et al. (Human Genetics, 2009)

Vascular and baroreceptor abnormalities in young males with a family history of hypertension - Yati N. Boutcher; Young J. Park; Stephen H. Boutcher (European Journal of Applied Physiology, 2009)

Epitope-positive truncating MLH1 mutation and loss of PMS2: implications for IHC-directed genetic testing for lynch syndrome - Israel Zighelboim; Matthew A. Powell; Sheri A. Babb; Alison J. Whelan; Amy P. Schmidt; Mark Clendenning; Leigha Senter; Stephen N. Thibodeau; Albert de la Chapelle; Paul J. Goodfellow (Familial Cancer, 2009)

Nodulation of Sesbania species by Rhizobium ( Agrobacterium ) strain IRBG74 and other rhizobia - Stephen P. Cummings; Prasad Gyaneshwar; Pablo Vinuesa; Frank T. Farruggia; Mitchell Andrews; David Humphry; Geoffrey N. Elliott; Andrew Nelson; Caroline Orr; Deborah Pettitt; Gopit R. Shah; Scott R. Santos; et al. (Environmental Microbiology, 2009)
Summary Concatenated sequence analysis with 16S rRNA, rpoB and fusA genes identified a bacterial strain (IRBG74) isolated from root nodules of the aquatic legume Sesbania cannabina as a close relative of the plant pathogen Rhizobium radiobacter (syn. Agrobacterium tumefaciens ). However, DNA:DNA hybridization with R. radiobacter , R. rubi , R. vitis and R. huautlense gave only 44%, 5%, 8% and 8% similarity respectively, suggesting that IRBG74 is potentially a new species. Additionally, it contained no vir genes and lacked tumour‐forming ability, but harboured a sym ‐plasmid containing nifH and nodA genes similar to those in other Sesbania symbionts. Indeed, IRBG74 effectively nodulated S. cannabina and seven other Sesbania spp. that nodulate with Ensifer ( Sinorhizobium )/ Rhizobium strains with similar nodA genes to IRBG74, but not species that nodulate with Azorhizobium or Mesorhizobium . Light and electron microscopy revealed that IRBG74 infected Sesbania spp. via lateral root junctions under flooded conditions, but via root hairs under non‐flooded conditions. Thus, IRBG74 is the first confirmed legume‐nodulating symbiont from the Rhizobium ( Agrobacterium ) clade. Cross‐inoculation studies with various Sesbania symbionts showed that S. cannabina could form fully effective symbioses with strains in the genera Rhizobium and Ensifer , only ineffective ones with Azorhizobium strains, and either partially effective ( Mesorhizobium huakii ) or ineffective ( Mesorhizobium plurifarium ) symbioses with Mesorhizobium . These data are discussed in terms of the molecular phylogeny of Sesbania and its symbionts.

Lymphocyte recruitment into the tumor site is altered in patients with MSI-H colon cancer - Kristen M. Drescher; Poonam Sharma; Patrice Watson; Zoran Gatalica; Stephen N. Thibodeau; Henry T. Lynch (Familial Cancer, 2009)

Ethanol effects on impulsivity in two mouse strains: similarities to diazepam and ketamine - Yolanda Peña Oliver; Tamzin L. Ripley; David N. Stephens (Psychopharmacology, 2009)

Characterization of equine and other vertebrate TLR3, TLR7, and TLR8 genes - Natalia M. Astakhova; Andrey A. Perelygin; Andrey A. Zharkikh; Teri L. Lear; Stephen J. Coleman; James N. MacLeod; Margo A. Brinton (Immunogenetics, 2009)

How Many Facets are Needed to Represent the Surface Energy Balance of an Urban Area? - Aurore Porson; Ian N. Harman; Sylvia I. Bohnenstengel; Stephen E. Belcher (Boundary-Layer Meteorology, 2009)

Assessing the abundance of freshwater turtles in an Australian urban landscape - Raymonde De Lathouder; Darryl N. Jones; Stephen R. Balcombe (Urban Ecosystems, 2009)

Imaging the Conditioned Behavioral Effects of Methamphetamine in Rodents - Joseph Carrion; Courtney N. B. Liebling; Corinne Reiszel; Reema Dalal; Stephen L. Dewey; Wynne K. Schiffer (Brain Imaging and Behavior, 2009)

Generation of large droplet aerosols within microbiological containment using a novel flow-focussing technique - Richard J. Thomas; Daniel Webber; William Sellors; Aaron Collinge; Andrew Frost; Anthony J. Stagg; Stephen C. Bailey; Pramukh N. Jayasekera; Rosa R. Taylor; Steve Eley; Richard W. Titball (Aerobiologia, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

The discriminative stimulus effects of dopamine D2- and D3-preferring agonists in rats - Mikhail N. Koffarnus; Benjamin Greedy; Stephen M. Husbands; Peter Grundt; Amy Hauck Newman; James H. Woods (Psychopharmacology, 2009)

Effect of Ions on Agitation- and Temperature-Induced Aggregation Reactions of Antibodies - R. Matthew Fesinmeyer; Sabine Hogan; Atul Saluja; Stephen R. Brych; Eva Kras; Linda O. Narhi; David N. Brems; Yatin R. Gokarn (Pharmaceutical Research, 2009)

Coccolithophores as palaeoecological indicators for shifts of the ITCZ in the Cariaco Basin during the late Quaternary - Kenneth N. J. M. Mertens; Matt Lynn; Mylene Aycard; Hui‐Ling Lin; Stephen Louwye (Journal of Quaternary Science, 2009)
Coccoliths were studied from the ODP Hole 1002C and core PL07‐39PC in the Cariaco Basin. Increases in Emiliania huxleyi are synchronous with decreases of Gephyrocapsa oceanica and vice versa. A new index (GEX) based on the relative abundances of these two taxa is proposed, and correlates with various other proxies. It is shown that GEX can serve as upwelling proxy. This confirms that the Intertropical Convergence Zone shifted north during the Bølling/Allerød, south during the Younger Dryas and back north during the Preboreal. The upwelling proxy shows few discrepancies with the terrigenous record. Copyright © 2008 John Wiley & Sons, Ltd.

Identification of Sex Pheromone Components of the Hessian Fly, Mayetiola destructor - Martin N. Andersson; Jenny Haftmann; Jeffrey J. Stuart; Sue E. Cambron; Marion O. Harris; Stephen P. Foster; Stephan Franke; Wittko Francke; Ylva Hillbur (Journal of Chemical Ecology, 2009)

Hydrological Impacts of Flood Storage and Management on Irrigation Water Abstraction in Upper Ewaso Ng’iro River Basin, Kenya - Stephen N. Ngigi; Hubert H. G. Savenije; Francis N. Gichuki (Water Resources Management, 2008)

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1 - Lynn M. Herrmann-Hoesing; Stephen N. White; Michelle R. Mousel; Gregory S. Lewis; Donald P. Knowles (Immunogenetics, 2008)

Epac activation, altered calcium homeostasis and ventricular arrhythmogenesis in the murine heart - Sandeep S. Hothi; Iman S. Gurung; Jennifer C. Heathcote; Yanmin Zhang; Stephen W. Booth; Jeremy N. Skepper; Andrew A. Grace; Christopher L.-H. Huang (Pflügers Archiv - European Journal of Physiology, 2008)

The July 2007 rock and ice avalanches at Mount Steele, St. Elias Mountains, Yukon, Canada - Panya S. Lipovsky; Stephen G. Evans; John J. Clague; Chris Hopkinson; Réjean Couture; Peter Bobrowsky; Göran Ekström; Michael N. Demuth; Keith B. Delaney; Nicholas J. Roberts; Garry Clarke; Andrew Schaeffer (Landslides, 2008)

Epipelic and pelagic primary production in Alaskan Arctic lakes of varying depth - Stephen C. Whalen; Brian A. Chalfant; Eric N. Fischer (Hydrobiologia, 2008)

Simple method for transformation of Ochrobactrum anthropi - Mohamed N. Seleem; Parthiban Rajasekaran; Mohammed Ali; Stephen M. Boyle; Nammalwar Sriranganathan (World Journal of Microbiology and Biotechnology, 2008)

Technical evaluation and development of low‐head drip irrigation systems in Kenya - Stephen N. Ngigi (Irrigation and Drainage, 2008)
Low‐head drip irrigation technology was recently introduced in Kenya. Imported drip systems are delicate to handle and require special maintenance. No guidelines regarding the optimum combination of lateral length, land slope and operating head were provided. To address the constraints, farmers appealed for technical assistance from research institutions. The objective of the present research was to address the farmers' challenges by evaluating existing low‐head drip irrigation systems to ascertain their performance in terms of water distribution/emission uniformity and to develop simple locally assembled drip irrigation kits. The research work focused on evaluation of emission uniformity and flow variation at different water supply heads, lateral lengths and land slopes. A number of the existing high‐head drip systems were evaluated under low‐head conditions with satisfactory results. Low‐head drip irrigation systems can be used effectively at 0.5–1.5 m water heads without compromising emission uniformity. Based on the technical evaluation, locally assembled drip irrigation systems “dream drip kits” were developed. The paper presents the methodology used for technical evaluation of different drip systems, results of the evaluation and a brief description of the design and development of locally assembled drip irrigation systems. Copyright © 2008 John Wiley & Sons, Ltd.

Surface Energy of Microcrystalline Cellulose Determined by Capillary Intrusion and Inverse Gas Chromatography - D. Fraser Steele; R. Christian Moreton; John N. Staniforth; Paul M. Young; Michael J. Tobyn; Stephen Edge (The AAPS Journal, 2008)

The trainability and contralateral response of cold-induced vasodilatation in the fingers following repeated cold exposure - Igor B. Mekjavic; Uroš Dobnikar; Stylianos N. Kounalakis; Bojan Musizza; Stephen S. Cheung (European Journal of Applied Physiology, 2008)

Sediment Organic Carbon in Todos Santos Bay, Baja California, Mexico - Stephen V. Smith; Silvia E. Ibarra-Obando; Victoria Díaz-Castañeda; Francisco Javier Aranda-Manteca; José D. Carriquiry; Brian N. Popp; Oscar Gonzalez-Yajimovich (Estuaries and Coasts, 2008)

Clapper rails as indicators of mercury and PCB bioavailability in a Georgia saltmarsh system - J. C. Cumbee; K. F. Gaines; G. L. Mills; N. Garvin; W. L. Stephens; J. M. Novak; I. L. Brisbin (Ecotoxicology, 2008)

Influences of climate on fire regimes in montane forests of north‐western Mexico - Carl N. Skinner; Jack H. Burk; Michael G. Barbour; Ernesto Franco‐Vizcaíno; Scott L. Stephens (Journal of Biogeography, 2008)
Aim To identify the influence of interannual and interdecadal climate variation on the occurrence and extent of fires in montane conifer forests of north‐western Mexico. Location This study was conducted in Jeffrey pine ( Pinus jeffreyi Grev. & Balf.)‐dominated mixed‐conifer forests in the central and northern plateau of the Sierra San Pedro Mártir, Baja California, Mexico. Methods Fire occurrence was reconstructed for 12 dispersed sites for a 290‐year period (1700–1990) from cross‐dated fire‐scarred samples extracted from live trees, snags and logs. Superposed epoch analysis was used to examine the relationships of tree‐ring reconstructions of drought, the El Niño/Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) with fire occurrence and extent. Results Years with no recorded fire scars were wetter than average. In contrast, years of widespread fires were dry and associated with phase changes of the PDO, usually from positive (warm) to negative (cold). The influence of the PDO was most evident during the La Niña phase of the ENSO. Widespread fires were also associated with warm/wet conditions 5 years before the fire. We hypothesize that the 5‐year lag between warm/wet conditions and widespread fires may be associated with the time necessary to build up sufficient quantity and continuity of needle litter to support widespread fires. Two periods of unusually high fire activity (1770–1800 and 1920–1950) were each followed by several decades of unusually low fire activity. The switch in each case was associated with strong phase changes in both PDO and ENSO. Main conclusions Climate strongly influences fire regimes in the mountains of north‐western Mexico. Wet/warm years are associated with little fire activity. However, these years may contribute to subsequent fire years by encouraging the production of sufficient needle litter to support more widespread fires that occur in dry/cool years.

Sensory gating and its modulation by cannabinoids: electrophysiological, computational and mathematical analysis - Margarita Zachariou; Dilshani W. N. Dissanayake; Stephen Coombes; Markus R. Owen; Robert Mason (Cognitive Neurodynamics, 2008)

Observations of herbivore attack on garlic mustard (Alliaria petiolata) in Southwestern Ontario, Canada - Colin N. Yates; Stephen D. Murphy (Biological Invasions, 2008)

The influence of diet on fatty acids in the egg yolk of green sea turtles, Chelonia mydas - Kathryn S. Craven; Joe Parsons; Stephen A. Taylor; Carolyn N. Belcher; David W. Owens (Journal of Comparative Physiology B, 2008)

Scaling environmental change through the community‐level: a trait‐based response‐and‐effect framework for plants - KATHARINE N. SUDING; SANDRA LAVOREL; F. S. CHAPIN; JOHANNES H. C. CORNELISSEN; SANDRA DÍAZ; ERIC GARNIER; DEBORAH GOLDBERG; DAVID U. HOOPER; STEPHEN T. JACKSON; MARIE‐LAURE NAVAS (Global Change Biology, 2008)
Predicting ecosystem responses to global change is a major challenge in ecology. A critical step in that challenge is to understand how changing environmental conditions influence processes across levels of ecological organization. While direct scaling from individual to ecosystem dynamics can lead to robust and mechanistic predictions, new approaches are needed to appropriately translate questions through the community level. Species invasion, loss, and turnover all necessitate this scaling through community processes, but predicting how such changes may influence ecosystem function is notoriously difficult. We suggest that community‐level dynamics can be incorporated into scaling predictions using a trait‐based response–effect framework that differentiates the community response to environmental change (predicted by response traits) and the effect of that change on ecosystem processes (predicted by effect traits). We develop a response‐and‐effect functional framework, concentrating on how the relationships among species' response, effect, and abundance can lead to general predictions concerning the magnitude and direction of the influence of environmental change on function. We then detail several key research directions needed to better scale the effects of environmental change through the community level. These include (1) effect and response trait characterization, (2) linkages between response‐and‐effect traits, (3) the importance of species interactions on trait expression, and (4) incorporation of feedbacks across multiple temporal scales. Increasing rates of extinction and invasion that are modifying communities worldwide make such a research agenda imperative.

Does context influence the duration of locomotor sensitization to ethanol in female DBA/2J mice? - Stephen L. Boehm; Karen J. Goldfarb; Kristen M. Serio; Eileen M. Moore; David N. Linsenbardt (Psychopharmacology, 2008)

Tom1l2 hypomorphic mice exhibit increased incidence of infections and tumors and abnormal immunologic response - Santhosh Girirajan; Paula M. Hauck; Stephen Williams; Christopher N. Vlangos; Barbara B. Szomju; Sara Solaymani-Kohal; Philip D. Mosier; Kimber L. White; Kathleen McCoy; Sarah H. Elsea (Mammalian Genome, 2008)

Automated postural responses are modified in a functional manner by instruction - Vivian Weerdesteyn; Andrew C. Laing; Stephen N. Robinovitch (Experimental Brain Research, 2008)

Genomic analysis of Ovis aries (Ovar) MHC class IIa loci - Lynn M. Herrmann-Hoesing; Stephen N. White; Lowell S. Kappmeyer; David R. Herndon; Donald P. Knowles (Immunogenetics, 2008)

Decomposition of Bt and Non-Bt Corn Hybrid Residues in the Field - David D. Tarkalson; Stephen D. Kachman; Johannes M. N. Knops; Janice E. Thies; Charles S. Wortmann (Nutrient Cycling in Agroecosystems, 2008)

Fine mapping of familial prostate cancer families narrows the interval for a susceptibility locus on chromosome 22q12.3 to 1.36 Mb - Bo Johanneson; Shannon K. McDonnell; Danielle M. Karyadi; Scott J. Hebbring; Liang Wang; Kerry Deutsch; Laura McIntosh; Erika M. Kwon; Miia Suuriniemi; Janet L. Stanford; Daniel J. Schaid; Elaine A. Ostrander; et al. (Human Genetics, 2008)

Measurement of particle concentrations in a dental office - Maria Sotiriou; Stephen F. Ferguson; Mark Davey; Jack M. Wolfson; Philip Demokritou; Joy Lawrence; Sonja N. Sax; Petros Koutrakis (Environmental Monitoring and Assessment, 2008)

Multivariate System Identification for Cerebral Autoregulation - Tingying Peng; Alexander B. Rowley; Philip N. Ainslie; Marc J. Poulin; Stephen J. Payne (Annals of Biomedical Engineering, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Serotonin transporter occupancy of high-dose selective serotonin reuptake inhibitors during major depressive disorder measured with [11C]DASB positron emission tomography - Aristotle N. Voineskos; Alan A. Wilson; Anahita Boovariwala; Sandra Sagrati; Sylvain Houle; Pablo Rusjan; Stephen Sokolov; Edgar P. Spencer; Nathalie Ginovart; Jeffrey H. Meyer (Psychopharmacology, 2007)

Approaches to resolving cephalopod movement and migration patterns - Jayson M. Semmens; Gretta T. Pecl; Bronwyn M. Gillanders; Claire M. Waluda; Elizabeth K. Shea; Didier Jouffre; Taro Ichii; Karsten Zumholz; Oleg N. Katugin; Stephen C. Leporati; Paul W. Shaw (Reviews in Fish Biology and Fisheries, 2007)

Establishment of facultative sexuals - Chris J. Paley; Sergei N. Taraskin; Stephen R. Elliott (The Science of Nature, 2007)

Hydrogeology of the Winnipeg Formation in Manitoba, Canada - Grant A. G. Ferguson; Robert N. Betcher; Stephen E. Grasby (Hydrogeology Journal, 2007)

Lysophosphatidylcholine induces inflammatory activation of human coronary artery smooth muscle cells - Nambi Aiyar; Jyoti Disa; Zhaohui Ao; Haisong Ju; Sandhya Nerurkar; Robert N. Willette; Colin H. Macphee; Douglas G. Johns; Stephen A. Douglas (Molecular and Cellular Biochemistry, 2007)

Plasma protein distribution and its impact on pharmacokinetics of liposomal amphotericin B in paediatric patients with malignant diseases - Ying Hong; Peter J. Shaw; Bruce N. Tattam; Christa E. Nath; John W. Earl; Katherine R. Stephen; Andrew J. McLachlan (European Journal of Clinical Pharmacology, 2007)

Molecular and genomic studies of IMMP2L and mutation screening in autism and Tourette syndrome - Erwin Petek; Thomas Schwarzbraun; Abdul Noor; Megha Patel; Kazuhiko Nakabayashi; Sanaa Choufani; Christian Windpassinger; Mara Stamenkovic; Mary M. Robertson; Harald N. Aschauer; Hugh M. D. Gurling; Peter M. Kroisel; et al. (Molecular Genetics and Genomics, 2007)

Factors affecting fertilization success in two species of patellid limpet (Mollusca: Gastropoda) and development of fertilization kinetics models - Alan N. Hodgson; Will J. F. Le Quesne; Stephen J. Hawkins; John D. D. Bishop (Marine Biology, 2007)

DNA banking for plant breeding, biotechnology and biodiversity evaluation - Trevor R. Hodkinson; Stephen Waldren; John A. N. Parnell; Colin T. Kelleher; Karine Salamin; Nicolas Salamin (Journal of Plant Research, 2007)

The impact of moderate daily alcohol consumption on aggression and the formation of dominance hierarchies in rats - Elizabeth A. Duncan; Kellie L. K. Tamashiro; Mary M. N. Nguyen; Stacy R. Gardner; Stephen C. Woods; Randall R. Sakai (Psychopharmacology, 2006)

An inverse agonist selective for α5 subunit-containing GABAA receptors improves encoding and recall but not consolidation in the Morris water maze - N. Collinson; J. R. Atack; P. Laughton; G. R. Dawson; D. N. Stephens (Psychopharmacology, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Identification of genetic variation and putative regulatory regions in bovine CARD15 - Kristen H. Taylor; Jeremy F. Taylor; Stephen N. White; James E. Womack (Mammalian Genome, 2006)

Removal of petroleum tar from bird feathers utilizing magnetic particles - Hien V. Dao; Lauren A. Maher; Lawrence N. Ngeh; Stephen W. Bigger; John D. Orbell; Margaret Healy; Rosalind Jessop; Peter Dann (Environmental Chemistry Letters, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Previous experience of ethanol withdrawal increases withdrawal-induced c-fos expression in limbic areas, but not withdrawal-induced anxiety and prevents withdrawal-induced elevations in plasma corticosterone - Gilyana G. Borlikova; Julie Le Merrer; David N. Stephens (Psychopharmacology, 2006)

Dimethylfuran-Lactone Pheromone from Males of Galerucella calmariensis and Galerucella pusilla - Robert J. Bartelt; Allard A. Cossé; Bruce W. Zilkowski; David Weisleder; Stephen H. Grode; Robert N. Wiedenmann; Susan L. Post (Journal of Chemical Ecology, 2006)

Comparative influence of resuspended glacial sediment on physicochemical characteristics and primary production in two arctic lakes - Stephen C. Whalen; Brian A. Chalfant; Eric N. Fischer; Kenneth A. Fortino; Anne E. Hershey (Aquatic Sciences, 2006)

Comparative influence of resuspended glacial sediment on physicochemical characteristics and primary production in two arctic lakes - Stephen C. Whalen; Brian A. Chalfant; Eric N. Fischer; Kenneth A. Fortino; Anne E. Hershey (Aquatic Sciences, 2006)

Reliability and Validity of an Assessment of Usual Phytoestrogen Consumption (United States) - Pamela L. Horn-Ross; Stephen Barnes; Valerie S. Lee; Christine N. Collins; Peggy Reynolds; Marion M. Lee; Susan L. Stewart; Alison J. Canchola; Landon Wilson; Kenneth Jones (Cancer Causes & Control, 2006)

Relating precipitation and water management to nutrient concentrations in the oligotrophic “upside‐down” estuaries of the Florida Everglades - Daniel L. Childers; Joseph N. Boyer; Stephen E. Davis; Christopher J. Madden; David T. Rudnick; Fred H. Sklar (Limnology and Oceanography, 2006)
We present 8 yr of long‐term water quality, climatological, and water management data for 17 locations in Everglades National Park, Florida. Total phosphorus (P) concentration data from freshwater sites (typically −1 , or 8 µg L −1 ) indicate the oligotrophic, P‐limited nature of this large freshwater—estuarine landscape. Total P concentrations at estuarine sites near the Gulf of Mexico (average ~0.5 µmol L −1 ) demonstrate the marine source for this limiting nutrient. This “upside down” phenomenon, with the limiting nutrient supplied by the ocean and not the land, is a defining characteristic of the Everglade landscape. We present a conceptual model of how the seasonality of precipitation and the management of canal water inputs control the marine P supply, and we hypothesize that seasonal variability in water residence time controls water quality through internal biogeochemical processing. Low freshwater inflows during the dry season increase estuarine residence times, enabling local processes to control nutrient availability and water quality. El Ni#x00F1;o—Southern Oscillation (ENSO) events tend to mute the seasonality of rainfall without altering total annual precipitation inputs. The Niño3 ENSO index (which indicates an ENSO event when positive and a La Niña event when negative) was positively correlated with both annual rainfall and the ratio of dry season to wet season precipitation. This ENSO‐driven disruption in seasonal rainfall patterns affected salinity patterns and tended to reduce marine inputs of P to Everglades estuaries. ENSO events also decreased dry season residence times, reducing the importance of estuarine nutrient processing. The combination of variable water management activities and interannual differences in precipitation patterns has a strong influence on nutrient and salinity patterns in Everglades estuaries.

Biochemical and molecular characterisation of the 2,3-dichloro-1-propanol dehalogenase and stereospecific haloalkanoic dehalogenases from a versatile Agrobacterium sp. - Timothy P. Higgins; Stephen J. Hope; Agus J. Effendi; Shula Dawson; Brian N. Dancer (Biodegradation, 2005)

Limb vasodilatory capacity and venous capacitance of trained runners and untrained males - Yati N. Boutcher; Stephen H. Boutcher (European Journal of Applied Physiology, 2005)

Use of Microsatellite Instability and Immunohistochemistry Testing for the Identification of Individuals at Risk for Lynch Syndrome - Linnea M. Baudhuin; Lawrence J. Burgart; Olga Leontovich; Stephen N. Thibodeau (Familial Cancer, 2005)

Biogeography of Dwarf Lemurs: Genetic Evidence for Unexpected Patterns in Southeastern Madagascar - Andreas Hapke; Joanna Fietz; Stephen D. Nash; Daniel Rakotondravony; Berthe Rakotosamimanana; Jean-Baptiste Ramanamanjato; Gisèle F. N. Randria; Hans Zischler (International Journal of Primatology, 2005)

Acute temperature dependency in the cleansing of tarry feathers utilizing magnetic particles - John D. Orbell; Hien Van Dao; Lawrence N. Ngeh; Stephen W. Bigger; Margaret Healy; Rosalind Jessop; Peter Dann (Environmental Chemistry Letters, 2005)

Trastuzumab and Liposomal Doxorubicin in the Treatment of MCF-7 Xenograft Tumor-Bearing Mice: Combination Does Not Affect Drug Serum Levels - Dawn N. Waterhouse; Tetyana Denyssevych; Norma Hudon; Stephen Chia; Karen A. Gelmon; Marcel B. Bally (Pharmaceutical Research, 2005)

The Seismic Project of the National Tsunami Hazard Mitigation Program - David H. Oppenheimer; Alex N. Bittenbinder; Barbara M. Bogaert; Raymond P. Buland; Lynn D. Dietz; Roger A. Hansen; Stephen D. Malone; Charles S. McCreery; Thomas J. Sokolowski; Paul M. Whitmore; Craig S. Weaver (Natural Hazards, 2005)

Effects of deletion of gria1 or gria2 genes encoding glutamatergic AMPA-receptor subunits on place preference conditioning in mice - Andy N. Mead; Geraldine Brown; Julie Le Merrer; David N. Stephens (Psychopharmacology, 2005)

Rates and controls on denitrification in an agricultural soil fertilized with liquid lagoonal swine waste - Eric N. Fischer; Stephen C. Whalen (Nutrient Cycling in Agroecosystems, 2005)

Monitoring perchlorate exposure and thyroid hormone status among raccoons inhabiting a perchlorate-contaminated site - Philip N. Smith; Sarah J. Utley; Stephen B. Cox; Todd A. Anderson; Scott T. McMurry (Environmental Monitoring and Assessment, 2005)

Scalar fluxes from urban street canyons. Part I: Laboratory simulation - Janet F. Barlow; Ian N. Harman; Stephen E. Belcher (Boundary-Layer Meteorology, 2004)

Scalar Fluxes from Urban Street Canyons Part II: Model - Ian N. Harman; Janet F. Barlow; Stephen E. Belcher (Boundary-Layer Meteorology, 2004)

Cyclic Pressure Affects the Biological Properties of Porcine Aortic Valve Leaflets in a Magnitude and Frequency Dependent Manner - Yun Xing; James N. Warnock; Zhaoming He; Stephen L. Hilbert; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2004)

Elevated CO 2 and herbivory influence trait integration in Arabidopsis thaliana - M. Gabriela Bidart‐Bouzat; Stephen Portnoy; Evan H. DeLucia; Ken N. Paige (Ecology Letters, 2004)
We lack information on how elevated CO 2 , and its interaction with other factors like herbivory, affect levels and patterns of trait integration in plants. We experimentally tested the hypothesis that elevated CO 2 disrupts and restructures functional associations among plant traits, in the selfing annual, Arabidopsis thaliana . We tested for these effects both in the presence and absence of herbivory by larvae of the diamondback moth, Plutella xylostella . Elevated CO 2 , both alone and combined with moth herbivory, modified integrated trait responses. In addition, integration under different environments was genotype‐specific. These results imply that global changes in CO 2 are likely to cause divergent evolutionary outcomes among populations of plants that differ in the initial structure of their quantitative genetic variation.

Discussion of “Tectonic controls of Mississippi Valley-type lead-zinc mineralization in orogenic forelands” by D.C. Bradley and D.L. Leach - Stephen E. Kesler; John T. Chesley; John N. Christensen; Richard D. Hagni; Wouter Heijlen; J. Richard Kyle; Phillipe Muchez; Kula C. Misra; Rob van der Voo (Mineralium Deposita, 2004)

The upper limit of physiological cardiac hypertrophy in elite male and female athletes: the British experience - G.P. Whyte; K. George; S. Sharma; S. Firoozi; N. Stephens; R. Senior; W.J. McKenna (European Journal of Applied Physiology, 2004)

Diversity and Productivity in Grassland Ecosystems - EMILY T. CLOYD; MELISSA S. LUCASH; NICOLE E. MUIR HOTALING; J. HOPE HORNBECK; HEATHER N. JENSEN; BYRON J. NORELIUS; STEPHEN H. REYNOLDS; JACOB D. WICKHAM (Conservation Biology, 2004)

Effects of Bridge Shading on Estuarine Marsh Benthic Invertebrate Community Structure and Function - Scott D. Struck; Christopher B. Craft; Stephen W. Broome; Michael D. Sanclements; John N. Sacco (Environmental Management, 2004)

Effects of Constant Static Pressure on the Biological Properties of Porcine Aortic Valve Leaflets - Yun Xing; Zhaoming He; James N. Warnock; Stephen L. Hilbert; Ajit. P. Yoganathan (Annals of Biomedical Engineering, 2004)

Urotensin-II: a novel systemic hypertensive factor in the cat - Kristeen Maniscalco; Gerald P. Stankus; Alexandra Wibberley; Robert N. Willette; Stephen A. Douglas; David J. Behm; Christopher P. A. Doe; Douglas G. Johns (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Nitrogen cycling in the soil–plant system along a precipitation gradient in the Kalahari sands - Julieta N. Aranibar; Luanne Otter; Stephen A. Macko; Chris J. W. Feral; Howard E. Epstein; Peter R. Dowty; Frank Eckardt; Herman H. Shugart; Robert J. Swap (Global Change Biology, 2004)
Nitrogen (N) cycling was analyzed in the Kalahari region of southern Africa, where a strong precipitation gradient (from 978 to 230 mm mean annual precipitation) is the main variable affecting vegetation. The region is underlain by a homogeneous soil substrate, the Kalahari sands, and provides the opportunity to analyze climate effects on nutrient cycling. Soil and plant N pools, 15 N natural abundance ( δ 15 N), and soil NO emissions were measured to indicate patterns of N cycling along a precipitation gradient. The importance of biogenic N 2 fixation associated with vascular plants was estimated with foliar δ 15 N and the basal area of leguminous plants. Soil and plant N was more 15 N enriched in arid than in humid areas, and the relation was steeper in samples collected during wet than during dry years. This indicates a strong effect of annual precipitation variability on N cycling. Soil organic carbon and C/N decreased with aridity, and soil N was influenced by plant functional types. Biogenic N 2 fixation associated with vascular plants was more important in humid areas. Nitrogen fixation associated with trees and shrubs was almost absent in arid areas, even though Mimosoideae species dominate. Soil NO emissions increased with temperature and moisture and were therefore estimated to be lower in drier areas. The isotopic pattern observed in the Kalahari ( 15 N enrichment with aridity) agrees with the lower soil organic matter, soil C/N, and N 2 fixation found in arid areas. However, the estimated NO emissions would cause an opposite pattern in δ 15 N, suggesting that other processes, such as internal recycling and ammonia volatilization, may also affect isotopic signatures. This study indicates that spatial, and mainly temporal, variability of precipitation play a key role on N cycling and isotopic signatures in the soil–plant system.

Radiative Exchange in an Urban Street Canyon - Ian N. Harman; Martin J. Best; Stephen E. Belcher (Boundary-Layer Meteorology, 2004)

A genome-wide search for allergic response (atopy) genes in three ethnic groups: Collaborative Study on the Genetics of Asthma - Malcolm N. Blumenthal; Carl D. Langefeld; Terri H. Beaty; Eugene R. Bleecker; Carole Ober; Lucille Lester; Ethan Lange; Kathleen C. Barnes; Raoul Wolf; Richard A. King; Julian Solway; William Oetting; et al. (Human Genetics, 2004)

The bovine 5? AMPK gene family: mapping and single nucleotide polymorphism detection - Raymond Loan; James E. Womack; Stephanie D. McKay; Stephen N. White; Srinivas R. Kata (Mammalian Genome, 2003)

The distribution of meteoric 36 Cl/Cl in the United States: a comparison of models - Stephen Moysey; Stanley N. Davis; Marek Zreda; L. DeWayne Cecil (Hydrogeology Journal, 2003)

Could the tyrosine-histidine ligand to CuB in cytochrome c oxidase be coordinatively labile? Implications from a quantum chemical model study of histidine substitutional lability and the effects of the covalent tyrosine-histidine cross-link - Stephen B. Colbran; Michael N. Paddon-Row (JBIC Journal of Biological Inorganic Chemistry, 2003)

Enhanced attention in rhesus monkeys as a common factor for the cognitive effects of drugs with abuse potential - John N. Bain; Mark A. Prendergast; Alvin V. Terry; Stephen P. Arneric; Mark A. Smith; Jerry J. Buccafusco (Psychopharmacology, 2003)

Laboratory Assessment of the Allelopathic Effects of Fine Leaf Fescues - Cecile Bertin; Rex N. Paul; Stephen O. Duke; Leslie A. Weston (Journal of Chemical Ecology, 2003)

Studies on high-temperature amination reactions of aromatic chlorides using discrete Palladium-N-Heterocyclic Carbene (NHC) complexes and in situ palladium/imidazolium salt protocols - Andrew J. McCarroll; David A. Sandham; Lisa R. Titcomb; Alexandra K. de K. Lewis; F. Geoffrey N. Cloke; Brian P. Davies; Alejandro Perez de Santana; Wolfgang Hiller; Stephen Caddick (Molecular Diversity, 2003)

Transgenic and tissue culture analyses of the muscle creatine kinase enhancer Trex control element in skeletal and cardiac muscle indicate differences in gene expression between muscle types - Quynh-Giao V. Nguyen; Jean N. Buskin; Charis L. Himeda; Christine Fabre-Suver; Stephen D. Hauschka (Transgenic Research, 2003)

Chlorine-36 in groundwater of the United States: empirical data - Stanley N. Davis; Stephen Moysey; DeWayne L. Cecil; Marek Zreda (Hydrogeology Journal, 2003)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Microbial impacts on plant-herbivore interactions: the indirect effects of a birch pathogen on a birch aphid - Scott N. Johnson; Angela E. Douglas; Stephen Woodward; Susan E. Hartley (Oecologia, 2003)

Comparative fine maps of bovine toll-like receptor 4 and toll-like receptor 2 regions - Stephen N. White; Srinivas R. Kata; James E. Womack (Mammalian Genome, 2003)

Neurofibromatosis type 1 gene as a mutational target in a mismatch repair-deficient cell type - Qing Wang; Gilles Montmain; Eric Ruano; Meena Upadhyaya; Sandra Dudley; Michael R. Liskay; Stephen N. Thibodeau; Alain Puisieux (Human Genetics, 2003)

Coping with Change: The Small Experiment as a Strategic Approach to Environmental Sustainability - KATHERINE N. IRVINE; STEPHEN KAPLAN (Environmental Management, 2001)

Assessment of Zn mobilization in the rhizosphere of Thlaspi caerulescens by bioassay with non-accumulator plants and soil extraction - Steven N. Whiting; Jonathan R. Leake; Stephen P. McGrath; Alan J.M. Baker (Plant and Soil, 2001)

Zinc accumulation by Thlaspi caerulescens from soils with different Zn availability: a pot study - Steven N. Whiting; Jonathan R. Leake; Stephen P. McGrath; Alan J. M. Baker (Plant and Soil, 2001)

Effects of seedling size, El Niño drought, seedling density, and distance to nearest conspecific adult on 6-year survival of Ocotea whitei seedlings in Panamá - Gregory S. Gilbert; Kyle E. Harms; David N. Hamill; Stephen P. Hubbell (Oecologia, 2001)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

A Mechanistic Model of Acute Platelet Accumulation in Thrombogenic Stenoses - David M. Wootton; Christos P. Markou; Stephen R. Hanson; David N. Ku (Annals of Biomedical Engineering, 2001)

Environmental vVariability and coccidioidomycosis (valley fever) - Korine N. Kolivras; Peter S. Johnson; Andrew C. Comrie; Stephen R. Yool (Aerobiologia, 2001)

Chemical Ecological Characteristics of Herbivory of Siparuna guianensis Seeds by Buffy-Headed Marmosets (Callithrix flaviceps) in the Atlantic Forest of Southeastern Brazil - Naomi K. Simas; Stephen F. Ferrari; Sonia N. Pereira; Gilda G. Leitão (Journal of Chemical Ecology, 2001)

Microsatellite Loci of the Cattle Tick Boophilus Microplus (Acari: Ixodidae) - Noel N. Chigagure; Glenn D. Baxter; Stephen C. Barker (Experimental and Applied Acarology, 2000)

Fast activation of a time-dependent outward current in protoplasts derived from coats of developing Phaseolus vulgaris seeds - Wen-Hao Zhang; N. Alan Walker; Stephen D. Tyerman; John W. Patrick (Planta, 2000)

Isolated supravalvular aortic stenosis: functional haploinsufficiency of the elastin gene as a result of nonsense-mediated decay - Zsolt Urbán; Virginia V. Michels; Stephen N. Thibodeau; Elaine C. Davis; Jean-Paul Bonnefont; Arnold Munnich; Benedicte Eyskens; Marc Gewillig; Koen Devriendt; Charles D. Boyd (Human Genetics, 2000)

Isolated supravalvular aortic stenosis: functional haploinsufficiency of the elastin gene as a result of nonsense-mediated decay - Zsolt Urbán; Virginia V. Michels; Stephen N. Thibodeau; Elaine C. Davis; Jean-Paul Bonnefont; Arnold Munnich; Benedicte Eyskens; Marc Gewillig; Koen Devriendt; Charles D. Boyd (Human Genetics, 2000)

Regional Patterns of Streamwater Acidity and Catchment Afforestation in Galloway, SW Scotland - Christoph B. Puhr; Daniel N. M. Donoghue; Alastair B. Stephen; David J. Tervet; Callum Sinclair (Water, Air, & Soil Pollution, 2000)

Cyclooxygenase-2 expression in colorectal cancer liver metastases - Mark A. Hull; Stephen W. Fenwick; Keith S. Chapple; N. Scott; Giles J. Toogood; J. Peter Lodge (Clinical & Experimental Metastasis, 2000)

Cationic Lipid-Mediated Transfection of Differentiated Caco-2 Cells: A Filter Culture Model of Gene Delivery to a Polarized Epithelium - Aimalohi N. Uduehi; Stephen H. Moss; Joanne Nuttall; Colin W. Pouton (Pharmaceutical Research, 1999)

An in vitro model of angiogenesis: Basic features - Eileen T. Bishop; Graham T. Bell; Stephen Bloor; I.J. Broom; Neil F.K. Hendry; Denys N. Wheatley (Angiogenesis, 1999)

Disparate phylogeographic patterns of molecular genetic variation in four closely related South American small cat species - Warren E. Johnson; Jill Pecon Slattery; Eduardo Eizirik; Jae‐Heup Kim; Marilyn Menotti Raymond; Cristian Bonacic; Richard Cambre; Peter Crawshaw; Adauto Nunes; Héctor N. Seuánez; Miguel Angelo Martins Moreira; Kevin L. Seymour; et al. (Molecular Ecology, 1999)
Tissue specimens from four species of Neotropical small cats ( Oncifelis geoffroyi , N = 38; O. guigna , N = 6; Leopardus tigrinus , N = 32; Lynchailurus colocolo , N = 22) collected from throughout their distribution were examined for patterns of DNA sequence variation using three mitochondrial genes, 16S rRNA, ATP8, and NADH‐5. Patterns between and among O. guigna and O. geoffroyi individuals were assessed further from size variation at 20 microsatellite loci. Phylogenetic analyses using mitochondrial DNA sequences revealed monophyletic clustering of the four species, plus evidence of natural hybridization between L. tigrinus and L. colocolo in areas of range overlap and discrete population subdivisions reflecting geographical isolation. Several commonly accepted subspecies partitions were affirmed for L. colocolo , but not for O. geoffroyi . The lack of geographical substructure in O. geoffroyi was recapitulated with the microsatellite data, as was the monophyletic clustering of O. guigna and O. geoffroyi individuals. L. tigrinus forms two phylogeographic clusters which correspond to L.t. oncilla (from Costa Rica) and L.t. guttula (from Brazil) and which have mitochondrial DNA (mtDNA) genetic distance estimates comparable to interspecific values between other ocelot lineage species. Using feline‐specific calibration rates for mitochondrial DNA mutation rates, we estimated that extant lineages of O. guigna diverged 0.4 million years ago (Ma), compared with 1.7 Ma for L. colocolo , 2.0 Ma for O. geoffroyi , and 3.7 Ma for L. tigrinus .

Dopamine-transporter occupancy after intravenous doses of cocaine and methylphenidate in mice and humans - S. J. Gatley; Nora D. Volkow; Andrew N. Gifford; Joanna S. Fowler; Stephen L. Dewey; Yu-Shin Ding; Jean Logan (Psychopharmacology, 1999)

A new class of proteins capable of binding transition metals - Philip E. Dykema; Philip R. Sipes; Anne Marie; Brenda J. Biermann; Dring N. Crowell; Stephen K. Randall (Plant Molecular Biology, 1999)

Biotic, abiotic and performance aspects of the Nevada Desert Free‐Air CO 2 Enrichment (FACE) Facility - DeaN. N. Jordan; Stephen F. Zitzer; George R. Hendrey; Keith F. Lewin; JohN. Nagy; Robert S. Nowak; Stanley D. Smith; James S. Coleman; Jeffrey R. Seemann (Global Change Biology, 1999)
Summary Arid and semiarid climates comprise roughly 40% of the earth’s terrestrial surface. Deserts are predicted to be extremely responsive to global change because they are stressful environments where small absolute changes in water availability or use represent large proportional changes. Water and carbon dioxide fluxes are inherently coupled in plant growth. No documented global change has been more substantial or more rapid than the increase in atmospheric CO 2 . Free Air CO 2 Enrichment (FACE) technology permits manipulation of CO 2 in intact communities without altering factors such as light intensity or quality, humidity or wind. The Nevada Desert FACE Facility (NDFF) consists of three 491 m 2 plots in the Mojave Desert receiving 550 μL L –1 CO 2 , and six ambient plots to assess both CO 2 and fan effects. The shrub community was characterized as a Larrea–Ambrosia–Lycium species complex. Data are reported through 12 months of operation.

Imbibition of white spruce seeds and somatic embryos: A study of morphological changes in an environmental scanning electron microscope and potassium leakage - Daryl A. Reid; John N. A. Lott; Stephen M. Attree; Larry C. Fowke (In Vitro Cellular & Developmental Biology - Plant, 1999)

Supravalvular aortic stenosis: a splice site mutation within the elastin gene results in reduced expression of two aberrantly spliced transcripts - Zsolt Urbán; Virginia V. Michels; Stephen N. Thibodeau; Helen Donis-Keller; Katalin Csiszár; C. D. Boyd (Human Genetics, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Molecular and functional characterization of s-KCNQ1 potassium channel from rectal gland of Squalus acanthias - Siegfried Waldegger; Bernd Fakler; Markus Bleich; Petra Barth; Anna Hopf; U. Schulte; Andreas E. Busch; Stephen G. Aller; John N. Forrest Jr.; Rainer Greger; Florian Lang (Pflügers Archiv - European Journal of Physiology, 1999)

A Phosphorus Budget for the Lake Mendota Watershed - Elena M. Bennett; Tara Reed-Andersen; Jeffrey N. Houser; John R. Gabriel; Stephen R. Carpenter (Ecosystems, 1999)

Evaluating Alternative Explanations in Ecosystem Experiments - Stephen R. Carpenter; Jonathan J. Cole; Timothy E. Essington; James R. Hodgson; Jeffrey N. Houser; James F. Kitchell; Michael L. Pace (Ecosystems, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

A Novel Method for Efficient Drug Delivery - Christos P. Markou; Elizabeth M. Lutostansky; David N. Ku; Stephen R. Hanson (Annals of Biomedical Engineering, 1998)

Analysis of the human Sonic Hedgehog coding and promoter regions in sacral agenesis, triphalangeal thumb, and mirror polydactyly - F. R. Vargas; E. Roessler; Karin Gaudenz; E. Belloni; Alexander S. Whitehead; Peader N. Kirke; James L. Mills; George Hooper; Roger E. Stevenson; Isabel Cordeiro; Patricia Correia; Temis Felix; et al. (Human Genetics, 1998)

Discriminative stimulus properties of low doses of ethanol in humans - T. Duka; D. N. Stephens; C. Russell; R. Tasker (Psychopharmacology, 1998)

Sensitisation to repeated withdrawal, in mice treated chronically with diazepam, is blocked by an NMDA receptor antagonist - S. J. Dunworth; D. N. Stephens (Psychopharmacology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

A comparative molecular analysis of four rat smooth muscle cell lines - Anthony B. Firulli; David Han; Louise Kelly-Roloff; Victor E. Koteliansky; Stephen M. Schwartz; Eric N. Olson; Joseph M. Miano (In Vitro Cellular & Developmental Biology - Animal, 1998)

Sensitisation of withdrawal signs following repeated withdrawal from a benzodiazepine: differences between measures of anxiety and seizure sensitivity - B. O. Ward; D. N. Stephens (Psychopharmacology, 1998)

Mapping sediment acoustic impedance using remote sensing acoustic techniques in a shallow-water carbonate environment - Donald J. Walter; Douglas N. Lambert; David C. Young; Kevin P. Stephens (Geo-Marine Letters, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Fever and production of cytokines in response to repeated injections of muramyl dipeptide in guinea-pigs - Joachim Roth; Stephen J. Hopkins; Margaret E. Hoadley; Anke Tripp; Tunai Aslan; Birgit Störr; Giamal N. Luheshi; E. Zeisberger (Pflügers Archiv - European Journal of Physiology, 1997)

Behavioral phenotypes of inbred mouse strains: implications and recommendations for molecular studies - J. N. Crawley; John K. Belknap; Allan Collins; John C. Crabbe; Wayne Frankel; Norman Henderson; Robert J. Hitzemann; Stephen C. Maxson; Lucinda L. Miner; Alcino J. Silva; Jeanne M. Wehner; Anthony Wynshaw-Boris; et al. (Psychopharmacology, 1997)

Isolation and Characterization of an Acetylated Impurity in Escherichia coli-Derived Recombinant Human Interleukin-10 (IL-10) Drug Substance - Mollie N. Pflumm; Stephen C. Gruber; Anthony Tsarbopoulos; David Wylie; Birendra Pramanik; James N. Bausch; Suman T. Patel (Pharmaceutical Research, 1997)

Phenotypic and genotypic stability of multiple lines of transgenic pigs expressing recombinant human protein C - Kevin E. Van Cott; Henryk Lubon; Christopher G. Russell; Stephen P. Butler; F.C. Gwazdauskas; James Knight; William N. Drohan; William H. Velander (Transgenic Research, 1997)

Distribution of contact force during impact to the hip - Stephen N. Robinovitch; Wilson C. Hayes; Thomas A. McMahon (Annals of Biomedical Engineering, 1997)

Restoring Ecosystem Health in Ponderosa Pine Forests of the Southwest - W. Wallace Covington; Peter Z. Fulé; Margaret M. Moore; Stephen C. Hart; Thomas E. Kolb; Joy N. Mast; Stephen S. Sackett; Michael R. Wagner (Journal of Forestry, 1997)

High Throughput Analysis and Purification in Support of Automated Parallel Synthesis - Harold N. Weller; Marian G. Young; Stephen J. Michalczyk; Gary H. Reitnauer; Robert S. Cooley; Peter C. Rahn; Dana J. Loyd; Dario Fiore; Steven J. Fischman (Molecular Diversity, 1997)

Wild-weed-crop complexes of common bean (Phaseolus vulgaris L., Fabaceae) in the Andes of Peru and Colombia, and their implications for conservation and breeding - Stephen Beebe; Orlando Toro Ch; Alma Viviana Gonza´lez; María Isabel Chaco´n; Daniel G. Debouck (Genetic Resources and Crop Evolution, 1997)

S-Phenylcysteine formation in hemoglobin as a biological exposure index to benzene - William E. Bechtold; James D. Sun; Linda S. Birnbaum; Songnian N. Yin; Guilan L. Li; Stephen Kasicki; George Lucier; Rogene F. Henderson (Archives of Toxicology, 1992)

Microbial degradation of the morphine alkaloids: identification of morphinone as an intermediate in the metabolism of morphine by Pseudomonas putida M10 - Neil C. Bruce; Clare J. Wilmot; Keith N. Jordan; Anna E. Trebilcock; Lauren D. Gray Stephens; Christopher R. Lowe (Archives of Microbiology, 1990)

Behavioraldominance and its relationship to habitat patch utilization by the hispid cotton rat (Sigmodon hispidus) - Stephen R. Spencer; Guy N. Cameron (Behavioral Ecology and Sociobiology, 1983)

The half-cycle sinusoid as an alternative defibrillating waveform in low-energy applications - Thomas W. Moore; Frank N. DiMeo; Stephen E. Dubin (Annals of Biomedical Engineering, 1977)